Essays on Economics of Litigation : an Application to Investor-State Disputes - Vu, Duy (Université Côte d'Azur, 2019)
International investment treaties often allow the foreign investor to sue the host country before international arbitration in case of breaches of treaty provisions. The number of investor-state disputes is growing so rapidly that some countries expressed their discomfort with the current international investment law regime. The first chapter gives readers a comprehensive view on the effectiveness and spillover effect of international investment arbitration. Based on a vast interdisciplinary literature, we reexamine recent criticisms and identify the root of the crisis faced by international arbitration. We conclude that it is possible for countries to adapt the current regime of international law to new situations without wholesale exit. The second chapter investigates the early settlement of investor-state disputes. Drawing on the rich economic literature and a new dataset related to treaty-based disputes, we find that the host state's experience, the case prospect, the nature of the regulatory measures, the identity of investors and Dutch investment treaties have significant impacts on the probability of early settlement. The third chapter focuses on an institutional dimension of arbitration: the effectiveness of ICSID in solving disputes. The time to resolution and the quality of the final judgment which is measured by the requirement of follow-on proceedings are used as performance indicators. We highlight how arbitrators' biographical and professional characteristics can impact the ICSID effectiveness. Les traités internationaux d'investissement permettent souvent à l'investisseur étranger de poursuivre le pays d'accueil devant un tribunal d’arbitrage international en cas de violation des dispositions du traité. Le nombre de différends entre investisseurs et États augmente si rapidement que certains pays expriment leur malaise à l'égard du régime actuel du droit international de l'investissement. Le premier chapitre donne aux lecteurs une vue générale sur l'efficacité et les effets de spillover de l'arbitrage international en matière d'investissement. En se basant sur une vaste littérature interdisciplinaire, nous réexaminons les critiques récentes et identifions la cause sous-jacente de la crise relative à l'arbitrage international. Nous concluons qu'il est possible pour les pays d'adapter le régime actuel du droit international à de nouvelles situations plutôt que de le quitter. Le deuxième chapitre étudie le règlement amiable des différends entre investisseurs et États. En nous fondant sur la riche littérature économique et sur une nouvelle base de données de différends relatifs à la violation des traités, nous constatons que l'expérience de l'État hôte, les perspectives du différend, la nature des mesures réglementaires, l'identité des investisseurs et les traités d'investissement néerlandais influencent significativement la probabilité d'un règlement rapide du différend. Le troisième chapitre se concentre sur une dimension institutionnelle de l'arbitrage : l'efficacité du CIRDI dans la résolution des différends. Le délai de résolution et la qualité du jugement final, représentée par la probabilité d'avoir des recours post-sentence, sont utilisés comme indicateurs de l'efficacité. Nous soulignons comment les caractéristiques biographiques et professionnelles des arbitres affectent l'efficacité du CIRDI.
Keywords: Analyse économique; Arbitrage international; Arbitrage international d'investissement; Centre international pour le réglement des différends relatifs aux investissements; Différends investisseur-Etat; Economic analysis; International Investment Arbitration; Investissements étrangers; Investor-state disputes; Médiation internationale

Arbitrage commercial international et politiques étatiques en matière commerciale : l'exemple du droit de la concurrence - Alhadidi, Ismaeel (Université de Bordeaux, 2019)
Il est admis que l’arbitrage international est impliqué dans l’assurance des politiques étatiques. Les droits nationaux contiennent des dispositions édictées en vue de protéger les intérêts étatiques et l’arbitre se trouve souvent amené à se prononcer sur une question qui met en jeu ces intérêts. Une telle opération n’est envisageable que si la matière en question est arbitrable. La question qui se pose est celle de savoir quelles sont les limites de l’arbitre dans la protection et l’assurance des politiques étatiques. En réalité plusieurs branches du Droit ont pour finalité d’assurer les politiques étatiques. A titre d’exemple, le droit de la propriété intellectuelle, le droit des sociétés, le droit de l’investissement et le droit de la concurrence peuvent être cités. Ce dernier constitue une bonne illustration des politiques étatiques. En effet, quand l’arbitre se charge de la mise en œuvre du droit de la concurrence, il est en train d’assurer le respect des politiques étatiques de l’Etat concerné.De ce fait, l’interaction entre l’arbitrage international et les ordres juridiques est devenue une réalité. Cette réalité procède de l’arbitrabilité des matières relevant de l’ordre public des Etats. Certains d'entre eux reconnaissent l’arbitrabilité des litiges intéressant l’ordre public comme le droit de la concurrence. D'autres n’acceptent pas que l’arbitre tranche ce type de litiges.La question de l’arbitrabilité objective nous conduit à étudier les différentes interactions entre l’arbitrage international et les politiques étatiques. Dans le cadre de cette étude, nous nous livrerons à l'étude des manifestations de cette interaction et des limites que l’arbitre doit considérer, du fait que la matière assurant des politiques étatiques, y compris le droit de la concurrence, n'est pas entièrement sujette à l’arbitrage.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitration; Competencia; Competition law; Concurrence; Policies; Politiques; State; Étatiques

The contribution mediation can make in addressing economic crime in corporate and commercial relationships in South Africa - Hoffman, Cornelia Hendrina (Stellenbosch University, 2019)
Economic crime is complex and costly. It is costly because it harms victims, both directly and indirectly, as well as the broader economy. The cost is not only financial, but also to confidence and trust in corporate and commercial relationships in South Africa. Economic crime is complex because it includes offences from common-law fraud to statutory contraventions such as incorrect bookkeeping. There are several mechanisms in the South African legal justice system to address economic crime. The conventional legal models include adversarial criminal prosecution of the offender and civil compensation claims, the model of inquisitorial administrative investigations and sanctions like penalties and compensation orders. In 2001 section 105A of the Criminal Procedure Act, namely plea and sentencing agreements, was added as a model of negotiated justice. This mechanism allows the prosecution and the offender to negotiate and enter into an agreement regarding the charges and the sanctions, subject to approval of the court that the plea of guilty is proper and that the proposed sanction is a just sentence. This dissertation proposes that mediation be added to the existing alternative models to help combat economic crime. Mediation involves negotiated justice, as well as restorative justice. More specifically, mediation as a restorative justice process, constitutes a practical alternative to standard litigation as the affected parties themselves, with the facilitation of a third person, resolve the disputes between them. Mediation, a facilitative and flexible procedure, allows the voices of both the victim and the offender to be heard securely and meaningfully. Mediation is rehabilitative and allows for agreed restorative provisions for both the perpetrator and the victims of economic crime. The outcome is a proposed amendment to the Criminal Procedure Act 51 of 1977, namely the insertion of section 105B, “Mediated Settlement Agreements”, that will provide for mediation and a mediated settlement agreement to be incorporated into and form part of the criminal justice processes. It is envisaged that an accredited mediator will mediate between the parties, including the public prosecutor, the perpetrator, the victim and possibly members of the community. The mediated settlement agreement will include both compensation for the victims and a proposed sentence for the perpetrator. This mediated settlement agreement will then be tabled before the court for adjudication and approval to serve as an effective court order. The proposal is a logical legal development of section 105A of the Criminal Procedure Act on plea and sentencing agreements, as the process of mediation builds on the process of negotiation established in it. To put it bluntly, if a plea and sentence agreement can be negotiated between the prosecutor and the offender, a plea and sentence agreement can be mediated between the prosecutor, the offender and the victim. Mediation can integrate and expand the constitutional principles of reparation and ubuntu and curb economic crime by providing an effective restorative and just response to it.
Keywords: Alternatives to prosecution; Commercial law; Dispute resolution; MARD; Mediación; Mediation; Mediação; Médiation; South Africa

De la conciliación a la mediación: alternativas para la gestión de los conflictos - Bartolomé Cantalejo, Mª Yolanda (Universitat de Barcelona, 2019)
En nuestro país, hasta hace unas décadas se desconocía la existencia de métodos de gestión y resolución de conflictos reglados diferentes al procedimiento judicial, a excepción del arbitraje y de algunas buenas prácticas consuetudinarias en las que se utilizaba el buen oficio de terceros, como, por ejemplo, el Tribunal de las Aguas en Valencia; también existía la conciliación previa al desarrollo del juicio, que salvo en la jurisdicción laboral había quedado relegada a ser un recurso residual, y muy pocas veces tenía efectos de terminación del procedimiento tras haberse alcanzado un acuerdo. Ante este panorama, no había más remedio que acudir al sistema adversarial para resolver los conflictos jurídicos que se producían en las relaciones entre las personas en el desarrollo de la vida tanto en el ámbito individual como colectivo. Y desde hace algún tiempo el sistema jurisdiccional se revelaba insuficiente para “absorber” la totalidad de las situaciones de conflicto que se producían de forma habitual en la sociedad; la complejidad de las relaciones interpersonales y la abundancia de situaciones donde se producen los conflictos, dada la evolución y las grandes transformaciones sociales de los últimos años. La implantación de la mediación en el ámbito civil y mercantil a partir de la publicación de la Ley 5/2012, de 6 de julio, de mediación en asuntos civiles y mercantiles, como método alternativo y/o complementario de la gestión y solución de conflictos, debería mejorar la eficacia en la búsqueda de solución a los conflictos planteados y su gestión de un modo más eficiente y rápido, evitando todos los inconvenientes que se producen en sede judicial cuando no queda más remedio que acudir al procedimiento judicial. Las ventajas más importantes son: el ahorro de costes y tiempo en relación al procedimiento judicial tradicional; una solución que supone una menor carga emocional para las partes en conflicto y que redundará en la posible continuación de las relaciones en el futuro, y todo ello facilitará sentar los principios para cambiar la cultura litigiosa existente en nuestro país, por una más conciliadora que suponga una mejor convivencia y una transformación pacífica de la sociedad, sin olvidar la descarga de asuntos con el consiguiente alivio de los órganos jurisdiccionales. Todo ello garantizará que los ciudadanos puedan solucionar sus controversias de forma rápida y eficaz y contribuirá a un mejor funcionamiento del sistema generando un mayor dinamismo de nuestra economía. Aunque no podemos olvidar la urgente necesidad de adaptar y modernizar nuestras leyes procesales y de incrementar el número de órganos judiciales para agilizar un sistema jurisdiccional que adolece de falta de personal, lentitud excesiva por la escasez de medios y de la abundante burocracia para llegar a resolver las controversias planteadas ante los tribunales de justicia. La mediación, por lo tanto, es una alternativa diferente para la solución de los conflictos a todos los niveles que tienen que afrontar los ciudadanos; se pueden resolver los conflictos de forma dialogada y con una actitud proactiva encaminada a encontrar una solución a sus diferencias con un mayor grado de satisfacción y bienestar, puesto que serán los propios implicados quienes ideen la solución a su conflicto, creando menos fricciones y evitando las situaciones más dolorosas y conflictivas para ellos y para su entorno, buscando una salida pacífica y consensuada. Y esta forma de resolver los conflictos no acarrea solo beneficios a las personas que lo utilizan a nivel individual, por solventar sus controversias de una manera más útil, rápida y eficaz, sino que sirve para que las controversias se pacifiquen y esto redundará en unas relaciones más eficientes que implicarán una sociedad más pacífica y con una menor tendencia a la confrontación con la consiguiente reducción de la hostilidad en nuestra sociedad.
Keywords: Ciències Jurídiques; Conflict management; Econòmiques i Socials; Gestió de conflictes; Gestión de conflictos; MARD; Mediació; Mediación; Mediation; Mediação; Médiation

Jurisdictional challenges and enforceability of arbitral awards in the UAE - Badr, Ahmed Abdelhafez (Université Paris Cité, 2019)
The United Arab Emirates (UAE) is one of the major emerging markets in the world. The economy of the UAE is the second largest in the Middle East (after Saudi Arabia), with an estimated gross domestic product (GDP) of USD 1422 billion in 2017. In connection with this economic development, the UAE attempted to establish a modernized legal system to accommodate domestic and foreign parties demanding efficient and independent dispute resolution. Many local and international companies, as well as individual investors operating in the UAE, agreed to submit their disputes to arbitration in their contracts as a neutral, efficient, predictable, and easily enforceable dispute resolution mechanism. However, historically, and due to specific incidents that happened during the western occupation to the Arab world, arbitration was frequently perceived in the Middle East as a western process that is neither naturally nor culturally connected to the traditional judicial system that was rooted in the Middle East's more developed countries in the 1950s and 1960s. This historical background could explain, to some extent, the existing animosity of certain national courts in Arab countries to international arbitration. Further, this is demonstration is closely connected to issues being studied in this dissertation in relation to: - The frequent number of arbitral awards being annulled in the UAE, and - The jurisdictional challenges to arbitral tribunals in the UAE. Studying UAE jurisprudence on cases confirming setting aside arbitral awards is one of the main themes being studied in the first Part of this thesis; the span of the study extends from 1995 to 2018. In order to diagnose the root causes of setting aside arbitral awards, it was essential to study each case that confirmed setting aside arbitral awards by UAE courts. Out of several hundred case laws in the UAE included in the study, over one hundred thirty case laws confirmed setting aside both domestic and international arbitral awards; each of these case laws was analyzed and discussed with particular emphasis on the problematic issues or procedure causing annulment. In order to suggest solutions to this problem, the research takes a comparative approach to contrast the UAE recognition and enforcement process of arbitral awards with more developed jurisdictions. France, naturally, is the primary jurisdiction for this comparative research. France has an international reputation as being one of the most (if not the most) supportive jurisdiction to recognizing arbitral awards and arbitration in general as a dispute resolution mechanism. Despite consuming considerable time searching for cases where the French courts set aside arbitral awards, only twenty-two case laws were identified where the French courts upheld the setting aside of arbitral awards. This relatively low number confirms the worldwide reputation that annulment of arbitral awards by the French courts is factually a rare incident given the considerable number of awards seated and/or being enforced in France. The broader comparative perspective reflects a consistent pattern that most developed jurisdictions generally respect, support, and recognizes arbitral awards. This has developed a general perception among parties to arbitration that arbitral awards, once issued, should be enforced voluntarily before initiating the enforcement process, whereby award debtors do not seek annulment and voluntarily satisfy the arbitral awards before the commencement of the enforcement proceedings due to their prior knowledge that national courts are likely to recognize and respect to arbitral awards.
Keywords: Arbitral Awards; Contestations juridictionnelles; Enforceability; Exécution; Jurisdictional challenges; Opposabilité; Sentences arbitrales; United Arab Emirates; Émirats arabes unis

O Favor Arbitrandum : Ensaio de uma teorização - Diamvutu, Lino (Universidade de Lisboa, 2019)
A presente tese constitui um ensaio de teorização do favor arbitrandum. A tese, contrariamente a algumas posições doutrinárias sobre o tema, não encara o favor arbitrandum como sendo uma política legislativa ou judiciária visando a promoção da arbitragem. Antes, ela procura, a partir das suas manifestações legais e jurisprudenciais, identificar um princípio jurídico, determinando o seu conteúdo, os seus limites e os seus fundamentos. O princípio do favor arbitrandum revela-se plurifacetado e não apresenta um alcance idêntico nos diversos ordenamentos jurídicos estudados. O seu conteúdo pode ser apreendido em dois sentidos principais. Trata-se, por um lado, de um critério interpretativo-decisional em matéria de validade da convenção de arbitragem, da competência do tribunal arbitral e de validade ou reconhecimento da sentença arbitral. Por outro lado, o favor arbitrandum é um princípio jurídico supralegal que se expressa como directriz orientadora da actividade legislativa, e, do trabalho interpretativo e integrativo pelo julgador das normas relativas à arbitragem. O princípio do favor arbitrandum encontra fortes limitações que podem ser de carácter geral (v.g. a aplicação da reserva da ordem pública, a ofensa dos bons costumes, a fraude, etc.), inerentes ao procedimento arbitral (a falta pelo árbitro do jus imperium, as anti-arbitration injunctions ou a responsabilização civil do árbitro) ou relativas à qualidade das partes envolvidas na arbitragem (a impecuniosidade das partes e a imunidade de execução dos Estados). Quanto aos seus fundamentos, o princípio do favor arbitrandum assenta em fundamentos jurídico-políticos e dogmáticos. Os seus fundamentos jurídico-políticos relacionam-se com o desenvolvimento do comércio internacional, a necessidade de redução das pendências nos tribunais judiciais, a concorrência entre Estados no acolhimento das arbitragens internacionais e o favor accordandum. O verdadeiro fundamento dogmático do favor arbitrandum encontra-se no princípio da tutela da confiança.
Keywords: Conteúdo do princípio; Favor arbitrandum; Fundamentos; Limites; Manifestações

Le consentement étatique à la compétence des juridictions internationales - Marquet, Clément (Université de Genève, 2019)
Le consentement étatique à la compétence des juridictions internationales est un élément incontournable du droit international public. Il régit le le fonctionnement de la justice internationale. Cependant, malgré son ubiquité, la notion est mal comprise. Ce travail, à travers la jurisprudence de la CIJ, d'ITLOS, de l'OMC et du CIRDI, redéfinit ce consentement, à la lumière de son histoire, son rôle et ses enjeux. Cette re-contextualisation est accompagnée d'une présentation et d'une analyse des enjeux contemporains entourant la notion.
Keywords: Arbitrage; Arbitragem; Arbitration; CIJ; CIRDI; Compétence; Compétence de la compétence; Consentement; Cour internationale de justice; Droit international public; Forum prorogatum; ICSID; ITLOS; Interprétation; Investissements; Investments; Juridictions; MFN; NPF; OMC; Organisation mondiale du commerce; Recevabilité; TIDM

Problems of Enforcement of ICSID Awards: An Analysis of Micula Case - Hasankhani, Ali (Public Law Researsh, 2019)
In the case Micula A.O. v. Romania, the arbitration tribunal established under the auspices of the International Center for Settlement of Investment Disputes (ICSID) sentenced Romania to pay a compensation for the revocation of investment incentives and for the breach of fair and equitable treatment principle that had been laid down in a bilateral investment treaty between Sweden and Romania. Considering investment incentives as a breach of the EU regulations regarding state aids, the European Commission then rendered a directive, prohibiting the enforcement of the arbitration award by the member states. As articles 53 and 54 of ICSID emphasize that the awards are binding, the EU Commission’s act of rendering the aforementioned directive, and the member states refusal to comply with the award equals to giving the EU law primacy over international law, which should be considered as a breach of their international obligations. Using a descriptive-analytical method, this article seeks to explain the viewpoints of the parties and the courts which were asked to enforce the award, as well as to determine the nature of their acts.

A arbitragem internacional de protecção de investimentos e a dupla nacionalidade: dois pode ser igual a zero? - Duarte, Tiago (e-Publica, 2019)
The assessment of the investor’s nationality is of utmost relevance to determine the arbitral tribunal’s jurisdiction in Investor-State Arbitration. In treaty-based arbitration the investor must give evidence that is protected by the BIT, which means that he must have the nationality of the State party to the BIT that is not the host State. The case law considers irrelevant the fact that the investor possesses another nationality besides the nationality of the State party to the BIT and considers also irrelevant the fact that the invoked nationality is not the dominant one. Things get more serious if the investor has also the nationality of the host State (double nationality). In this scenario the investor cannot launch an ICSID arbitration against the host State because the Washington Convention forbids it. The possibility of an ad hoc arbitration is subject to the interpretation of the applicable BIT which has led to an unstable case law both because the BITs are not all equal and because different tribunals have analyzed the dominant nationality doctrine in different ways. A determinação da nacionalidade do investidor é um dos elementos mais importantes para a verificação da jurisdição dos tribunais arbitrais nas arbitragens de proteção de investimentos. Nas arbitragens baseadas em BIT (bilateral investment treaties) o investidor que inicia a arbitragem tem de demonstrar que está protegido pelo BIT que pretende invocar, pelo que terá de possuir a nacionalidade do Estado parte nesse mesmo BIT, que não seja o Estado onde o investimento foi realizado. A jurisprudência tem considerado irrelevante o facto de o investidor poder ter outras nacionalidades, para além da nacionalidade do Estado parte no BIT, desvalorizando igualmente o facto de essa nacionalidade não ser a nacionalidade dominante do investidor. Tudo se complica no caso de o investidor possuir igualmente a nacionalidade do Estado onde o investimento foi realizado. Nesse caso o investidor não poderá iniciar uma arbitragem com base no ICSID tendo em conta que a Convenção de Washington veda essa possibilidade. Já no caso de arbitragens ad hoc tudo dependerá da interpretação do BIT em concreto, o que tem levado a uma flutuação jurisprudencial, seja porque os BIT são diferentes, seja porque tem havido diferentes abordagens jurisprudenciais quanto à relevância da nacionalidade dominante.

Proceedings of 1st Annual Research Symposium on International Commercial Arbitration - Casoria, Maria (Royal University for Women, 2019)
Keywords: Arbitrage; Arbitragem; Arbitration; Convention on the Recognition and Enforcement; Foreign Arbitral Awards; International Commercial Mediation; International Settlement Agreements; International commercial arbitration; MARD; Mediación; Mediation; Mediação; Médiation; UN Convention on International Settlement Agreements; UNCITRAL Model Law

Causes of Delay in the Resolution of Commercial Disputes via Litigation Arbitration as a Way out within OHADA Laws - Sigala, Buma Roland (International Journal of Trend in Scientific Research and Development, 2019)
An essential requirement of justice is that it should be dispensed as quickly as possible. It is a well-known adage that, « justice delayed is justice denied». Delay in litigation is caused by a number of factors. For example in litigation the parties have the right to make a counterclaim, right to make appeal etc. Arbitration has been able to overcome the factors which cause delay in litigation because in arbitration, parties are given the right to exclude the possibility to make a counterclaim, the right to make appeal has expressly been prohibited by the Organization for the Harmonization of Business Laws in Africa (OHADA)1 legislator etc. But since the OHADA legislator has not expressly prohibited counter claim in arbitration, it is recommended that counterclaim should be expressly prohibited in arbitration as it is the case with appeal. This article aims at identifying the causes of delay in the disposal of commercial disputes via litigation and how these causes of delay have been combated in arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial dispute; Delay commercial; Disputes Litigation; Law and management

Arbitraje Comercial Internacional. Reconocimiento y Ejecución de Sentencias y Laudos Arbitrales Extranjeros - Paulsson, Jan; Opertti Badán, Didier; Santos Belandro, Rubén; Bouchenaki, Amal; Ojea, Mildred; Rivera, Irma; Caivano, Roque J.; Solís Zelaya, Román; Fernández López, Alberto; Fresnedo de Aguirre, Cecilia; Gosis, Diego B.; Gomm Santos, Mauricio; et al. (IIJ, 2019)
Keywords: Arbitraje Comercial International; Arbitration; Commercial arbitration agreements; Conflict of laws; International arbitration award; Sentences arbitrales étrangères

Interaction entre les Cours de justice communautaires et les juridictions suprêmes nationales : spécificités de la Cour Commune de Justice et d’Arbitrage (CCJA) de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) - Ondo Mve, César Apollinaire (La diffusion de la jurisprudence des Cours suprêmes judiciaires francophones au temps d’internet, 2019)

Règlement d'arbitrage en vigueur à compter du 1er mars 2017, règlement de médiation en vigueur à compter du 1er janvier 2014 - Cour internationale d'arbitrage; Centre international d'ADR (Publication ICC, 2019)
Keywords: Arbitration; Mediation

Médiation du champ pénal dans le monde francophone - Jullion, Daniel (La lettre des médiations, 2019)
Initiée au milieu des années 80, dans le contexte bien particulier de la politique de la ville mise en place par un nouveau pouvoir politique, la médiation pénale a bénéficié du contexte très favorable des relations mises en place entre le politique et le judiciaire lors de la création du CNPD (1), sous la présidence de Gilbert Bonnemaison (2), des CCPD puis, en 1988 de la DIV (3) et, enfin la circulaire du 10 juillet 1989 « ... participation de l’institution judiciaire à la politique de prévention ». Véritables instances de concertation sur les problèmes de société et de sécurité, élus et professionnels se sont rapprochés sur leurs préoccupations communes : apporter une réponse « sociale » à un « contentieux de masse » (constitué de « petits » actes de délinquance qui participent au sentiment d’insécurité) et que « ... la Justice traiterait mal ou pas du tout ... » selon l’expression de G. Apap (alors procureur de la République de Valence) qui a initié les premières expériences de médiation pénale (appelée à l’époque « conciliation pénale » ... !!).
Keywords: Droit pénal; Mediation; Médiation

Les rapports entre la justice étatique et la justice arbitrale : Etude comparative France-OHADA - Kouchanou, Balbine Léa Modukpé (Université de Perpignan Via Domitia, 2019)
L’arbitrage est un moyen de gestion de litige apprécié et privilégié par les acteurs du commerce international. Son bon fonctionnement dépend de la justice étatique. Ces deux appareils doivent entretenir un rapport tantôt fusionnel et tantôt concurrentiel. Le déroulement de cette relation peut réciproquement susciter des complications et de la méfiance. En France comme dans plusieurs autres États de l’Afrique subsaharienne, le juge étatique est le collaborateur de l’arbitre malgré l’envergure de leurs rapports. Ces États reconnaissent à la justice étatique son pouvoir explicite et implicite durant l’arbitrage. La présente recherche et étude aborde la mise en œuvre des compétences respectives attribuées à l’arbitre et au juge durant l’arbitrage. Afin d’accentuer et de pérenniser le bon déroulement de l’arbitrage en France et en Afrique francophone, cette étude s’est attardée sur la question de l’arbitrabilité et du développement économique. Après avoir énuméré des réalités freinant la floraison durable de l’arbitrage en Afrique, quelques solutions sont proposées pour le préserver de tout dysfonctionnement. Arbitration has been used to resolving cases appreciated by international trade actors. However, well-functioning depends upon state justice. Both devices should have maintain a fusional and competitive relationship. The unfolding of this relationship can reciprocally bring complications and mistrust. State judge is referee’s collaborator despite the spacing of reports in France and several other states in sub-Saharan Africa. These states recognize the explicit and implicit power of state justice during arbitration. This study approaches courts assigned to the arbitrator and judge during their challenge. In order to accentuate and sustain the smooth running of arbitration in France and Francophone Africa, this research has been focused on the issue of economic development. After listing realities hindering the flowering of arbitration in this part of Africa, some solutions have been proposed to preserve this method of dispute resolution of dysfunction.
Keywords: Approximation; Arbitrage; Arbitragem; Arbitration; Cases; Différents; France; Interstate; Interétatique; Justice (administration); Pays de l'OHADA; Proceedings; Procédures; Rapprochement

What the African Continental Free Trade Agreement Protocol on Dispute Settlement says about the culture of African States to Dispute Resolution - Akinkugbe, Olabisi (Articles, Book Chapters, & Popular Press, 2019)
An effective Dispute Settlement Mechanisms (DSM) upholds a rules-based trade regime; enunciates, clarifies and develops the jurisprudence of its constituent trade agreement; and also ensures predictability in the trading regime. Article 20 of the African Continental Free Trade Agreement (AfCFTA) establishes the DSM. The AfCFTA Protocol on Dispute Settlement (“Dispute Protocol”) provides for the rules and procedures for the settlement of disputes. Unlike the majority of the African regional economic community courts that are modelled after the Court of Justice of the European Union, the AfCFTA-DSM follows a handful of other regional judicial bodies – such as the Southern African Community Development Community (SADC) and the Tripartite Free Trade Area Agreement (TFTA) – that are modelled after the World Trade Organization (WTO) dispute settlement mechanism.
Keywords: AfCFTA; Dispute Settlement Mechanisms; Free Trade; Trade Agreement

La transparencia en el arbitraje internacional y en los tratados bilaterales de inversión - Febles Pozo, Nayiber (Universitat de Girona, 2019)
The thesis's main objective is the analysis of transparency in international arbitration. To this purpose, we start from a broad conception of the notion of transparency and its relevance in the current Bilateral Investment Treaties (BITs) and in the main international arbitration regulations: the ICSID, the ICC, UNCITRAL and its Rules on Transparency in Treaty-based Investor-State Arbitration, followed by a study of the most important issues of the arbitration procedure related to transparency, such as public hearings, the participation of third parties in the procedure (third-party funders and amicus curiae), the appointment of arbitrators and the conflict of interests and, finally, the analysis of transparency in the decisions (arbitral awards). The thesis proposes and bases, among other issues, the need to create an ICSID Court of Appeal and, if not, the most suitable mechanism for the implementation of an International Investment Tribunal
Keywords: Advertising; Arbitrage; Arbitragem; Arbitraje internacional; Arbitration; Bilateral Investment Treaties (BITs); Confidencialidad; Confidencialitat; Confidentiality; Ethical principles; International Arbitration; International Investment Tribunal; Investments; Investor-state arbitration; Preciding; Principios éticos; Principis ètics; Publicidad; Publicitat; Transparencia; Transparency; Transparència

Harmonização das Regras de Execução do Acordo de Mediação Comercial Internacional - Carvalho, David França Ribeiro de (Universidade de São Paulo, 2019)
O acordo mediado é aquele alcançado pelas partes como resultado de um procedimento de mediação. Diversamente das sentenças arbitrais estrangeiras, as quais gozam de um instrumento global para seu reconhecimento e execução, sob os auspícios da Convenção de Nova York, os acordos mediados transnacionais não possuem um instrumento harmonizado ou uniformizado que lhes conferem a mesma segurança. A mediação é um método de resolução de conflitos cada dia mais utilizado nas relações comerciais transnacionais e o resultado alcançado pelas partes precisa ser provido de maior reconhecimento e exequibilidade transnacional. Assim, são apresentadas algumas questões conceituais sobre o reconhecimento e a execução dos acordos mediados comerciais transnacionais para, na sequência, evidenciando o fenômeno da transnormatividade e pluralidade normativa, apresentar o arcabouço jurídico existente e seus limites no âmbito europeu com a Diretiva Europeia 2008/52/CE e transnacional, com a Lei Modelo da UNCITRAL sobre Conciliação Comercial Internacional de 2002. Essas normas reforçam a importância da elaboração de instrumentos que possam melhor assegurar o reconhecimento e a execução dos acordos mediados transnacionais. São apresentados e examinados argumentos sobre a necessidade e eventuais formas para o reconhecimento e execução dos acordos mediados transnacionais, proporcionando um melhor acesso à justiça. Ao final, são evidenciadas formas para a harmonização/uniformização e contextualizada a questão no âmbito do ordenamento jurídico brasileiro.
Keywords: Acordo mediado transnacional; Cross-border enforcement; Harmonization; Harmonização; International commercial mediation; MARD; Mediación; Mediation; Mediação; Mediação comercial internacional; Médiation; Reconhecimento e execução; Transnational mediated settlement agreement

Proceedings ISDS reform conference 2019: mapping the way forward - Asian Academy of International Law (2019)
Keywords: Dispute settlement; Investment disputes; LAW REFORM; UN Commission on International Trade Law

La déjudiciarisation de l'arbitrage OHADA - Massosso Benga, Cruse Hervé (Université de Perpignan Via Domitia, 2019)
Historiquement, l'arbitre et le juge sont un vieux couple. Cette union légale procède de l'assistance technique que ce dernier porte à l'arbitre. Les nombreux dysfonctionnements que connaissent les justices étatiques des États membres de l'OHADA poussent ces derniers à réorganiser cette institution phare des États. A l'instar des États-Unis, du Canada ou encore de la France, les États membres de l'OHADA peuvent également opter pour une déjudiciarisation qui, délesterait le juge étatique de toutes ses tâches supplémentaires, dont celles relevant de l'arbitrage, spécifiquement pour les États de cet espace juridique. Dans cette hypothèse, il s'agira de bâtir un système arbitral totalement affranchi de toute intrusion du juge étatique. Ces travaux s'inscrivent donc dans une logique de droit prospectif, l'objectif étant à terme de présenter un droit de l'arbitrage totalement émancipé de l'apport du juge et ainsi, véritablement conférer à cette justice privée son caractère indépendant tant vanté. Historically, the referee and the judge are an old couple. This legal union proceeds from the technical assistance that the judge brings to the referee. The numerous issues faced by the state courts of the OHADA member states are forcing them to reorganize this all important institution. Just like in the United States, Canada or France, the OHADA member states can also opt for a judicial injunction, which would relieve the state judges of additional duties, including those related to arbitration specifically for the member States of this legal environment. In regard to this, it will be useful to build an arbitral system completely free from any intrusion of the state judge. This work is therefore part of a prospective-law approach, the ultimate goal being to present a right for arbitration totally liberated from the contribution of the judge and thus, truly confer to this private justice it’s independent character.
Keywords: Arbitrage; Arbitrage OHADA; Arbitragem; Arbitration; Déjudiciarisation; Indépendance des arbitres; Indépendence of arbitrator; OHADA Arbitration; Organisation pour l'harmonisation en Afrique du droit des affaires; Simplification du droit

Financement de l'arbitrage par un tiers : une approche française et international - Mechantaf, Khalil (Université Paris 1, 2019)
Le financement des procès présente de nombreux avantages pour le développement de l'arbitrage international, auparavant inaccessible aux parties impécunieuses. Les systèmes anglo-saxons, traditionnellement contre le financement des procès, commencent à introduire des règlementations facilitant l'accès au financement et promouvant son développement. La sophistication des formes de financement et le statut du tiers financeur apportent cependant une certaine complexité à l'exercice par l'arbitre de son pouvoir et au déroulement de la procédure arbitrale. Cette dernière reste gérer par le consensus des parties et la confidentialité de la procédure. La divulgation de l'accord de financement et la détermination du statut du financeur sont parmi les questions que posent l'existence d'un tiers dans la procédure arbitrale. Third-party funding presents various advantages for the development of international arbitration, previously inaccessible for insolvent parties. Common law systems, traditionally against the funding of litigation, are recently adopting regulations allowing access to funding and promoting its development. The sophistication of the forms of funding and the status of third-party funder give rise to certain challenges with regard to the exercise by the arbitrator of his/her powers and the administration of the arbitration process. This process remains widely governed by the will of the parties and the confidentiality of the procedure. The disclosure of the funding agreement and determining the status of the funder are amongst the various questions triggered by the presence of a third-party in the arbitration process.
Keywords: Arbitrage; Arbitrage international; Arbitragem; Arbitration; Common law; Confidentialité; Droit -- Aspect économique; Extension contrat; Financement; Third-party; Tiers; Tiers (droit)

L'administration de la preuve en arbitrage international au regard des règles de l'International Bar Association ainsi que des règles de Prague - Gommé, Laurence (Université de Liège, 2019)
Ce travail traite principalement de l’administration de la preuve en arbitrage international. Cette question divise les praticiens du monde arbitral en deux camps : ceux issus de la tradition de common law et ceux issus de la tradition de civil law. Dans un premier temps, les règles de l’International Bar Association relatives à l’administration de la preuve ont tenté de concilier ces deux traditions juridiques différentes. Dans un second temps, les règles de Prague ont, récemment, été publiées ce qui nous permettra, dans ce travail, d’analyser les deux systèmes pour ensuite les comparer. Enfin, nous essayerons d’envisager l’avenir de ces nouvelles règles de Prague.
Keywords: Arbitrage; Civil law; Common law; Preuve; Production de documents; Règles de Prague; Règles de l'IBA; Soft law

L'intervention du juge étatique dans le cadre des mesures provisoires ou conservatoires en présence d'une convention d'arbitrage : analyse du droit belge - Sabatini, Fiona (Université de Liège, 2019)
L’arbitrage, en tant que justice privée, s’entend comme un mode de règlement des différends tant alternatif qu’antagoniste de la justice étatique. Dépourvu d’imperium, l’arbitre peut nécessiter le soutien et la coopération du juge pour traiter une procédure arbitrale. Divers droits contemporains de l’arbitrage envisagent explicitement le recours aux mesures provisoires et conservatoires lors d’un arbitrage interne ou international sans nécessairement apporter une définition de ces mesures. En matière d’arbitrage, les mesures provisoires et conservatoires détiennent un rôle capital préalablement ou durant l’instance arbitrale. Elles permettent le maintien d’une preuve, d’une situation de fait ou de droit et garantissent ou préparent une exécution efficiente et rapide de la sentence. La réunion dans le chef de l’arbitre de la compétence au fond et celle au provisoire peut être défavorable aux intérêts des parties, notamment lorsque le tribunal arbitral n’est pas encore saisi. Dès lors, prenant en considération les particularités de l’arbitrage et plus particulièrement du déroulement du procès arbitral, l’intervention du juge est indispensable pour résoudre temporairement une urgence sur le fondement de l’apparence d’un droit afin de conférer une force exécutoire aux décisions de l’arbitre. Le tribunal arbitral n’est pas seul à décerner ces mesures. Il est subséquemment légitime de se questionner sur la position du juge au sujet des mesures provisoires et conservatoires lors d’un arbitrage. Après analyse des diverses dispositions du Code de l’arbitrage, il résulte que le législateur met un point d’honneur à orchestrer la relation entre l’arbitre et le juge étatique. Pour ce faire, il opte pour une distribution de compétences entre le juge du provisoire et l’arbitre, une sorte de répartition qui implique un retrait de la compétence exclusive de l’arbitre en termes de mesures provisoires et conservatoires. Aussi, délibérément choisi par les parties, l’arbitre prononce le droit, mais sa décision est dénuée d’imperium. C’est la raison pour laquelle le recours au juge étatique est indispensable afin de soutenir sa décision. En matière de mesures provisoires et conservatoires, la compétence du juge judiciaire est à la fois partagée avec l’arbitre, mais aussi exclusive.

Médiation dans le domaine de la santé - Bonafe-Schmitt, Jean-Pierre (La lettre des médiations, 2019)
Depuis le milieu des années soixante-dix, la médiation s’est développée dans tous les champs de la vie sociale de l’entreprise à la famille, sans oublier le quartier ou l’école… et plus tardivement dans le champ de la santé, ce qui tend à démontrer qu’il existe un certain nombre de résistances à son développement1. Pourtant, au-delà du phénomène de mode, il convient de s’interroger sur ce renouveau de la médiation qui ne peut pas être réduit à une simple technique de gestion des conflits, car elle vise plus largement à (re)créer du lien social dans nos sociétés marquées par l’individualisation, la fragmentation, le délitement des rapports sociaux. Le domaine de la santé n’échappe pas à ce délitement des se caractérise à la fois par la montée des incivilités et de la violence dans les établissements hospitaliers, et plus largement par une crise de confiance entre le monde médical et les patients.
Keywords: Mediation; Médiation; Santé

May an employer dismiss an employee if the disciplinary chair imposed a lesser sanction? South African Revenue Service v Commission for Conciliation Mediation and Arbitration 2017 38 ILJ 97 (CC) - Calitz, Karin Beatrix (Stellenbosch Law Review, 2019)
In South African Revenue Services v Commission for Conciliation, Mediation & Arbitration, Kruger, the employee, called his superior a “kaffir” on more than one occasion. The employer unilaterally dismissed the employee after the chairperson of the disciplinary hearing had imposed a lesser sanction. In doing so, the employer disregarded the collective agreement which did not make provision for the sanction of the disciplinary chair to be substituted. The employee claimed that his dismissal was invalid and therefore unfair. The Commission for Conciliation Mediation and Arbitration (“CCMA”), Labour Court and Labour Appeal Court (“LAC”) agreed. However, in the Constitutional Court (“CC”) the employer no longer argued that it was entitled to substitute the sanction in the light of the breach in the trust relationship, but only alleged that reinstatement was a remedy that no reasonable decision-maker would order. The CC agreed and held that the dismissal was substantively fair but procedurally unfair. The CC did not answer questions of lawfulness, fairness and invalidity, but in Steenkamp v Edcon the CC held that employees claiming remedies for unfair dismissal in terms of the Labour Relations Act 66 of 1995 (“LRA”) should not rely on invalidity. However, employees still have the right to common-law remedies based on their employment contract. Considering the importance of collective agreements, negotiated disciplinary codes, certainty and consistency, and to avoid employers exercising unfettered power over employees, state organs should apply for a review of an unsatisfactory sanction by the disciplinary chairperson in terms of section 158(1)(h) of the LRA. Private employers could negotiate a disciplinary code which allows both the employer and employee to appeal against the decision of the disciplinary chair which should make provision that a more severe sanction can be imposed on appeal.
Keywords: Arbitrage; Arbitragem; Arbitration; Commission for Conciliation; Dismissal of employees; Labor discipline; MARD; Mediación; Mediation; Mediação; Médiation; South Africa; South African Revenue Services

La protection du tiers lésé par une sentence arbitrale - Do, Van dai (Revue internationale de droit comparé, 2019)
L’arbitrage est un mode de règlement des litiges convenu entre les parties mais il se peut que la sentence issue de ce mode de règlement porte atteinte au tiers, qui n’est ni partie, ni représenté à l’instance arbitrale. La présente étude comparative montre qu’il existe divers moyens de protection offerts au tiers lésé mais le meilleur instrument de protection est la tierce opposition contre la sentence arbitrale. Toutefois, une telle tierce opposition est encore peu connue dans le monde, de très nombreux systèmes, l’ignorent. En espérant que ce recours se développe au profit du tiers, cette étude montre ses avantages, sa consécration dans certains pays ainsi que son régime juridique. Arbitration is a mode of dispute resolution agreed between the parties but it is possible that the award resulting from this method of settlement infringes a third party’s right, who is neither a party nor represented in the arbitration proceedings. This comparative study shows that there are various means of protection offered to the injured third party but the best protection instrument is the third party opposition to the arbitration award. However, such a third party opposition is still not widely known in the world, many systems ignore it. Hopefully this remedy will be developed for the benefit of the third parties, this study shows its advantages, its recognition in certain countries as well as its legal regime.

L'avocat et la résolution des conflits - Dutoit, Nicolas (Anwalts Revue de l'Avocat, 2019)
Keywords: Arbitrage; Conciliation; Différends; Droit collaboratif; Litiges; Médiation; Négociation; Orientation préalable; Résolution de conflit

A Critical Look at the Mechanism for Challenge of Arbitrators Under ICSID Convention and Arbitration Rules - Gautama, Ivan (Juris Gentium Law Review, 2019)
Administered arbitrations under ICSID are amongst the most-utilized means to resolve investor-state disputes. Part of why it is so is because the ICSID as an institution is heavily affiliated with the World Bank. This affiliation serves as a double-edged sword in ICSID’s hands: while on one side such affiliation lends ICSID the credibility any successful arbitral institutions need, on the other side ties between the two institutions are proving to become too close for comfort. This paper explores what could go and has gone wrong in the past within the current ICSID arbitration system with regards to the mechanism for challenging arbitrator(s), and whether such mechanism allows ICSID to effectively deliver what it is expected to provide.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; Conflict of interest; ICSID; Investor-State; World Bank

Online Dispute Resolution: Methods and Effects - Kumari, Poonam; Sood, Geetika (International Journal of Science and Research, 2019)
The concept of online dispute resolution came with the development of e-commerce. It is a branch which resolves the dispute between parties without interference of court. It includes arbitration mediation and negotiation. It also includes consumer to consumer disputes. With the emerging to globalisation the concept of online dispute resolution emerging day by day. The purpose of this study is to present the main facets of online dispute resolution, including a definition of the term, the types of resolution available, and the most recent legal regulations in this area. Thearticle is a study of ODR, online mediation and electronic arbitration. It includes their uses and their relationships with e-commerce. The paper is regarding primary aspects of online dispute resolution, its definition and its growth and development. It also includes the relationship between ODR and technology. Research paper isdiscussing the two forms of ODR: online mediation and electronic arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration; Online Dispute Resolution

El estatuto jurídico de los árbitros en el sistema CIADI - Soto-Díaz, David (Universidade da Coruña, 2019)
[Resumen] El arbitraje entre Estados y particulares extranjeros es un mecanismo de resolución de litigios a caballo entre el Derecho internacional público y el Derecho privado, que desde finales de la década de 1990 ha vivido un sorprendente auge a nivel mundial. Una modalidad de arbitraje institucional de inversiones es la del CIADI -Centro Internacional para el arreglo de Disputas sobre inversiones-, organismo dependiente del Grupo del Banco Mundial. El propósito de la tesis es llevar a cabo una investigación sobre la configuración de la independencia e imparcialidad de los árbitros del CIADI, sus derechos y deberes en tanto que tales y sus facultades procesales. La investigación se valdrá del Derecho comparado, tanto nacional como internacional, realizando una análisis de la doctrina, la práctica y la legislación que regula el sistema CIADI. A arbitraxe entre Estados e particulares estranxeiros é un mecanismo de resolución de controversias a cabalo entre o Dereito internacional público e o Dereito privado, que dende finais da década de 1990 viviu un sorprendente auxe a nivel mundial. Unha modalidade de arbitraxe institucional de investimentos é a do CIADI -Centro Internacional para o Arranxo de Desputas sobre Investimentos-, organismo dependente do Grupo do Banco Mundial. O propósito da tese é facer unha investigación sobre a independencia e imparcialidade dos árbitros do CIADI, os seus dereitos e deberes como tales e as súas facultades procesuais. A investigación valerase do Dereito Comparado, tanto nacional como internacional, realizando unha análise da doutrina, a práctica e a lexislación que regula o sistema CIADI. Arbitration between States and foreign investors is a dispute-resolution mechanism halfway between international public Law and private Law, which had surprisingly rised during the 1990's at the world level. In this work the following issues will be tackled: the legal nature of the aforementioned arbitrators. ICSID -International Centre for the Settlement of Investments Disputes- is a modality of institutional arbitration for investments. This institution is incarditated into the World Bank Group. The aim of this dissertation is to carry out a research on the configuration of the independence and impartiality of ICSID arbitrators, as well as their duties and rights as such and their procedural faculties. The research will be based on both national and international comparative Law, focusing in legal doctrine, in praxis and in the law governing the ICSIS system.
Keywords: Arbitrage international; Arbitragem; Arbitraje internacional; Arbitration; Derecho comparado; Mercado financiero-Derecho

Emerging Issues in Arbitration, Mediation and Conciliation - Sunil, Bhawna Bhelly (International Journal of Science and Research, 2019)
The resolution of disputes through alternative dispute resolution mechanisms has gained momentum over recent decades. It has increasingly occupied space in the academic literature as the “new” method to achieve “justice” for disputing parties. It is important to note that a variety of definitions of “justice” can be relied upon. However, in many cases, justice will mean the parties being able to resolve their dispute fairly, justly and amicably by applying law or legal principles. Traditional legal mechanisms for resolving disputes have been increasingly questioned as to whether they are actually capable of achieving justice in individual cases. Resolution in the courts is not only the method of resolving disputes . If the parties can resolve their own disputes then there will arise no need for court system in world. All though court system is good and fair way of dealing with civil disputes yet it might not be the best method to resolve the disputes. Basically there are four ways to of alternate dispute resolution. They are Negotiation, Mediation, Conciliation and Arbitration . The of ADR is to resolve the matters in a cost effective manner and foster long term relationship.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitration; Conciliation; MARD; Mediación; Mediation; Mediação; Médiation; Méthodes alternatives de règlement de conflit

Milletlerarası Özel Hukukta arabuluculuk - Yarar, Güven (Akdeniz Üniversitesi, 2019)
Son yıllarda farklı hukuk düzenlerinde ve Türk hukukunda uyuşmazlıkların arabuluculuk yoluyla çözümü hususunda önemli gelişmeler kaydedilmesine rağmen bünyesinde yabancılık unsuru barındıran arabuluculuk faaliyetleri konusunda belirsizlik bulunmaktadır. Zira arabuluculuk faaliyetinin birden fazla hukuk düzeni ile irtibatlı olmasının arabuluculuk sürecine etkisine yönelik yasal düzenleme ve monografik çalışma eksikliği mevcuttur. Bu nedenle, arabuluculuk faaliyetinin yabancılık unsuru içermesi hâlinde meydana gelebilecek Kanunlar İhtilâfı ve Milletlerarası Usul Hukuku meselelerinin tespit edilip çözüm önerileri sunulması teorik ve pratik açıdan son derece önemlidir. Bu çalışma kapsamında ilk olarak, arabuluculuğa ilişkin genel bilgiler verilmiş ve arabuluculuğun hukuk sistemlerindeki yeri incelenmiştir. Akabinde arabuluculuğun Kanunlar İhtilâfı boyutu üzerinde durulmuş ve arabuluculuk faaliyeti kapsamında meydana gelebilecek Kanunlar İhtilâfı meselelerinin çözülebilmesi için terminoloji oluşturulması gereği anlaşılmıştır. Bu bağlamda, millî, milletlerarası ve milletlerarası ticarî arabuluculuğun çerçevesi genel hatlarıyla çizilmiştir. Ardından arabuluculuk faaliyetinin temel taşları niteliğinde olan arabuluculuk ve arabulucu sözleşmesine uygulanacak hukuka dair değerlendirme yapılmış, arabuluculuğa elverişliliğe ve arabulucunun hak ve yükümlülüğüne uygulanacak hukuka ilişkin muhtemel sorunlar tespit edilip çözüm önerilerinde bulunulmuştur. Arabuluculuğun Milletlerarası Usul Hukuku boyutu kapsamında ise arabuluculuk usulüne uygulanacak hukukun önemi ve bu hukukun tespitinde kullanılabilecek kriterlere yer verilmiştir. Daha sonra, birden fazla hukuk düzeni ile irtibatlı bulunan arabuluculuk faaliyetinin başarıyla sonuçlanmasıyla oluşan milletlerarası anlaşma belgesi ele alınmıştır. Bu bağlamda, milletlerarası anlaşma belgesinin mevcudiyeti için kabul edilebilecek koşullara yönelik değerlendirme yapılmıştır. Son olarak, milletlerarası anlaşma belgesinin tanınması ve tenfizine yönelik ihtiyaç tespit edilmiş, milletlerarası anlaşma belgesinin tanınması ve tenfizine ilişkin kabul edilebilecek ön ve aslî şartlar ile tanıma-tenfiz usulüne yer verilmiş ve sonuç ve değerlendirmelerde bulunularak çalışmamız tamamlanmıştır. Although significant progress has been achieved in different legal systems and Turkish law in terms of settlement of disputes through mediation for last years, there is uncertainty regarding mediation activities that include foreign elements. The reason is that there is not much legal regulation and monographic studies on the effect of mediation activity being linked to more than one legal order over mediation process. For this reason, it is very important theoretically and practically to identify the issues of Conflict of Laws and International Procedural Law that may occur in case of mediation activity involving foreign elements. In this study, first of all, general information concerning mediation is given and the legal aspect of mediation is examined in legal systems. Subsequently, the legal aspect of mediation in conflict of law was emphasized and it was understood that the terminology should be established in order to solve the Conflicts of Laws that may occur within the scope of mediation activity. In this context, the framework of national, international and international commercial mediation is outlined. Then, the assessment of the law to be applied to the mediation and mediation agreement which is the cornerstones of the mediation activity was made, possible problems related to the mediability and mediation of the mediator's rights and obligations were identified and solutions were proposed. Within the scope of mediation law aspect of International Procedural Law, the importance of the law to be applied to mediation procedure and the criteria that can be used in determining this law are included. Following this, the international agreement document which was formed by the successful completion of the mediation activity which is connected with more than one legal order was emphasized. In this context, an assessment was made on the conditions acceptable to the existence of the international convention. Finally, the need for the recognition and enforcement of the international agreement document was determined and our study was completed making results and evaluations by including the prerequisite and essential conditions for the recognition and enforcement of the international agreement document and the recognition-enforcement procedure.
Keywords: Arabuluculuk; Droit international privé; International law; International private law; Mediation; Médiation; Uluslararası hukuk; Uluslararası özel hukuk

La collaboration entre la CCJA et les juridictions nationales de cassation dans le cadre du droit OHADA - Assi N'Guessan, René Marcel (Université de Perpignan, 2018)
La collaboration entre la CCJA et les juridictions nationales de cassation, s’effectue dans le contentieux des Actes uniformes. Il met en oeuvre la supranationalité judiciaire de la CCJA qui se manifeste par sa substitution aux juridictions nationales de cassation soulevant des questions liées aux Actes uniformes. Il faut reconnaître que la complémentarité de la collaboration entre la CCJA et les juridictions nationales de cassation dans le recours en cassation devant la CCJA fait ressortir différents des problèmes : une inconstitutionnalité du Traité ou des Actes uniformes dans le processus d’intégration, des inquiétudes dans la procédure de recours en cassation (pas d’auto-saisine de la CCJA, absence de cas d’ouverture à cassation devant la CCJA, formule exécutoire sur les arrêts de la CCJA), l’évocation, la substitution des juridictions nationales de cassation créent devant la CCJA, une controverse dans l’identification du juge compétent dans les procédures de l’AUPSRVE, un risque de conflit de compétence et de lois avec des organisations régionales surtout (UEMOA). Cette collaboration se poursuit entre le juge étatique et la CCJA dans l’arbitrage, c’est le mode de règlement des litiges dans le système OHADA, à cause de l’éthique de l’arbitrage. Ce mode de règlement des litiges dans le mode des affaires ne répond plus au critère du monde des affaires. Même si l’arbitrage OHADA est dual (ad hoc et CCJA), il faut trouver des moyens dans divers droits plus adéquats pour pallier aux divers problèmes évoqués dans le monde des affaires.
Keywords: Arbitrage; Arbitration; Arbitration Agreement; Auto-saisine; CCJA; Connectedness; Controverse; Controversy; Inconstitutionnalité; Litispendance; Organisation pour l'harmonisation en Afrique du droit des affaires; Self-referral; Unconstitutionality

Règlement des différends relatifs à l'investissement dans le système de règlement des différends de l'Organisation Mondiale du Commerce (OMC) : Étude comparative entre l'arbitrage investisseur-Etat et les mécanismes de règlement des différends de l'OMC - Al Jehni, Rania (Université Paris-Est, 2018)
Les investisseurs étrangers dans les secteurs de services occupent une position particulière dans le droit économique international : ils sont couverts par des accords internationaux d'investissement ainsi que par des disciplines multilatérales sur le commerce des services. Contrairement à ce que la pratique actuelle suggère, les deux principales composantes du droit économique international, à savoir le droit commercial et le droit des investissements, fusionnent. Ils partagent non seulement des principes et des règles essentiellement équivalents, mais leurs disciplines s'appliquent également aux mêmes sujets et situations. Les accords internationaux d'investissement et les règles de l’OMC sur le commerce des services (disciplines de l'AGCS), bien que de nature très différente, présentent des principes communs qui favorisent l'investissement international dans les secteurs de services. En particulier, les deux ensembles d'accords consacrent des obligations de non-discrimination entre les investisseurs étrangers et nationaux dans les secteurs de services. Dans cette situation, les investisseurs étrangers profitent également des obligations que les deux ensembles d'instruments imposent aux États contractants. Ces instruments prévoient de solides mécanismes de règlement des différends en cas de violation de leurs obligations. Les investisseurs étrangers dans les secteurs de services peuvent donc avoir recours à deux mécanismes alternatifs de règlement des différends pour contester les mesures de leurs pays hôtes qui enfreignent les obligations internationales.L’OMC, contrairement au CIRDI, est beaucoup plus qu’un simple système de règlement des différends : l’OMC possède un élément institutionnel important qui a la capacité de fournir et d’appliquer les valeurs systémiques. Cette différence fondamentale entre le système de règlement des différends de l’OMC et d’arbitrage du CIRDI fournit une perspective analytique à travers laquelle l’étude évalue et compare la portée précise du chevauchement entre les disciplines du commerce et de l'investissement, ainsi que la capacité des parties privées à recourir à ces mécanismes de règlement des différends.Du point de vue méthodologique, deux approches sont concevables. Une analyse comparative et contextuelle : l'accent est mis sur les accords internationaux accordant la qualité pour les parties privées dans les procédures internationales de règlement des différends. L'attention est attirée sur le droit international du commerce et d'investissement, en comparant les principes, les règles et les mécanismes de règlement des différends du cadre de l'investissement international (y compris les accords qui définissent les relations d'investissement internationales) et le cadre d'investissement assez limité de l'OMC, principalement les dispositions pertinentes de l'AGCS. Une approche inductive, la jurisprudence est également pertinente. Un examen approfondi de la jurisprudence existante sur chaque sujet, afin de clarifier le sens de règles par ailleurs vagues et ambiguës et de répondre finalement à la question de savoir si les procédures de règlement des différends de l'OMC pourraient constituer une alternative valable pour le règlement des différends entre l'investisseur dans le secteur de services et l'État.
Keywords: CIRDI; Centre international pour le réglement des différends relatifs aux investissements; Commerce international; Différends; ICSID; Investissements; Investissements étrangers; Investment; Investments; OMC; Organisation mondiale du commerce; Réglementation; Settlement; WTO; Échanges internationaux de services

The defence of illegality in international investment arbitration : a hybrid model to address criminal conduct by the investor, at the crossroads between the culpability standard of criminal law and the separability doctrine of international commercial arbitration - Busco, Paolo (Sant'Anna School of Advanced Studies ; Université Paris 1, 2018)
Cette thèse analyse la question relative au cas où, dans l'arbitrage international en matière d'investissements, dont le but principal est l'application des normes visées à la protection des investisseurs, l’État défendeur soutient que l'investissement pour lequel la protection est demandée a été obtenu au moyen d'une forme de criminalité. Dans ce contexte, la défense de l'illégalité soulevée par les État dans les contentieux d'investissement est de plus en plus courante. Cette défense fonctionne selon le schéma suivant : un État hôte enfreint les dispositions de fond que le droit international accorde aux investissements effectués dans un pays étranger, par exemple en expropriant un investisseur étranger de son investissement sans indemnité. Dans le différend qui s'ensuit devant un tribunal arbitral d'investissement, l'État défendeur invoque l'illégalité commise par l'investisseur lors de la réalisation de l'investissement pour se défendre contre la procédure arbitrale intenté contre lui. Le but principal de cette étude est celui de démontrer que des considérations systématiques de nature strictement juridique, aussi bien que de politique juridique, exigent que la défense d'illégalité dans l'arbitrage d'investissement soit strictement restreinte et qu'un tribunal ne puisse décliner d'exercer sa compétence / juridiction que dans des cas exceptionnels. Cette étude aboutit à la conclusion d'après laquelle les tribunaux d'arbitrage devraient plutôt examiner au cas par cas au stade du fond l'ensemble des circonstances soumises devant lui et procéder à une mise en balance appropriée entre les comportements de l'investisseur et ceux de l'État hôte. This thesis addresses the question as to how an investment Tribunal is to react if, in the context of a case brought before it for breach of standards of protection of an investment, the respondent argues that the investment for which protection is sought has been secured by resorting to some form of criminality. Against this background, a defence by the Host State that has become increasingly common is the so-called Defence of Illegality. It operates on the basis of the following scheme : a Host State breaches the substantive provision that international law accord to investments made in a foreign Country, for instance by means of expropriating without compensation the investor's investment. In the ensuing dispute before an investment Tribunal, the defendant Host State raises the illegality committed by the investor in the making of the investment as defence against the breach of the substantive provisions on the protection of the investment, of which it is accused, to avoid responsibility. This thesis intends to demonstrate that both legal and policy consideration dictate that the Defence of Illegality in investment arbitration should be strictly curtailed and that a Tribunal should only decline to exercise its jurisdiction in exceptional cases. Rather, Tribunals should look at the entire set of circumstances at the merits stage and perform a proper balancing test between the conduct of the investor and the Host State.
Keywords: Admissibility and jurisdiction; Admissibilité; Approche comparée; Arbitrage; Arbitrage commercial; Arbitrage d'investissement; Arbitrage et crime; Arbitrage international; Arbitragem; Arbitration; Arbitration and crime; Clause de légalité; Clean hands doctrine; Commercial Arbitration; Comparative law; Compétence; Compétence juridictionnelle; Corruption; Defence of Illegality; Doctrine des mains propres; Défense d'illégalité; Investment arbitration; Investments

L'unité fondamentale des accords amiables - Poli, Catherine (Aix-Marseille Université, 2018)
Les processus de résolution amiable des différends – conciliation, médiation, procédure participative ou droit collaboratif – présentent une unité d’objectif. Leur mise en œuvre permet une tentative de conclusion d’un accord amiable : un contrat consacrant la solution du différend construite par les parties. Sans se départir d’une approche procédurale, cette étude propose une analyse contractuelle de la résolution amiable des différends. Au-delà d’une procéduralisation de la formation de l’accord amiable, le droit commun des contrats sert en effet de manière unitaire les négociations et la conclusion de l’accord amiable. Ce dernier présente néanmoins une certaine diversité au regard des qualifications contractuelles qu’il peut revêtir. Si le contrat de transaction apparaît comme un référent à l’accord amiable, tout accord amiable ne consiste pas nécessairement en une transaction. Mais au-delà du jeu des qualifications possibles, le droit commun des contrats fédère les conditions de validité et les forces de l’accord amiable. Une unité fondamentale des accords amiables se révèle ainsi, garantissant la résolution effective des différends. The amicable settlement process - conciliation, mediation, collaborative procedure or law - present the same aim. Every amicable settlement process permits the conclusion of an amicable agreement: a contract consecrating the solution built by the parties. Without distracting from procedural approach, this study offers a contractual analysis of the amicable dispute resolution. Beyond a proceduralisation of the negotiation and the amicable settlement formation, it is the general law of contract that insure a support to the amicable settlement process. However, the amicable settlement presents some diversity due to peripheral qualifications. If the transaction contract is a reference to the amicable settlement, every amicable settlement is not necessarily a transaction. Beyong the choice of qualifications, the general contract law unites the validity conditions and the forces of the amicable settlement. A fundamental unity of amicable settlements reveals, safeguarded the effective dispute resolution.
Keywords: ADR; Accord amiable; Alternative dispute resolution; Amicable settlement; Amicable settlement process; Collaborative law; Conciliation; Conciliation process; Droit collaboratif; MARD; Mediación; Mediation; Mediação; Modes alternatifs de résolution des différends; Médiation; Processus de résolution amiable des différends; Procédure participative; Résolution amiable des différends; Transaction; Transaction (droit); Transaction agreement

Arbitraje y propiedad intelectual: consideraciones procesales y desafíos para un arbitraje eficiente - Gil Seaton, Ayllen (Universitat Pompeu Fabra, 2018)
En el presente trabajo se propone estudiar al arbitraje en materia de propiedad intelectual desde una perspectiva procesal, con miras a contribuir a la eficiencia y eficacia de su procedimiento. La especial idoneidad del arbitraje como mecanismo de resolución de estas controversias, muestra la fuerte conexión entre los derechos de propiedad intelectual y el arbitraje. Sin embargo, del estudio empírico realizado se revela una disonancia entre el desarrollo de los derechos de propiedad intelectual y la evolución del arbitraje en la materia. A partir de esta primera constatación, se profundiza en la identificación de tres obstáculos clave en el funcionamiento del arbitraje y se sugiere recurrir al derecho procesal como método de solución de los mismos. Finalmente, se proporcionan herramientas concretas de solución en materia de arbitrabilidad, intervención de terceros y efectos del laudo. Todo lo anterior con el objetivo de consolidar al arbitraje como un mecanismo de resolución de disputas en materia de la propiedad intelectual.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Intellectual property; Propriedad intelectual; Propriedade intelectual; Propriété intellectuelle

Modes alternatifs de résolution des conflits – droit des affaires - Conférence internationale des barreaux CIB (2018)

Le procédé de passerelle entre la conciliation et la sauvegarde - Approche comparative droit français/droit OHADA - Kourouma, Moussa Fanta (Université de Toulon, 2018)
Cette thèse porte sur le procédé de passerelle entre la conciliation et la sauvegarde, dans une approche comparative droit français, droit OHADA. Le procédé de passerelle permet au chef d’entreprise d’élaborer un plan de redressement dans le cadre de la conciliation, avant de le faire adopter lors d’une sauvegarde accélérée. La présente thèse se subdivise en deux parties. Dans la première partie, un diagnostic est posé pour comprendre les raisons de l’adoption de ce mécanisme de traitement des difficultés des entreprises en droit français, et celles qui pourraient ou non justifier sa reconnaissance en droit OHADA. Il ressort de cette partie que, dans les droits français et OHADA, la rigidité du régime de la cessation des paiements ainsi que l’unanimité obligatoire de l’accord de conciliation constituent un handicap au redressement des entreprises, car le principe d’unanimité donne un droit de véto à chaque créancier. Le procédé de passerelle permet de passer outre l’opposition des créanciers minoritaires qui utilisent ce droit de véto pour faire adopter le projet de redressement du chef d’entreprise par vote majoritaire sur le terrain judiciaire. Dans la deuxième partie, une étude prospective est menée ; le procédé de plan pré-négocié joue un rôle à la fois préventif et curatif : il permet, d’une part, la libre négociation, entre un débiteur et ses créanciers, d’un plan conventionnel de restructuration et, d’autre part, l’anticipation de l’intervention du tribunal pour optimiser l’actif et maîtriser le passif. Le procédé de passerelle est adopté en droit français ; la présente thèse propose une étude de son régime juridique. Il n’est pas reconnu pour le moment en droit OHADA ; son applicabilité y est analysée. Pour l’amélioration de la prévention et du traitement des difficultés des entreprises dans les droits français et OHADA, des pistes sont proposées. Il en est ainsi notamment, d’un côté, de l’adoption des comités de créanciers dans la procédure de conciliation française et, de l’autre, de la reconnaissance du mécanisme de plan pré-négocié, de la réforme du régime de la cessation des paiements et de la spécialisation des tribunaux connaissant des contentieux régis par l’AUPC en droit OHADA. La présente étude, en plus d’apporter une contribution scientifique à l’étude des nouvelles procédures de sauvegarde accélérée en droit français, vise à lancer le débat sur l’opportunité de l’adoption du procédé de passerelle en droit OHADA. L’organisation de la cession pré-arrangée dans le cadre du mandat ad hoc en droit français et l’opportunité de l’adoption d’une telle cession en droit OHADA sont des problématiques qui pourraient faire l’objet d’une recherche. This thesis focuses on the bridging process between conciliation and safeguarding, in a comparative French law approach, OHADA law. The gateway method allows the entrepreneur to develop a recovery plan in the context of conciliation, before adopting it during an accelerated backup. This thesis is divided into two parts. In the first part, a diagnosis is made to understand the reasons of the adoption of this mechanism of treatment of the difficulties of the companies in French law, and those which could or could not justify its recognition in OHADA law. It appears from this section that, in the French and OHADA laws, the rigidity of the system of cessation of payments and the compulsory unanimity of the conciliation agreement constitute a handicap to the recovery of the undertakings, since the principle of unanimity a veto right to each creditor. The gateway process makes it possible to override the opposition of the minority creditors who use this right of veto to get the project of recovery of the head of enterprise adopted by majority vote on the legal ground. In the second part, a prospective study is conducted; The pre-negotiated plan process plays both a preventive and curative role : it allows, on the one hand, the free negotiation, between a debtor and its creditors, of a conventional restructuring plan and, on the other hand, the anticipation of court intervention to optimize assets and control liabilities. The gateway method is adopted in French law; this thesis proposes a study of its legal regime. He is not recognized for the moment in OHADA law ; its applicability is analyzed. For the improvement of the prevention and the treatment of the difficulties of the companies in the French rights and OHADA, tracks are proposed. This is notably the case, on the one hand, of the adoption of the creditor committees in the French conciliation procedure and, on the other, of the recognition of the pre-negotiated plan mechanism, of the reform of the cessation of payments and specialization of courts dealing with disputes governed by the AUPC under OHADA law. This study, in addition to making a scientific contribution to the study of new accelerated safeguard procedures in French law, aims to launch the debate on the appropriateness of the adoption of the OHADA gateway process. The organization of the pre-arranged assignment under the ad hoc mandate in French law and the advisability of adopting such an assignment in OHADA law are issues that could be the subject of research.
Keywords: Cessation des paiements; Cessation of payments; Conciliation; Contractualisation; Contractualization; Droit du travail; Entreprises; Entreprises en difficulté; Etude comparative; Expedited backup; Faillite; France; Gateway process; Labour law; MARD; Mediación; Mediation; Mediação; Médiation; Negociation; Négociation; Pays de l'OHADA; Plan pré-négocié; Pre-negotiated plan; Prepack-cession; Prevention; Preventive regulation; Procédé de passerelle; Prévention; Règlement préventif; Sauvegarde accélérée; Transmission

Les émanations de l'État à vocation économique dans l'arbitrage des investissements et dans le contentieux de l'O.M.C - Cortesi, Giulio Alvaro (Université Paris 1 ; Università degli Studi di Padova, 2018)
L'idée de cette thèse sur le droit international des investissements concernant les entreprises d'État trouve son origine dans l'impressionnant développement économique de ces dix dernières années. D'une part, ce dernier donne une pertinence considérable à ce thème compte tenu de son actualité. D'autre part, il existe un intérêt considérable pour les problèmes juridiques laissés en suspens par ces entités. Cette thèse commence par un chapitre préliminaire dans lequel la forme juridique de ces institutions est analysée, à la fois avec une évaluation empirique et du point de vue du droit national et international applicable à ces sujets. L'analyse empirique approfondie qui n'a pas encore été réalisée dans les recueils de contributions examinés s'est révélée fondamentale, car certaines des questions juridiques concernant les entreprises d'État ne pourraient vraiment pas être abordées sans une telle approche. Le corps plus juridique de la thèse, consacré uniquement à l'analyse juridique, est composé de trois parties et présente deux principaux pôles d'intérêt : le premier est lié à la compréhension des implications juridiques de ces entités et le second, plus large, vise à comprendre le traitement qui a été réservé à ces organes dans les différends examinés. Ce traitement peut nous renseigner au niveau systémique sur le droit international des investissements, qui a également nécessité une comparaison ciblée avec l'arbitrage commercial et avec le droit commercial international. The idea of a thesis on state enterprises in international investment law finds its roots in their impressive economic development during the last decade, which, on one hand, gives considerable relevance to this theme given its inherent actuality and, on the other hand, there is a considerable interest in the juridical problems that these entities leave open. The thesis consists of a preliminary chapter, were the legal form of these institutions has been analyzed, from both an empirical assessment and the standpoint of national and international law applicable to these subjects. The empirical, in-depth analysis, not yet reached in the collections of examined contributions, turned up as fundamental, because some of the legal issues concerning state enterprises cannot really be tackled without such an approach. The more juridical body of the thesis, devoted only to legal analysis is composed of three parts and has two main poles of interest: the first linked to the understanding of the legal implications of these entities and a second, and, wider one, aimed at understanding what the treatment of these bodies, occurred in the dispute cases examined, can tell us at a systemic level about international investment law, which has required also a targeted comparison with commercial arbitration and international trade law.
Keywords: Contentieux d'investissement; Contentieux fiscal; Contentieux économique; Economic litigation; Entreprises publiques; Finances publiques; Fond souverain; Investment arbitration; State enterprises

Problématique de la compétence et de la procédure devant la Cour Commune de Justice et d’Arbitrage de l'OHADA : cas de recours dans les litiges commerciaux congolais - Banza Ilunga, Aimé; Mwansa Kalunga, Jean-Pierre (KAS African Law Study Library, 2018)

Exécution des sentences arbitrales étrangères en République Démocratique du Congo - Kangaseke Mbaka, John; Tshizena Tshinate, Céline (KAS African Law Study Library, 2018)

Pour une justice contractuelle efficace : la médiation OHADA - Kenfack, Hugues (La Lettre, 2018)
Pendant longtemps, la médiation a été le parent pauvre de la justice contractuelle dans le monde. Depuis quelques temps, un vent de faveur souffle sur tous les modes alternatifs de règlement des différends (MARD) parmi lesquels la médiation occupe une place importante.
Keywords: Mediation; Mediação

La renonciation ponctuelle à la mise en œuvre d’une clause compromissoire rend-elle cette dernière manifestement inapplicable dans d’autres contentieux ? - Posocco, Laurent (La Lettre, 2018)

Le litige du travail a-t-il une nature réfractaire à l'arbitrage - Posocco, Laurent (La Lettre, 2018)

Les parties à un arbitrage international sont-elles solidairement tenues de la rémunération due aux membres du tribunal arbitral ? - Posocco, Laurent (La Lettre, 2018)

Médiation de la consommation dans le monde francophone - Thomas, Vincent (La lettre des médiations, 2018)
Le litige de consommation est souvent modeste. Il appelle de ce fait une solution rapide à moindre coût. Sauf exception, l'action en justice ne convient ni au consommateur, ni à l'entreprise, nommée « professionnel » par Code de la consommation. En effet, l'action judiciaire est longue, son résultat échappe à la prévisibilité des parties et les frais induits sont sans commune mesure avec les montants en jeu. Le législateur en a conscience. C'est l'une des raisons pour lesquelles il expérimente depuis quelques années des alternatives à la justice ordinaire. Le juge de proximité a ainsi été créé en 2002 pour les litiges inférieurs à 4 000 €, taux de compétence qui a permis de régler bon nombre de contentieux de la consommation. Malgré son utilité, ce juge spécial n'a pas survécu aux critiques du monde judiciaire et a été supprimé en 2017. Parallèlement, les modes amiables – c'est à-dire par l'accord des parties – de résolution des différends se sont développés. Le Code de procédure civile consacre depuis 2012 un titre complet à la médiation et à la conciliation conventionnelles dont dispositions s'appliquent en dehors de toute procédure judiciaire.
Keywords: Consommation; Mediation; Médiation

Defragmenting Investment disputes: Multilateral Court of Investment Disputes as a Panacea? - Kidane, Brook Bekele (Revue juridique des étudiants de la Sorbonne, 2018)
Never was there a time whereby investment dispute settlement came to the forefront of every possible communication outlet, from academia and mainstream news to civil societies and an outright protest of the public. TTIP and CETA brought ISDS to a broad daylight scrutiny in many parts of Europe getting the attention of law and policy makers at EU and national level. The criticisms and anxiety over ISDS relates to divergent interpretation of similar or identical International Investment Agreements (IIAs) provisions that lead to inconsistency and unpredictability of decisions, lack of transparency in investment disputes, lack of independence and impartiality of arbitrators, the elite group of arbitrators, costs, diversions of public money from public goods and services, ‘chilling effect’ on state regulatory powers and bypassing national judicial systems.; With a view to establish and tackle the problem with a meaningful solution to the legitimate concerns and anxieties, the EU, with its competence to conclude the Investment Agreements, attempted to create two mechanisms. The inclusion of Investment Court System (ICS) in newly concluded IIAs and the creation of a multilateral investment court.; This article will assess the three systems together, i.e. the ISDS, ICS, and the multilateral investment court, in terms the pros and cons and attempt to envisage the policy shortcomings or benefits under any of the systems. Jamais il n'y a eu une époque où le règlement des différends en matière d'investissement a été au premier plan de tous les moyens de communication possibles, qu'il s'agisse d'universitaires, de la presse grand public, de la société civile voire d’actions publiques. La TTIP et la CETA ont permis à l'ISDS de faire l'objet d'un examen minutieux dans de nombreuses parties de l'Europe, attirant l'attention des législateurs et des décideurs politiques au niveau européen et national. Les critiques et l'anxiété à l'égard de l'ISDS ont trait à l'interprétation divergente de dispositions similaires ou identiques des accords internationaux d'investissement (AII) qui conduisent à l'incohérence et à l'imprévisibilité des décisions, au manque de transparence dans les différends en matière d'investissement, au manque d'indépendance et d'impartialité des arbitres, à l'élite des arbitres, aux coûts, aux détournements de fonds publics des biens et services publics, à l'"effet paralysant" sur les pouvoirs réglementaires des États et au contournement des systèmes judiciaires nationaux. En vue d'établir et d'aborder le problème avec une solution significative aux préoccupations et aux inquiétudes légitimes, l'UE, avec sa compétence pour conclure les accords d'investissement, a tenté de créer deux mécanismes. L'inclusion de l'Investment Court System (ICS) dans les AII nouvellement conclus et la création d'un tribunal multilatéral de l'investissement. Cet article évaluera les trois systèmes ensemble, c'est-à-dire le SIPDS, le SCI et le tribunal multilatéral de l'investissement en termes d'avantages et d'inconvénients et tentera d'envisager les lacunes ou les avantages de l'un ou l'autre des systèmes.

Political risk in energy-related investment disputes - Sahin, H. (The World Arbitration and Mediation Review (WAMR), 2018)
The energy industry is a key source of growth stimulation for developing states. This is true not only in terms of economic growth, but also in terms of the transfer of knowledge and skills as well as the provision of employment opportunities. Understandably, developing states are well-disposed towards international investors, and are eager to enter into petroleum investment contracts with the expectation that this will bring the aforementioned benefits to their countries particularly where the host state is less able to act as a provider of such resources autonomously. On a global scale, regardless of their type, all investments face risks. These risks are volatile in nature and reach as the world economy globalises. It is, of course, true that political risk phenomena per se are potentially destructive to all industries. However, it is fair to say that due to its high stakes, the energy industry is more acutely exposed and subject to political risk than most sectors. The purpose of this article is to examine political risk, particularly direct expropriation risk, in long-term energy investment projects. This paper will refer to arbitral decisions with regard to expropriation cases, as well as the valuation techniques applied by the investment arbitration tribunals in unlawful expropriation cases.

International Arbitration Practices in Nigeria: A Construction Industry Appraisal - Ewa, O. O.; Haytham, B.; Okon, E. E.; Enang, O. P.; Emiri, D. A. (World Journal of Innovative Research, 2018)
This paper aims to investigate Corporate Alternative Conflict Management and Dispute Resolution compliance through an appraisal of International Arbitration practices in Project-based Organizations in the Nigerian Construction Industry. In this study, simple percentages and frequencies of occurrence were used to analyse data derived through subject matter interviews and a questionnaire survey. Using the Survey Monkey tool, 85 questionnaires were distributed to key players in the AEC (Architecture-Engineering-Construction) Industry including Engineers, Project Managers, Architects and Quantity Surveyors and 53 were returned complete. The survey indicated that 66% preferred a more private Construction Arbitration to a public Litigation as a preferred method of dispute resolution, with 65% agreeing that a lack of proper project funding hinders the arbitration process in the Nigerian Construction Industry. 66% agree that Arbitration Time contributes more to project delays while 32% believe that Cost of the arbitration process is the greater source of project delays. We recommend that issues of confidentiality be carefully managed in dealing with outside counsels, while Project-based Organisations in Nigeria should ensure to develop master plans compatible with long-term strategies, including setting aside adequate funding for the timely resolution of project disputes through the implementation of only Arbitration-friendly contracts. This paper contributes to knowledge by bringing to bear the current compliance levels of project-based organisations in the practice of Arbitration in the Nigerian Construction Industry.

Who is in? Who is out? How the Uncitral Transparency Rules Can Influence the Upcoming Amendments of the ICSID Arbitration Rules - Yu, Hong-Lin (Contemporary Asia Arbitration Journal, 2018)
The International Center for Settlement of Investment Disputes (hereinafter "ICSID") has started its fourth amendment of its Arbitration Rules since 2016. The issue of transparency has been highlighted as a delicate issue in ICSID ongoing current amendment. It is also listed in the topics that have been identified for potential amendment. This article analyses how the issues of access to hearings and confidentiality over information arising from arbitration is treated under the current framework. A comparison is made against the Transparency Rules. The analysis is also made against the comments received from the public whose views are analysed as a possible direction the amendment may take.

L'ineffectivité du droit du travail à l'orée de la réforme OHADA - Bitsamana, Hilarion Alain (Université Côte d'Azur, 2018)
Cette thèse est un condensé de différentes irrégularités ou violations des droits dont sont victimes les travailleurs africains par leurs employeurs, en dépit des diverses législations en matière du travail qui existent dans tous les Etats parties. Au point où ils paraissent vivre une autre exploitation après l’esclavage et le colonialisme, cette fois-ci par leurs propres compatriotes. Ces maux sont constatés à la fois dans les rapports individuels de travail comme dans les rapports collectifs. C’est ainsi que certains salariés sont recrutés à la suite des tests de complaisance, sinon par la corruption, sans un document de travail ; d’autres travaillent pendant des années pour percevoir des salaires de misère, dans des conditions de travail affreuses. Quant aux irrégularités relatives aux rapports collectifs, pour mieux les duper, ces travailleurs sont exclus de la gestion de l’entreprise, ne bénéficiant ni du droit d’expression, ni du droit de participer aux performances de l’entreprise ; encore moins d’une représentation collective exemplaire par les délégués du personnel et les syndicalistes. En cas de litige, ils n’ont pratiquement pas une bonne protection étatique par les inspecteurs du travail et les magistrats. Ainsi pour sortir de cette crise aigüe dans le secteur du travail privé qui fait des ravages depuis plusieurs années après les indépendances, bien qu’il existe une réforme en vue à travers l’OHADA, les autorités nationales et internationales doivent veiller à la bonne application du droit du travail en prenant les mesures qui s’imposent. A défaut, la réforme du droit du travail envisagée par l’OHADA sera elle aussi vouée à l’échec. This thesis is a compendium of various of rights which are currently victims of African workers by their employers despite various legislations in the work that exist in all states parties ; to the point where they appear to live another operation after slavery and colonialism. They live poverty on a daily basis. These evils are recognized both in the individual employment relationship as in public reports. This is how some employees are recruited following tests of complacency, if not corruptly there, without a working document ; others work for years to collect wages, without bonus, without leave, in terrible working conditions. As for collective reporting irregularities, to better trick these workers are excluded from the management company born with the right of expression or of the right to participate in the performance of the company still less than exemplary collective representation by the staff representatives and trade unionists. In case of dispute they have virtually no state protection by labor inspectors and judges. So out of this acute crisis in the sector private work that wreaks havoc for many years after independance, well there is a view through the OHADA reform, national and international authorities to ensure the correct application of the right to work by taking the measures that are necessary. Otherwise the reform of the labour law envisaged by the OHADA of the Right Business is also doomed to failure.
Keywords: Arbitrage; Arbitragem; Arbitration; Droit du travail; Employeur et employé (droit); Irregularities; Irrégularités; Job; Labour law; Organisation pour l'harmonisation en Afrique du droit des affaires; Pays de l'OHADA; Recruitment; Recrutement; Sécurité du travail; Travail

L’arbitrage international dans l'OHADA : évolution vers l’arbitrage des investissements en Afrique - Dalil, Mustapha (Journal of Strategic Affairs, 2018)
En vertu des dispositions de l’article 53 Al. 1 du Traité de création de l’OHADA (l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires) : « Le présent traité est, dès son entrée en vigueur, ouvert à l’adhésion de tout Etat membre de l’Union Africaine et non signataire du traité. Il est également ouvert à l’adhésion de tout autre Etat non membre de l’Union Africaine invité à y adhérer du commun accord de tous les Etats Parties ». Cette action d’harmonisation du droit des affaires, tout en s’inspirant d’autres législations telles que le droit français et la common law, les Etats-membres de l’OHADA ont à leur disposition un arsenal législatif efficace et approprié à leur développement économique communautaire. Ce droit revêt un intérêt particulier pour les entreprises marocaines actives dans l’espace OHADA. Le Maroc, par le renouvellement de son adhésion à l’Union Africaine (UA) et en procédant à une demande d’adhésion à la Communauté Economique des Etats de l’Afrique de l’Ouest (CEDEAO) dont le but est de « promouvoir la coopération et l’intégration dans la perspective d’une Union économique de l’Afrique de l’Ouest », (le Maroc) a réaffirmé sa détermination d’intégrer les espaces économiques africains de référence
Keywords: Arbitrage international; Droit des affaires; Développement économique; Relations internationales; Union africaine; الاتحاد الإفريقي; التحكيم الدولي; التنمية الاقتصادية; العلاقات الدولية; قانون الأعمال

Guide de l'arbitrage de la CCJA-OHADA - Cour Commune de Justice et d'Arbitrage (CCJA) (OHADA, 2018)

Médiation des relations de travail dans le monde francophone - Housty, Françoise (La lettre des médiations, 2018)
La médiation pour déminer les conflits au travail » : c’est ainsi que fut annoncée une grande vague de réforme judiciaire et des institutions du travail en France par les lois Macron dès 2016, afin d’introduire de la « médiation » dans le monde du travail1. L’objectif déclaré est de développer le dialogue au sein de l’entreprise et de prévenir le recours à une justice lente parce que engorgée.
Keywords: Mediation; Médiation; Relation de travail

60 Years of the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards 1958: Are We There Yet in Sub-Saharan Africa? - Okubote, Abayomi (Social Science Research Network, 2018)
Sub-Saharan Africa has, in recent years, been classified as a natural-resource play for foreign investors. These investment potentials have made the region one of the most attractive investment destinations in the world. The region is also diverse, with a mix of different legal systems and legal traditions. While investors are constantly seeking to understand the different legal regimes, international arbitration offers comfort by providing a framework for the enforcement of rights in a neutral forum and on a different platform. According to the World Bank, the ability to enforce an arbitral award is an important factor for investors considering potential markets in which to invest.Given the sixtieth anniversary celebration of the New York Convention (NY Convention), this article examines the enforcement regimes for arbitral awards in sub-Saharan Africa. It considers the momentous developments in the enforcement regimes in the region, due to the implementation of the NY Convention. It examines the proposed amendments to the enforcement provisions in the Nigerian Arbitration Act (Repeal and Re-enactment) Bill 2017, recently passed by the Nigerian Senate. It also examines the important provisions in the revised Uniform Act on the Law of Arbitration and the revised Rules of Arbitration of the Common Court of Justice and Arbitration – both recently adopted by the OHADA Council of Ministers. It attempts a comparison between the enforcement regimes in the OHADA Member States, the NY Convention Member States, and in countries that do not belong to any of the two regimes.A chart of the legal regimes on enforcement of foreign arbitral awards in sub-Saharan Africa is attached as appendix.
Keywords: ACA; Annulment; Arbitral Awards; CCJA; Commercial Arbitration; Convention; Enforcement; Enforcement of Arbitral Awards; Foreign Awards; ICSID Convention; Judiciary; New York Convention; OHADA; Reciprocity; Reservations; Sub-Saharan Africa; Treaty; UAA; UNICTRAL Model law

Guide pour le développement des services de médiation et arbitrage - Centre du Commerce International (ITC, 2018)
Keywords: Centre d'arbitrage; Centre de conciliation; Centre de médiation; Gestion; Management

L’arbitrage comme mode alternatif de règlement des litiges en RDC : cas de l’arbitre du CENACO - Kapinga K. Nkashama, Symphorien (KAS African Law Study Library, 2018)
Cette étude s’intéresse à l’arbitrage comme mode alternatif de règlement des litiges en RDC. L’auteur y analyse les règles juridiques qui s’appliquent à la compétence et à la sai- sine du Tribunal arbitral, au mode de désignation des arbitres qui le composent et à la pro- cédure arbitrale à suivre. Il étudie aussi la sentence arbitrale ainsi que les voies de recours offertes aux parties, avec un coup d’œil particulier sur l’arbitrage organisé par le centre Na- tional d’Arbitrage, de Conciliation et de médiation de la Fédération des Entreprises du Congo et en comparaison avec la procédure usitée devant les juridictions civiles étatiques
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Arbitre; MARD; MARL; RDC

Les efforts de la CNUDCI pour accroitre le niveau de transparence dans l’arbitrage d’investissement - Belhadj, Miriana (Revue de l'ERSUMA, 2018)
Récemment, la Commission des Nations Unies pour le Droit commercial international (CNUDCI) a adopté deux instruments sur la transparence dans l’arbitrage entre investisseurs et États fondé sur des traités. Un Règlement adopté en 2013, prévoit des règles spécifiques pour compléter tout règlement d’arbitrage choisi pour régir un arbitrage conduit sur la base d’un traité d’investissement. Ces règles prévoient notamment, et sous certaines conditions, la publication d’informations et de documents relatifs à l’affaire. Elles permettent aussi que des observations soient présentées par les tiers ou par une partie au traité non partie au litige. Une Convention adoptée en 2014 met en place un mécanisme efficace permettant aux États de prévoir l’application du Règlement sur la transparence à leurs traités d’investissement antérieurs à l’entrée en vigueur du Règlement. À la date de cet article, la Convention compte cinq États parties, dont deux États africains (18 autres États, dont 3 États africains, l’ont signée) et est entrée en vigueur le 18 octobre 2017. Ces efforts de promotion de la transparence dans l’arbitrage d’investissement ont été suivis de discussions au sein de la CNUDCI aboutissant à ce qu’un nouveau groupe de travail au sein de la CNUDCI soit chargé de réfléchir à une possible réforme du système de règlement des différends entre investisseurs et États (RDIE). Dans le cadre de ces réflexions politiques et techniques de haut niveau, la question de la place de la transparence – autre que la transparence procédurale – est récurrente à plusieurs égards et inévitablement au cœur des débats.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; CNUDCI; Investissements; Investments; Transparence; Transparency

Arbitrage commercial international - Besson, Sebastien (Arbitrage, médiation et autres modes pour résoudre les conflits autrement, 2018)

La médiation et l'arbitrage dans l'espace UEMOA : recueil des lois et pratiques - Centre du Commerce International (ITC, 2018)
Keywords: Arbitrage; Arbitration; Mediation; UEMOA

La médiation et l’arbitrage de litiges commerciaux dans l’espace UEMOA - Centre du Commerce International (ITC, 2018)
Keywords: Arbitrage; Arbitration; Mediation; Médiation

Revista PLMJ Arbitragem : Jurisprudência comentada de 2017 - Coimbra Trigo, Ana; Monteiro, António Pedro Pinto; Heidrich Jaques, Betyna; Góis Coelho, Carla; Carrera, Iñaki; Schmid Moura, Joana; Tornada, João; Júdice, José-Miguel; Caldeira, Leonor; Carvalho, Mariana; Gouveia, Mariana França; Ziegler, Pacôme; et al. (PLMJ Advogados, 2018)

An Empirical Study of Dispute Resolution Clauses in International Supply Contracts - Coyle, John F.; Drahozal, Christopher R. (Vanderbilt Journal of Transnational Law, 2018)
International transactions present unique legal risks. When a contract touches several different nations, a party may not know where it will be called upon to defend a lawsuit or, alternatively, which nation’s law will be applied to resolve that dispute. To mitigate these risks, parties will often write dispute resolution provisions into their contracts. Arbitration clauses and forum selection clauses help to reduce uncertainty relating to the forum. Choice-of-law clauses help to reduce uncertainty as to the governing law. Over the past few decades, such provisions have become commonplace in international contracting. And yet there exist vanishingly few empirical studies exploring the use of these provisions in international commercial agreements.

Kroniek Internationale Arbitrage - De Ly, Filip (Tijdschrift voor Arbitrage, 2018)

L’arbitrage comme mode de règlement des différends dans les codes d’investissements des Etats membres de l’UEMOA - Djigle, Doundongue (Revue de Recherches en Economie et en Management Africain, 2018)
Dans le but d’attirer les investissements directs étrangers, les Etats membres de l’UEMOA ont adopté des codes d’investissements destinés à régir les relations entre investisseurs et Etats. Ces codes privilégient l’arbitrage comme mode de règlement des différends. Mais le fondement de cet arbitrage n’est pas le même dans chacun des codes. Certains codes comportent directement dans leur corpus la clause d’arbitrage que l’investisseur peut activer en cas de survenance d’un litige, tandis que d’autres renvoient à des sources extérieures, tel un contrat d’investissement ou un traité bilatéral d’investissement liant l’Etat d’accueil avec l’Etat d’origine de l’investisseur. En outre, dans leur pratique, les Etats de l’UEMOA donnent souvent le choix aux investisseurs entre différentes instances arbitrales. Pourtant, peu de procédures d’arbitrage sont engagées contre ces Etats sur le fondement des codes nationaux d’investissement.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Code des investissements; Etats membres.; Investissements; Investments; Offre d’arbitrage; UEMOA

Arbitration cost : a short comparative view of the schedule of fees of arbitration centers within the OHADA zone - Dogué, Karel Osiris Coffi (Revue de l'ERSUMA, 2018)
Amongst the seventeen OHADA member states there are over fourteen arbitration centers or institutions that handle disputes arising from contractual agreement without going through the courts of the state. The arbitration cost within the various arbitral centers differs from one arbitration center to another. The schedule or method for calculating fees are regulated by the rules of the various arbitration centers or by the OHADA Uniform Act Arbitration Rules pertaining to arbitration fees annexed to the rules of arbitration for the Common Court of Justice and Arbitration and for arbitration centers without arbitration rules. This contribution describes and contrast the various schedule of fees applicable with the arbitration centers under the OHADA zone in particular and also makes a comparative view of the arbitration fees out of the OHADA zone.
Keywords: Arbitragem; Arbitraje; Arbitration; Arbitration cost; Arbitration fee; Arbitration proceedings; Coût de l’arbitrage; Frais d’arbitrage; OHADA Arbitration's Center; Procédure arbitrale

Les MARD (modes alternatifs de résolution des différends) au prisme des droits fondamentaux substantiels - Dumas, Romain (Revue des droits et libertés fondamentaux, 2018)
La loi pour la justice du XXIème siècle a renforcé le recours aux MARD (modes alternatifs de résolution des différends) en incitant, voire en obligeant les parties à les utiliser pour tenter d’aplanir un nombre croissant de différends. Si la prise en compte des droits fondamentaux processuels par les MARD ne fait plus guère de doute, la question se pose néanmoins de savoir quel niveau de garantie ces processus accordent aux droit fondamentaux substantiels des parties qui les mobilisent.
Keywords: Arbitrage; Liberté contractuelle; Liberté d'expression; Médiation; Vie privée

Les fondements de la circulation de la convention d’arbitrage - Faye, Ousmane (Revue de l'ERSUMA, 2018)
« Il n’y a pas de contrat sans consentement des parties ». Tel est formulé le principe sacro-saint du consensualisme contractuel. Toutefois cette règle générale reconnue par tous les systèmes juridiques d’obédience romano-germanique ne finit pas de montrer des réserves. Ces exceptions se retrouvent dans tous les types de contrats même dans ceux qui portent sur le règlement alternatif des litiges. C’est cette dernière situation que traduit la problématique de l’application du contrat d’arbitrage à des tiers non-signataires, encore connu sous le terme de la circulation du contrat d’arbitrage. En principe la théorie de la relativité des conventions impose que l’engagement soit source d’obligations pour son auteur, mais pas pour les tiers auxquels l’acte ne peut ni profiter ni nuire. Malgré cette restriction, la jurisprudence et la doctrine restent largement favorables à la circulation de la convention d’arbitrage. Les fondements avancés pour justifier cet élargissement du contrat d’arbitrage à des tiers non-signataires sont assez divers. Certains sont tirés du droit des obligations notamment de la théorie de la représentation et des groupes de contrat. D’autres ont pour fondement le droit des sociétés, particulièrement la théorie des groupes de sociétés et celle de la levée du voile social ou l’alter ego.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Contrat d'arbitrage; Convention d'arbitrage; Corporate law; Droit des sociétés

La preuve dans la médiation commerciale - Kpako, Valentin V. V. (Revue de l'ERSUMA, 2018)
En considération de ce que la médiation commerciale entendue comme un processus par lequel des personnes physiques ou morales, demandent à un tiers de les aider à parvenir à un règlement amiable d’un différend découlant d’un rapport juridique, contractuel ou autre ou lié à un tel rapport, il est aisé de percevoir qu’il s’agit d’un mode de résolution non judiciaire de litige. A la différence du règlement judiciaire des conflits, la médiation commerciale tend à solutionner les points d’oppositions entre les parties, et à maintenir et soigner leurs relations d’affaires. Elle s’oppose à l’arbitrage qui tranche le litige par une sentence, qui s’impose aux parties, qu’elles la veuillent ou non. Elle ne génère donc pas de perdant, mais les deux parties doivent avoir fait des concessions, et gagner en temps. De ce fait, l’on est tenté d’affirmer que la médiation commerciale pourrait se passer de l’exploitation des moyens de preuve. D’ailleurs, l’Acte uniforme de l’OHADA relatif à la médiation ne fait aucune mention du principe de preuve dans la conduite de la médiation commerciale pas plus que l’ensemble des textes qui organisent la matière. L’on se pose même a question de l’opportunité d’avoir à prouver les faits dans une telle discipline si tant est que toutes les parties en sortent gagnantes. Mais à y voir de près, la médiation commerciale ne semble pas totalement exclure le système de la preuve tel que pratiqué dans la procédure judiciaire de résolution des conflits. Au contraire, elle en a fortement besoin pour à la fois justifier le fondement des prétentions des parties ainsi que la solution au litige. Précisément, la preuve dans la médiation commerciale participe à la détermination des points à discuter et à la justification tant des propositions formulées par le médiateur que des concessions à faire par les parties.
Keywords: Espace OHADA; MARD; Mediation; Médiation; Médiation commerciale; Procédure de médiation

La médiation civile : alternative ou étape du procès ? - Leborgne, Anne (Droit privé, 2018)
Initialement pensé comme une alternative à la solution judiciaire, le recours à la médiation, processus structuré, par lequel deux ou plusieurs parties tentent de parvenir à un accord en vue de la résolution amiable de leurs différends, avec l’aide d’un tiers le médiateur, choisi par elles ou désigné avec leur accord par le juge saisi du litige, apparaît aujourd’hui, dans de nombreux procès de droit privé comme une étape du règlement judiciaire. Il en est ainsi, en droit de la famille, en droit de la consommation, en droit commercial mais également désormais, en droit social. Depuis 2015 en effet, le Code de procédure civile impose aux parties à un litige de justifier, lors de l’introduction de l’instance, des diligences entreprises en vue de parvenir à une résolution amiable de leur litige et le juge est lui-même invité à leur proposer une mesure de conciliation ou de médiation à défaut de justification. Un pas de plus a été franchi avec la loi de modernisation de la justice du 18 novembre 2016, dite « Justice 21 », qui a rendue obligatoire la tentative de conciliation ou de médiation pour les petits litiges du quotidien, avant la saisine du juge d’instance. On pouvait dès lors se demander si ce mode de résolution d’un conflit participait de la justice ou s’il s’en distinguait et comment il était accueilli par les justiciables et les praticiens du droit. C’est à ces questions que le colloque des 28 et 29 avril 2017 a cherché à répondre, à partir de l’examen du droit positif et prospectif français et en utilisant le droit comparé, européen et international. Les résistances comme les initiatives pour promouvoir la médiation ont été examinées lors de la première journée de la manifestation. Le deuxième jour a permis de faire point sur l’actualité de la médiation civile dans les différentes branches du droit privé et de mesurer l’influence des règlements européens et de la jurisprudence de la Cour européenne des droits de l’homme sur le développement de ce processus.
Keywords: Code de procédure civile; Cour européenne des droits del'homme; Droit de la consommation; Droit privé; MARD; Mediación; Mediation; Mediação; Médiateur; Médiation; Médiation familiale; Recours

L'avocat et la médiation - entrez dans la danse ! - Lévy, Cinthia (Arbitrage, médiation et autres modes pour résoudre les conflits autrement, 2018)

L'arbitrage international et la place réservée à l’ordre public dans les pays du golfe persique - Mazidi, Sépideh (Revue de l'ERSUMA, 2018)
La notion de l’ordre public est l’un des concepts les plus complexes des systèmes juridiques. Dans les pays arabo-musulmans la difficulté est encore plus grande, car cette notion se rapproche de celle de la Chari’a. En effet, l’ordre public des pays de la région du golfe trouve sa légitimité dans l’Islam et dans les Constitutions de ces pays. Les Constitutions du Koweït, Bahreïn, Qatar et les Émirats Arabes Unis considèrent la Chari’a comme la source principale de la législation. A l’échelle internationale, la présence indirecte de la Chari’a se manifeste à travers l’arbitrage international, mode efficace et rapide de résolution des conflits du commerce international. Dans la procédure arbitrale, la Chari’a peut intervenir à tous les niveaux : elle peut jouer un rôle fondamental pour la conclusion de la convention d’arbitrage, le choix de la loi applicable ainsi que pour l’exécution et les recours contre la sentence. Dans le cadre de notre étude, nous étudions le choix de la loi applicable et la phase exequatur. Cependant le stade de la conclusion de la convention d’arbitrage est en dehors des limites de ce travail.
Keywords: Arbitrage international; Arbitration; Charia; International arbitration; Islam; Légitimité; Région du golfe

Vers des partenariats inter-états africains, gages d’équité en faveur des investissements économiques en Afrique - Nguemdom, Ruth Carelle (Revue de l'ERSUMA, 2018)
Est-il essentiel de créer de véritables et solides couloirs juridiques entre les régions et les Etats africains pour encourager les investissements économiques ? La question mérite d’être posée. Un tel partenariat implique que soit mise en place une stratégie commune autour des investissements économiques. Il va ainsi permettre de créer une dynamique industrielle et commerciale encore plus forte que celle observée aujourd’hui au sein de l’OHADA. L’UA ou l’OHADA doivent être dotées de moyens réels car l’union fera la force pour les africains trop faibles pour agir et compter seuls face aux puissances étrangères (l’UE, la Chine, l’Inde, la Russie, les USA…). Pour ces Etats, l’Union serait la négociatrice privilégiée pour de nouveaux partenariats plus équitables. Avec cette stratégie de coopération rentable, les Etats africains pourront parler d’une même voix et passer du statut de « perfusés » à celui de « partenaires ». Si ce vœu pieux semble loin de portée, il est malheureusement une des clés de la réussite africaine en matière de développement économique et social, de croissance durable par le biais des investissements économiques. Ceci au même titre que l’intégration régionale car, comme le rappelle si bien la CEA, l’approfondissement de l’intégration régionale permettra d’améliorer de façon significative l’attractivité du continent africain comme destination pour les investissements économiques.
Keywords: Afrique; Coopération Sud-Sud; Investissements; Investments; Partenariat inter-Etats

Vers la contractualisation de la justice : Cas de la médiation en droit OHADA - Ntumba Musuka, Zacharie-Richard (Annales de la Faculté de Droit, 2018)

La justice étatique à l’épreuve de l’avancée des modes alternatifs de règlement des différends en droit OHADA - Soumaïla, Sounon Tamou Abdou (Revue de l'ERSUMA, 2018)
La « raison d’être » de l’OHADA est de faciliter l’activité des entreprises et garantir la sécurité juridique et judiciaire des activités économiques. A cette fin, la justice ou « la juridiction compétente dans l’Etat Partie » selon les termes du législateur de l’OHADA, est d’une grande contribution. Mais, en marge de cette justice, on voit se développer remarquablement les Modes Alternatifs de Règlements des Différends (MARD) en Droit OHADA. Le législateur est parti de l’arbitrage pour en arriver aujourd’hui à la médiation, sans oublier la conciliation. Le souci du législateur est sans doute d’assurer la célérité dans le traitement des conflits, garantie que n’offre pas toujours la justice étatique. Que devient alors le juge étatique au milieu de ces «nouveaux» modes de règlement des différends dans le droit OHADA ? La réponse à cette interrogation est apportée en considération des deux Actes uniformes récemment adoptés (le 23 novembre 2017 à Conakry) par le Conseil des Ministres de l’OHADA sur la Médiation et l’Arbitrage. Dans l’un ou l’autre de ces textes, le juge n’est pas traité de la même manière, conséquence de la nature de chaque procédure. La nature contractuelle de l’accord de médiation s’impose au juge tandis que la sentence arbitrale doit faire l’objet de reconnaissance et d’exequatur. En conséquence, le juge qui semble s’effacer lors du déroulement des procédures d’arbitrage et de médiation, réapparaît à l’occasion de l’exécution des décisions qui en résultent, mais là encore, son intervention est nuancée. Dans l’exécution de la sentence arbitrale elle est obligatoire et exclusive ; dans la mise en œuvre de l’accord de médiation elle est facultative. Au final, l’on peut souhaiter que le législateur fasse interagir les différentes procédures de règlement des différends en droit OHADA.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Conciliation; Droit OHADA; MARD; Mediation; Médiation; Règlement des conflits

Quelle médiation dans l’espace OHADA sans professionnalisation des médiateurs ? Les inspirations du contexte belge - Tadjudje, Willy (Revue de l'ERSUMA, 2018)
Le 23 novembre 2017, le dixième Acte uniforme de l’OHADA sur la médiation a été adopté au cours de la 45e session du Conseil des Ministres tenue à Conakry (Guinée). Selon le communiqué final de ladite session, cet Acte uniforme a pour objectif « de combler le vide législatif existant en la matière dans la plupart des Etats membres de l’OHADA et promouvoir ce procédé amiable de règlement des différends ». Le but de cette réflexion est de jeter un regard critique sur ce texte dans une approche comparative avec le contexte belge. L’analyse sera focalisée sur la question de la professionnalisation des médiateurs. En Belgique, la médiation est une « profession réglementée », alors que dans l’espace OHADA, l’accès à la médiation semble libre, ce qui peut laisser des doutes sur la crédibilité de cet outil de règlement amiable des litiges.
Keywords: Belgique; Espace OHADA; Mediation; Médiateur; Médiation; Médiation et négociation; Procédure de médiation; Professionnalisation

Ex Aequo et Bono as a Response to the ‘Over-Judicialisation’ of International Commercial Arbitration - Teramura, Nobumichi (UNSW Sydney, 2018)
Ex aequo et bono is a long-lived legal concept that enables arbitrators to decide a dispute based on notions of fairness instead of a strict application of legal norms. Jurists generally agree that arbitrators authorised to decide commercial disputes ex aequo et bono can more easily tailor arbitral procedure to achieve an efficient and fair dispute resolution process. They therefore agree that ex aequo et bono arbitration maximises procedural flexibility. However, this flexibility is now perceived more as a negative rather than a positive, despite the potential of ex aequo et bono to mitigate growing concerns about the ‘over-judicialisation’ of arbitration – the increasing formalisation and inefficiency of arbitral procedure. Commentators usually assert that ex aequo et bono introduces excessive unpredictability into arbitration and encourages arbitrators to abuse their discretion. As a result, ex aequo et bono has remained unpopular to this day. This thesis challenges this overly negative conception of ex aequo et bono. It does so particularly under the UNCITRAL Model Law, as an important foundation stone of the global commercial arbitration regime. The thesis investigates significant divergence in the understanding of ex aequo et bono across state jurisdictions and international arbitration institutions. It also analyses the core trends in actual legal practice and in thinking about the principle. The thesis thereby demonstrates that the Model Law requires arbitrators to ensure that their arbitral awards are based on three objective elements: contract terms, trade usages, and mandatory rules of law. Accordingly, while the Model Law allows arbitrators deciding ex aequo et bono to invoke their subjective conceptions of fairness as the ultimate gap-filler when discerning the intention of the parties, the scope for doing so is not unduly expansive. Further, the refinement of various legal theories underpinning international commercial arbitration has enabled parties to determine and challenge more readily the arbitrators’ subjective ideas of fairness. The thesis therefore concludes that the flexibility inherent in ex aequo et bono needs to be both re-evaluated and rejuvenated. It urges the international arbitration community to adopt a revitalised conception of ex aequo et bono to counter-balance the encroaching ‘over-judicialisation’ of arbitration.
Keywords: AI; Amiable composition; Arbitrage; Arbitragem; Arbitration; Arbitration theory; Artificial Intelligence; Blockchain; Cryptocurrency; Ex aequo et bono; Inteligência artificial; Intelligence Artificielle; International commercial arbitration; Trade usages; UNCITRAL Model Law

Médiation et arbitrage dans les services financiers : conseil en placement et gestion de fortune - Thévenoz, Luc (Arbitrage, médiation et autres modes pour résoudre les conflits autrement, 2018)
Dans le contexte actuel d'échange automatique de renseignements en matière fiscale, quelles sont les perspectives de la médiation et de l'arbitrage comme modes de résolution des litiges relatifs aux services financiers - spécialement la gestion de fortune et le conseil en placement - que la place financière suisse offre à sa clientèle privée et institutionnelle suisse et étrangère? Cet article commence par un rapide tour d'horizon international de la situation. Il examine ensuite le développement de la médiation qui résultera de la mise en oeuvre de la loi sur les services financiers et s'achève par quelques réflexions sur l'arbitrage et les actions collectives dans ce domaine.
Keywords: Conseil en placement; Gestion de fortune; Médiation; Services financiers

Without Silence, There Is No Golden Rule; Without Dissent, There Is No Progress - Uluc, Inan; Sutton, Kristi R. (Oregon Review of International Law, 2018)
The frequency of dissenting opinions accompanying arbitration awards in international arbitration has multiplied, particularly in international investment arbitration. Accordingly, dissenting opinions are now inevitable companions to majority awards. Notwithstanding the fact that dissenting opinions neither form part of an arbitral award nor constitute a separate award, the escalation of dissenting opinions spawns anxiety in scholars and practitioners. This trepidation ignited a crusade whereby those opposed to the practice of rendering dissent challenge the role and usefulness of these opinions. In this respect, this Article initially considers and critiques specific arguments raised by those opposed to dissenting opinions in international arbitration. Following analysis of the criticisms, this Article explores the beneficial and constructive aspects of dissenting opinions. Evident from this discussion is that dissenting opinions are not only integral to supplement an arbitrator’s quasi-judicial capacity, but also encourage issuance of well-reasoned awards. Clear from the benefits of dissenting opinions in international arbitration, any departure from the present clemency espoused toward the practice will eventuate in the field’s regression.
Keywords: Civil law; Common law; International arbitration

The Impartiality and Independence of Arbitrators and Its Implication on the Validity of Arbitral Awards - Yoga, I. Ketut Dharma Putra (Juris Gentium Law Review, 2018)
Arbitration is a way to resolve disputes outside the courts as a form of an alternative dispute resolution. The submitted dispute will be decided by one or more arbitrators, who will then render an arbitral award. One of the most fundamental principles of arbitration that must be adhered to by all arbitrators worldwide is the impartiality and independence of arbitrators, which have been regulated in various International laws. Arbitrators are not allowed to communicate with any party related to the case they are hearing. Further, arbitrators should not be influenced by others in making their decision and drafting the arbitral award to ensure objectivity and prevent any bias. An arbitrator's failure to act impartial and independent can lead to the invalidity or annulment of an arbitral award.

O.E.C.D. promotion for arbitration as an additional tool of settling disputes in the field of international taxation - Zeyen, Gaëtan (Revue de l'ERSUMA, 2018)
In a globalized world, arbitration plays an increasing role in settling international disputes. Almost all areas of Law are or might be concerned. Until very recently, [international] taxation was - as a rule - seen as a not ‘arbitrable-friendly’ matter. As the ‘classical’ method of settling international tax disputes - i.e., based on the so-called ‘Mutual Agreement Procedure’ (shortly, ‘M.A.P.’) - has shown its limits (mainly: lack of efficiency and involvement from the taxpayers themselves), arbitration became a subject of study for well-known and established academics and even an appropriate method of settling such international tax issues. As a result, both on international (O.E.C.D.) and European levels, legal initiatives have been taken, in order to promote arbitration as an additional tool of settling disputes in the field of international taxation. The purpose of the present article is, therefore, to describe and scrutinize these [very] recent legal initiatives and raise some potential issues that, at least in the author’s view, need to be addressed. One of these issues concerns the enforcement of such arbitral decisions.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Arbitration proceedings; Dispute settlement; International taxation; O.E.C.D; OCDE

الاطار القانوني للاستثمار العربي في الجزائر - عبد الصدوق, حفيظة (Université d'Oran 2 Mohamed Ben Ahmed, 2018)
للاستثمار العربي في الج ا زئر أهمية خاصة لسببين: أحدهما يتعلق بأهمية الاستثمار في حد ذاته لما يلعبه من دور لا يستهان به في التنمية الاقتصادية للدولة، مؤث ا ر على كل جوانب الحياة في المجتمع بما يوفره من تطور اقتصادي وازدهار واستق ا رر، وثانيهما يرتبط باتخاذه وسيلة لتجسيد التعاون العربي المشترك وتحقيق التكامل المنشود منذ عقود، والذي تأكد عدم تحققه الا بالاعتماد على المدخل الإنتاجي من خلال توظيف رؤوس الأموال العربية في الدول العربية. بدافع هذين العاملين وجذبا لرؤوس الأموال العربية وضعت الج ا زئر اطا ا ر قانونيا ا زخ ا ر بالضمانات والامتيا ا زت بعد تحديد مفهوم الاستثمار العربي، هذا الإطار يتألف من الاحكام الاتفاقية السامية على التشريع الوطني الواردة في الاتفاقيات المبرمة بين الج ا زئر والدول العربية بعد المصادقة عليها، ومن احكام التشريع الوطني الذي يعد آلية قانونية تنفذ بها الدولة است ا رتيجياتها. ت ا زمن ذلك مع تهيئة مناخ الاستثمار بصفة عامة من خلال الإصلاحات التي طالت مختلف التشريعات المتعلقة بإقامة الاعمال اولاستثمار في الج ا زئر. جاءت هذه الد ا رسة لتبين معالم هذا الإطار القانوني، مكوناته ومدى تأثيره في رفع مست وى الاستثمار العربي في الج ا زئر كما ونوعا، ضمن مشاريع التكتل الإقليمي والجهوي او المبادلات الثنائية مع الدول العربية.
Keywords: Accords bilatéraux; Algeria; Arab Nationality; Arbitrage; Arbitration; Bilateral Agreements; Blocage; Blocking; Business Establishment; Compensation; Création d'entreprise; Encouragement; Garanties; Guarantees; Investissements; Investment Protection; Investments; Nationalité arabe; Privileges; Privilèges; Protection des investissements

L’arbitrage des litiges relatifs à la finance islamique - Alyaqout, Yousef (Université de Lorraine, 2017)
L’essor de la finance islamique moderne va poser logiquement la question de la résolution des litiges. En effet, le recours à la justice étatique aboutit à des impacts négatifs sur la réalisation des objectifs de la finance islamique et sur le développement de ce secteur d’activité. Dans cette optique, l’application de la législation nationale par le juge étatique aboutit à la requalification des contrats de financement islamique en des contrats de financement conventionnel. En outre, ce recours au juge étatique conduit à la neutralisation de la Charia en tant que droit applicable. Tout cela conduit à la dénaturation de la finance islamique. Cette dénaturation est une source de contradictions. On sait bien que les institutions financières islamiques reposent sur une obligation fondamentale, selon laquelle toutes les opérations financières effectuées doivent être conformes à la Charia. De plus, les personnes ayant recours à la finance islamique visent principalement à exercer des activités financières en toute conformité avec leurs principes religieux et éthiques issus de la législation islamique. L’étude a également montré que les modes amiables de règlement des litiges contribuent à prendre en considération la particularité de la finance islamique. Cependant, cette prise en compte reste insuffisante. En effet, ces modes ne présentent pas un mécanisme complet, homogène et cohérent de règlement des litiges relatifs à la finance islamique. Leur contribution à la construction d’un système juridique propre à la finance islamique est très limitée. De ce fait, ils ne peuvent pas participer efficacement à la promotion de l’industrie financière islamique. De plus, ils souffrent d’un défaut majeur au niveau de la force de la solution proposée : l’efficacité de cette solution dépend en principe de la bonne volonté des parties. Face à ce dysfonctionnement de la justice étatique et des modes amiables, la solution a été recherchée du côté de l'arbitrage. En effet, l’arbitrage connaît une expansion spectaculaire dans le monde actuel au point de devenir le mode normal de règlement des litiges. Cet essor exceptionnel de l’arbitrage se constate notamment dans la vie économique et financière. A l’heure actuelle, cette vie est devenue inconcevable sans l’arbitrage. En matière de finance islamique, l’arbitrage en tant que mécanisme reposant sur la liberté et la volonté apparaît comme la meilleure voie permettant la prise en considération de la spécificité de cette activité, l’application de la Charia dans le domaine de la résolution des litiges. C’est pourquoi, ce mode alternatif de règlement des litiges s’adapte parfaitement aux exigences des litiges relatifs à la finance islamique et pourrait contribuer à la promotion de ce secteur d’activité. Grâce aux avantages qu’il offre aux opérateurs de la finance islamique, l’arbitrage s’affirme comme la justice naturelle des litiges relatifs à la finance islamique. Pour renforcer le rôle de l’arbitrage dans le domaine de la finance islamique, un projet de réforme a été présenté. Ce projet vise à moderniser l’arbitrage dans toutes ses étapes. Dans cette optique, l’accent a été mis sur la convention d’arbitrage, le statut de l’arbitre, le droit applicable et la sentence arbitrale. Tout cela a été achevé par l’élaboration d’un projet de charte éthique de l’arbitrage en matière de finance islamique. Une fois modernisé et renouvelé, l’arbitrage peut devenir un pilier essentiel de l’industrie financière islamique, en participant efficacement à la promotion de cette activité. Avec une justice équitable, pratique, efficace, conforme à la Charia et adaptée, la finance islamique se trouve renforcée et consolidée
Keywords: Arbitrage; Arbitragem; Arbitration; Droit commercial; Droit financier islamique; Droit procédure; Litiges; Marché financier; Règlement de conflits

Le règlement des litiges survenant des contrats de partenariats public-privé (PPP / PFI) : recherche d’une meilleure gestion des sources des litiges dans les contrats de PPP : enjeux et conséquences pour l’Egypte - Eissa Zakaria Abdelsalam, Nora (Université Lille 2, 2017)
Le partenariat public privé est un instrument pour la réalisation des objectifs du développement en Egypte. Sur le plan international, le recours aux PPP soulève des difficultés compliquées à résoudre. La nature complexe de ce type de projets augmentent la probabilité de litiges entre les parties. L’analyse comparée des expériences britannique et française, permet d’élaborer une référence pour le gouvernement égyptien en matières des réformes juridique et économique. Dans le cadre d’améliorer la gestion des projets de PPP en Egypte, deux approches peuvent être adressées dans notre recherche. En premier lieu, le développement d’une méthodologie de gestion efficace des risques par l’analyse de types des risques attachés aux PPP pendant le cycle de vie du projet. En deuxième lieu, la présentation des mécanismes les plus efficaces de résolution des litiges découlant des projets de PPP. Public-private partnership is an instrument for achieving development objectives in Egypt. On the international level, the use of the PPP model raises complicated challenges and difficulties. The complex nature of such projects increase the probability of disputes between the parties. The comparative analysis of the British and French experience allows the elaboration of a reference for the Egyptian government in the legal and economicreforms. In order to improve the management of PPP projects in Egypt, two approaches can be addressed in our research. First, the development of an effective risk management methodology through the analysis of the types of risk associated with PPP during the life cycle of the project. Second, the presentation of the most effective mechanisms for the resolution of disputes arising from PPP projects.
Keywords: Egypte; Gestion des risques; PFI; PPP; Partenariat public-privé; Pays en développement; Projets d’infrastructures; Étude comparative

La réception par le droit Iranien de la loi type de la CNUDCI sur l’arbitrage commercial international - Pour, Mohammad Mehdi (Université de Lorraine, 2017)
De nos jours, les activités et les relations d'affaires sont beaucoup plus larges et complexes qu'auparavant. L'extension de cet espace, nécessite que les différends relatifs aux affaires commerciales soient réglés dans des systèmes efficaces adaptés à la nature des litiges de ce domaine, c'est-à-dire, rapidement, de manière précise et par des experts. C'est pour quoi, au cours des dernières décennies, les législations des pays relatives à l’arbitrage ont été actualisées, et les conventions internationales dans ce domaine connaissent une large réussite. Les pays recherchant à transformer leur législation sur l’arbitrage commercial disposent d’un modèle législatif apprécié et intéressant fourni par la loi type sur l’arbitrage commercial international ; il a été adopté en 1985 par la CNUDCI et constitue aujourd’hui une référence pour réaliser une unité juridique dans le domaine de l’arbitrage commercial international. Les transformations des régimes juridiques nationaux ont débuté assez tôt dans certains des pays développés tels la France, la Suisse et la Belgique, tandis qu’elles ont été entamées assez tardivement dans d’autres pays, tels ceux en voie de développement dont l’Iran. En Iran, l’arbitrage a toujours été admis et pratiqué ; néanmoins, la procédure civile iranienne présentait encore des insuffisances, et dévoila encore davantage de défauts concernant l’arbitrage international. En conséquence, les parties iraniennes aux contrats internationaux ne pouvaient convaincre les parties étrangères à accepter l’Iran en tant que place d’arbitrage. C’est en accord avec les évolutions législatives mondiales que l’Iran aussi, tout en se joignant à la Convention de New York de 1958, réforma sa législation sur l’arbitrage commercial international, en adoptant en 1997 une loi sur l’arbitrage commercial international rédigée en adoptant le modèle législatif proposé par la CNUDCI. Cette loi marqua une évolution marquante dans la législation iranienne vu qu’elle institua d’importantes règles alignées sur les tendances récentes du droit de l’arbitrage international. Malgré cela, certains praticiens y découvrirent des défauts et des lacunes, réclamant ainsi une réforme nécessaire pour rendre le droit iranien réellement attractif. Néanmoins, la loi iranienne de 1997 n’a jamais fait jusqu’à ce jour l’objet d’une étude scientifique systématique. L’examen des droits d'autres pays tels que : la français, la belge et l'anglais sur l’arbitrage commercial international, ainsi que l’étude d’autres sources pertinentes, permettra d’identifier et d’analyser en profondeur les lacunes et de proposer des remèdes. Nowadays, the business relations are much broader and more complex than before. The extension of this area of activities requires the disputes arising out of business relationships to be resolved through the effective systems aligned with the nature of this area, i.e. the promptness, accuracy and expertise. Hence, over the last few decades, the national laws relating to the arbitration have been developed, and international conventions in this field achieved a great deal of success.The countries seeking to reform their legislation on commercial arbitration can adopt the well-known model law provided by the UNCITRAL Model Law on International Commercial Arbitration which has been adopted in 1985 by UNCITRAL and is now a reference for the realization of a legal system in the field of international commercial arbitration. Changes in national legal regimes began relatively early in some of the developed countries such as France, Switzerland and Belgium, while they were initiated fairly late in other countries, such as developing world, including Iran.In Iran, arbitration has always been admitted and practiced; nevertheless, the civil procedure in Iran was inadequate in this area, and revealed even more defects concerning international arbitration. Consequently, Iranian parties to international contracts could hardly convince their foreign parties to accept Iran as the seat of arbitration.It was in line with global legislative developments that Iran, while joining the 1958 New York Convention, has reformed its legislation on international commercial arbitration by adopting a law on commercial arbitration in 1997 in accordance with the model law proposed by UNCITRAL. This law marked a significant development in Iranian legislation as it established important rules aligned with recent trends in the law of international arbitration. Despite this, the practitioners discovered some defects and shortcomings. That’s why they call for a reform necessary to make Iranian law truly attractive. Nevertheless, the Iranian law of 1997 has never been subject of a comprehensive study so far. Examination of the laws of other countries such as French, Belgian and English on international commercial arbitration, as well as the study of other relevant sources, will pave the way to identify and analyze in depth the gaps and propose remedies.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitraje; Arbitration; Convention de d'arbitrage; Droit commercial; Iran; Loi de l'arbitrage; Loi type de la CNUDCI; UNCITRAL

Contractual renegotiations and International investment arbitration : a relational contract theory interpretation of investment treaties - Florou, Aikaterini (Institut d'études politiques, 2017)
The relationship between international investment treaties and the underlying contracts remains a highly disputed matter in international investment law. This thesis explored the contract-treaty interaction by using the renegotiation of regulatory contracts in the sector of energy infrastructure as a natural experiment, with a particular emphasis on the arbitral disputes that arose from the Argentine crisis. It deployed to this end an original analytical framework drawing from transaction cost economics and relational contract theory. The result of the novel combination of these two analytical frameworks is the construction of an interpretative methodology that takes an integrated approach to the two instruments – the contract and the overarching treaty – in a way that achieves a more sustainable balance between the competing public and private interests. In particular, the thesis rests on three arguments: the first is the relational-contract nature of dynamic treaty standards, which require the long-term cooperation of the parties. The second is the status of these vague standards as default rules complemented by the provisions of the underlying contracts, which are also relational, and act as gap-fillers. The last, normative argument is that the relationship between these (default) treaty rules and the (gap-filling) contractual provisions should be determined by transaction cost economics, and specifically the goal of economizing on the transaction costs of bounded rationality and opportunism when and interpreting relational treaty standards. La relation entre les traites internationaux d’investissement et les contrats sous-jacents reste un sujet très contentieux dans le domaine du droit international de l’investissement. Cette thèse explore l’interaction entre le contrat et le traité en utilisant la renégociation des contrats règlementaires dans le secteur de l’infrastructure énergétique comme un exemple d’ « expérience naturelle », en se focalisant en particulier sur les litiges arbitraux découlant de la crise économique en Argentine. A cette fin, un cadre analytique original, s’inspirant de l’économie des coûts de transaction et la théorie du contrat relationnel. Le résultat de la combinaison originelle de ces deux cadres analytiques est la construction d’une méthodologie interprétative proposant une approche d’intégration entre les deux instruments – le contrat et le traité – d’une manière apportant plus d’équilibre entre les intérêts publics et privés souvent opposés. La thèse est fondée en particulier sur trois arguments : le premier est la nature des standards dynamiques des traités comme contrats relationnels exigeant la coopération des parties à long terme. Le deuxième est le statut de ces standards vagues comme règles par défaut, complémentés par les provisions des contrats sous-jacents, qui sont aussi relationnels et fonctionnent comme « gap fillers ». Le dernier argument, normatif, est que la relation entre ces règles (par défaut) des traites et les provisions contractuels doit être déterminée par l’économie des coûts de transaction, et en particulier le but d’économiser les coûts de transaction découlant de la rationalité limitée et l’opportunisme durant l’interprétation des standards relationnels des traités.
Keywords: Arbitrage commercial international; Contrats internationaux; Economie des coûts de transaction; Interprétation des traités; Relational contract theory; Théorie du contrat relationnel; Transaction cost economics; Treaty interpretation

La pratique de l'arbitrage OHADA selon le règlement d'arbitrage CCJA - Bebohi Ebongo, Sylvie (Revue juridique de l'Océan Indien, 2017)
L’arbitrage OHADA repose sur un régime dual. Le régime dual de l’arbitrage OHADA est constitué, d’une part, par l’arbitrage de droit commun régi par l’acte uniforme OHADA relatif au droit de l’arbitrage qui réglemente l’arbitrage de droit commun dans l’espace OHADA et, d’autre part, par l’arbitrage spécifique CCJA qui repose sur le titre IV du Traité OHADA et le règlement d’arbitrage de la Cour commune de justice et d’arbitrage. Qu’est-ce qui caractérise dès lors l’arbitrage OHADA selon le règlement d’arbitrage CCJA et le distingue de l’arbitrage de droit commun de l’acte uniforme OHADA relatif au droit de l’arbitrage ? Comment fonctionne l’arbitrage selon le règlement d’arbitrage CCJA ? Pour mieux comprendre comment se pratique l’arbitrage OHADA selon le règlement d’arbitrage CCJA, il est nécessaire d’appréhender ses spécificités tant dans sa mise œuvre (I) qu’en matière d’exécution des sentences arbitrales qui en sont issues (II).
Keywords: Arbitrage; Arbitragem; Arbitration; Clause compromissoire; Compromis d'arbitrage; Convention d'arbitrage; Espace OHADA; Exequatur; Exécution; Investissements; Organisation pour l'harmonisation en Afrique du droit des affaires (OHADA); Promotion; Protection; Règlement d'arbitrage; Sentence arbitrale; TBI; Traités Bilatéraux; lois nationales

Le règlement par voie d'arbitrage des litiges relatif aux investissements dans l'espace OHADA - Kenfack Douajni, Gaston (Revue juridique de l'Océan Indien, 2017)
Keywords: Arbitrage; Arbitragem; Arbitration; Clause compromissoire; Commission des Nations Unies pour le droit commercial international (CNUDCI); Contrat; Convention d'arbitrage; Exequatur; Investissements; Investments; Jurisprudence arbitrale; Loi nationale; Organisation pour l'harmonisation en Afrique du droit des affaires (OHADA); Règlement des litiges; Sentence arbitrale; Traité de protection des investissements

Les ambigüités de la voie de cassation en matière de droit pénal des Actes uniformes, (A propos de l'arrêt de la CCJA n°143/2016, du 14 juil. 2016 Ibrahima Aboukhalil c/Etat du Sénégal et le ministère public et a) - Lekebe Omouali, Daphtone (Revue de l'ERSUMA, 2017)
L'interprétation des Actes uniformes est un défi pour son application. L'harmonisation des règles de droit des affaires dans l'espace OHADA s'est accompagné d'un objectif d'unification de la jurisprudence et la Cour Commune de Justice et d'Arbitrage joue à cet égard un rôle essentiel. L'articulation des compétences judiciaires entre la CCJA et les juridictions nationales statuant en cassation offre cependant, en matière pénale des Actes uniformes, l'image d'une option pathologique. Alors que la CCJA proclame la compétence exclusive des cours suprêmes nationales en cas d'application des sanctions pénales, la nécessité d'assurer une répression uniforme en cas de violation du droit uniforme milite en faveur d'un partage de compétence entre celle-ci et celles-là.
Keywords: Droit de l'arbitrage; Droit pénal des affaires

La médiation : une approche constructive à la hauteur des conflits de notre temps : un pont possible entre la justice et la paix dans un monde pluraliste - Graf, Kathrin (Université Paris 2, 2017)
Ce présent travail a pour vocation de fournir une approche multidisciplinaire – historique, socio-politique, économique, et psychologique – pour comprendre l’intérêt général de la gestion constructive de conflit, et en particulier les opportunités liées à la méthode de la médiation. La thèse reflète le chemin parcouru - de la déconstruction à la reconstruction du sujet – débutant par une analyse théorique (les origines, les spécificités, les différences avec d’autres méthodes, les valeurs et principes), passant par une prise en considération des phénomènes individuels et collectifs inhérents au conflit et à sa gestion (les niveaux de conflit, les dimensions de la gestion, les fondements psychologiques individuels, les opportunités d’une démarche intégrative mais aussi les limites et risques liés à la méthode de médiation). Le travail tient également compte de l’évolution personnelle du chercheur, de sa pratique de médiateur, des échanges avec d'autres professionnels ainsi que ses constats de réalisabilité (conseils de mise en pratique, organisation logistique, outils concrets pour les différentes phases, et restitution des étapes clés d’un cas pratique).Mots clés : accompagnement, arbitrage, compréhension mutuelle, confidentialité, consensus, dialoguer, doubler, écoute active, empathie, facilitation de communication, gestion de conflit effective et constructive, impartialité, médiation, méthodes alternatives de règlement de conflit, modération, négociation intégrative, prévention/traitement auto-responsable de futures conflits, résolution créative de problèmes, solutions « pareto optimales », rétablissement de la paix, gestion des processus, rapprochement, réconciliation, science décisionnelle, supervision, zone d’accords possibles This work aims to provide a multidisciplinary approach - historical, socio-political, economic, and psychological - to understand the general interest of constructive conflict management, and in particular the opportunities related to the method of mediation. The thesis reflects the path taken - from deconstruction to reconstruction of the subject - beginning with a theoretical analysis (origins, specificities, differences with other methods, values and principles) and considering the individual and collective phenomena inherent to each conflict and its management (levels of conflict, management dimensions, individual psychological foundations, opportunities of integrative bargaining, but also the limits and risks associated with the method of mediation). The present work also takes into account the personal evolution of the researcher, her practice as a mediator, exchanges with other professionals on this behalf and her personal findings of feasibility (practical advice, logistical organization, concrete tools for the various phases, and the restitution of the key steps of a practical case). Key words : active listening, alternative dispute resolution, arbitrary, communication facilitation, conciliation, confidentiality, consensus, constructive and effective conflict management, creative problem-solving, decision science, dialogue, empathy training, empowerment, Harvard negotiation model, impartiality, integrative bargaining, looping, mediative solutions, moderation, negotiation, “pareto optimal” solutions, peacemaking, process management, reconciliation, reframing, settlements, supervision, therapy, understanding, zone of possible agreements
Keywords: Arbitrage; Arbitrage (droit européen); Arbitragem; Arbitrary; Arbitration; Conciliation; Creative problem-solving; Ecoute active; Gestion de conflit effective et constructive; Gestion des crises; Impartiality; Impartialité; Integrative bargaining; MARD; Mediación; Mediation; Mediative solutions; Mediação; Moderation; Modération; Médiation; Méthodes alternatives de règlement de conflit; Negotiation; Négociations; Pays de l'Union européenne; Peacemaking; Réconciliation; Résolution créative de problèmes; Rétablissement de la paix; Understanding

L’arbitrage en cinq idées reçues - Couturier, Jean-Pascal (La Lettre, 2017)
Les pouvoirs publics n’ont de cesse de vouloir orienter les justiciables (entreprises comme particuliers) vers des modes alternatifs de règlement des différends (MARD). L’arbitrage est le plus ancien d’entre eux ; le grand public l’a (malheureusement) découvert à travers les nombreux rebondissements de l’affaire Bernard TAPIE / CREDIT LYONNAIS.

Regards croisés sur l’arbitrage et sa perception par l’usager - De La Chapelle, Antoine; Heraud, Cindy (La Lettre, 2017)
L’affaire dite « Tapie », résolue par une sentence arbitrale en date du 7 juillet 2008, a placé l’arbitrage sous le feu des projecteurs médiatiques et a fait couler beaucoup d’encre, alimentée par un certain nombre de représentations erronées et de préjugés vis-à-vis de la justice arbitrale. D’aucuns ont ainsi dénoncé une justice arbitraire, au service d’intérêts privés et au fonctionnement opaque, invitant à une défiance généralisée.

La médiation interentreprises dans le monde francophone - Henry, Sophie (La lettre des médiations, 2017)
Concurrence déloyale, inexécution contractuelle, rupture brutale, conflit entre associés… Autant d’exemples de litiges qu’une entreprise peut être amenée à connaître au cours de son existence. La longueur et le coût des procédures, l’aléa et le carcan d’une décision de justice obligent les entreprises à repenser leur politique de gestion des conflits, Leurs contraintes économiques favorisent progressivement les modes amiables de règlement. Elles optent de plus en plus pour la médiation, dans une perspective d’efficacité, d’optimisation des coûts et délais et de maîtrise de leur image. Dans une étude réalisée en 2016 par le CMAP (Centre de Médiation et d’Arbitrage Paris) en partenariat avec Squaremic et Baro Alto, il apparait que 90% des entreprises interrogées ont eu recours à la médiation au moins une fois sur les douze derniers mois et 77% d’entre elles jugent ce mode de résolution efficace.
Keywords: Gestion de conflits; Mediation; Médiation

Les provisions pour arbitrage face à l’impécuniosité d’une partie - Posocco, Laurent (La Lettre, 2017)

Rejet de l’annulation de la sentence rendue par un arbitre ayant divulgué une hypothétique cause de partialité - Posocco, Laurent (La Lettre, 2017)

The Admissibility of Shareholder Claims: Standing, Causes of Action, and Damages - Bottini, Gabriel (University of Cambridge, 2017)
This thesis addresses risks of multiple recovery, prejudice to legitimate interests of third parties, and inadequate consideration of the applicable law in shareholder claims in investment treaty arbitration. It challenges the application by investment tribunals of two basic premises: i) that shareholders are entitled to claim for damages vis-à-vis measures against the company in which they hold shares and ii) that ‘contract claims’ are to be distinguished from ‘treaty claims’. The central argument is that the failure to recognize substantive overlaps between shareholder treaty claims and contract claims risks more than one recovery, potentially prejudices third parties, and can lead to an incomplete application of the applicable law. The foundations of standing and the cause of action in shareholder treaty claims involve two complementary ideas of independence, i.e., independence of shareholder treaty rights vis-à-vis the local company’s contractual/national law rights and independence of treaty claims vis-à-vis contract claims. However, the substance of shareholder treaty claims, defined as the state measure and particularly the losses involved, is often identical to or at least overlaps considerably with related contract/national law claims. Prevailing ideas on shareholder standing and the cause of action in international investment law have provided useful conceptual tools for jurisdictional determinations. Yet they have not allowed tribunals and the literature to fully consider the implications of shareholder indirect claims. The thesis argues, first, that investment tribunals should acknowledge substantive overlaps between contract and treaty claims. Second, shareholder claims may be inadmissible when such overlap exists and there is a risk of double recovery or prejudice to third parties. Third, the substantive coincidence of treaty and contract claims calls for an integrated approach to the applicable law, where proper weight is given not only to IIA provisions but also to general international law and the national law governing the investment.
Keywords: Admissibility; Admissibility and jurisdiction; Applicable law; Arbitrage; Arbitragem; Arbitration; Contract claims; Contract-treaty distinction; Double recovery; Investment arbitration; Investment claims; Investments; Mixed claims commissions; Prejudice to third parties; Shareholder claims; Shareholder standing; Treaty claims

Conflict of treaty-norms in investment arbitration - Atanasova, Dafina (Université de Genève, 2017)
The study analyses the process through which investment arbitral tribunals identify and resolve conflicts between investment standards of protection and norms from other international regimes relevant for the merits of the dispute. It questions the validity behind the current approach that tribunals adopt, under which arguments based on extraneous norms are overwhelmingly unsuccessful and proposes its' transformation in three respects. First, rather than being a mere means of interpretation, as in current practice, a broader pool of international norms must be applied to the substance of investment disputes. Second, the concept of normative conflict must be broadened if one is to address the actual challenges that inter-regime conflicts pose for international law. Third, fleshing out the modalities under which one could use private international law as a source of inspiration in public international law context, the study offers best practices for approaching the types of conflict commonly found in investment disputes.
Keywords: Arbitrage; Arbitrage d'investissements; Arbitragem; Arbitration; Diversification; Droit international; Droit international privé; Fragmentation; International courts and tribunals; International law; Investissements; Investment arbitration; Investments; Private international law

Usages et arbitrage - Sanchez Saëz, Crystelle (Université de Montpellier, 2017)
Alors même, qu’au sein de l’arbitrage, les usages sont omniprésents, un grand nombre d’acteurs ne sont pas conscient de leur existence. Pour autant, ils sont retrouvés tout au long de l’instance arbitrale. En amont de la prise de décision, les usages processuels permettent une règlementation précise et efficace de la procédure arbitrale. Au moment de la prise de décision, le recours aux usages substantiels est un bon moyen de parvenir à la décision la plus adéquate et ainsi mettre un terme au litige. Ils constituent ainsi un outil efficace, mais surtout alternatif aux Droits nationaux. Although, in arbitration, usages are everywhere, many practitioners are not aware of their existence. However, they are involved in every step of the arbitral proceeding. Before the making of the decision, procedural usages enable the organization of a sound and precise regulation of the arbitral proceeding. At the time of the making of the decision, substantial usages ensure to come to the most adequate decision, in order to put an end to the dispute. Hence, they can be a very useful tool, that would be an alternative to national Laws
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration

Dispute resolution in the oil and gas industry: an appraisal of mediation and litigation procedures. - Mohammed, Jamilu Ibn (Journal of private and business law, 2017)
The Oil and Gas Industry Resolution originally recognised negotiation and concede to the alternative dispute resolution rather, their litigation. The paper analysed appraised the different alternative dispute resolution, formulae including mediation the doctrinal method of research which analyses all legal in others as applied. All methods relating to the dispute resolution were analysed from the library and it has formed that mediation which involves the process of resolution dispute weather the involvement of litigating is prefer for being use costly and time consuming. Litigation been so expensive and time wasting is not recommence for oil and Gas Industry.
Keywords: Dispute Resolution; Gas; Industry; Litigation; MARD; Mediación; Mediation; Mediação; Médiation; Oil

فعالية اتفاق التحكيم التجاري الدولي - تعويلت, كريم (جامعة مولود معمري, 2017)
استند الفقه والقضاء على فكرة فعالية اتفاق التحكيم مجال التجارة الدولية، لتبرير الأخذ ببعض القواعد، كاستقلالية هذا الاتفاق ومبدأ "الاختصاص بالاختصاص"، التي كيفت على أنها قواعد مادية ومبادئ راسخة في قانون التحكيم التجاري الدولي. غير أن اللجوء إلى هذه المبادئ في مفهومها الليبرالي الحالي ، الذي وصل إليه خاصة القانون الفرنسي ، يسمح من الناحية العملية بانفلات هذا الاتفاق ليس فقط من حكم القانون الوطني، بل أيضا من إرادة الأطراف، التي جاءت هذه المبادئ لحمايتها، لذا نرى أنه من الأجدر الأخذ بالحلول التي وضعها القانون النموذجي للتحكيم التجاري الدولي، الذي سنته لجنة الأمم المتحدة للقانون التجاري الدولي في سنة 1985. L’efficacité de la convention d’arbitrage en matière de commerce international a été évoquée pour justifier le recours à certaines règles telles que l’autonomie de ladite convention et la « compétence-compétence ». Ces dernières sont qualifiées de règles matérielles et de principes indiscutables du droit de l’arbitrage international. Toutefois, le recours à ces principes dans leur sens actuel permet en pratique, et selon la conception du droit français notamment, de soustraire la convention d’arbitrage non seulement à toute loi étatique, mais aussi à la volonté des parties que ces principes sont sensés préserver. Par conséquent, nous pensons qu’il est préférable de recourir aux solutions consacrées par la loi type sur l’arbitrage commercial international de la CNUDCI de 1985
Keywords: Arbitrage; Arbitrage commercial international; Arbitration; Commerce international; Compétence-compétence; Convention d'arbitrage; اتفاق التحكيم; التجارة الدولية; التحكيم التجاري الدولي; مبدأ الإختصاص بالإختصاص

Le rôle historique et actuel de la francophonie dans le règlement des conflits - Dramé, Omar (Université Toulouse 1 Capitole, 2017)
Cette thèse porte sur le rôle historique et actuel de la Francophonie dans le règlement des conflits. L'objectif est d'étudier la contribution de l'Organisation internationale de la Francophonie dans les processus de résolution des conflits qui secouent l'espace francophone qui est devenu un théâtre de guerre civile et de guerre ethnico-religieuse, affaiblissant le développement économique et social de plusieurs pays, particulièrement ceux d'Afrique francophone. Devenu un acteur incontournable sur la scène internationale, l'Organisation internationale de la Francophonie, regroupant des ayant le français en partage, décide de contribuer activement à la résolution des conflits. Du point de vue méthodologique, cette thèse est basée sur une approche évolutive, centrée sur la particularité de l'approche francophone dans les processus de règlement des conflits en tenant compte de son historique et l'utilise au service de la paix et de la stabilité de ses Etats membres. Dans la première partie, la thèse met l'accent sur l'approche préventive de l'OIF dans les processus de maintien de la paix en exhortant ses Etats membres à promouvoir la culture de la paix et la gouvernance démocratique. Elle met en exergue la politique de prévention de cette organisation, qui repose sur la volonté de promouvoir l'Etat de droit, le respect des droits de l'homme, considérée comme la meilleure stratégie de maintien de la paix. Elle expose la stratégie adoptée la l'Organisation internationale de la Francophonie pour accompagner ses Etats membres dans la promotion de la démocratie, de la paix, de la bonne gouvernance qui sont des leviers importants pour assurer une gouvernance démocratique synonyme de stabilité d'un pays. Ce travail de recherche démontre la spécificité de l'approche francophone dans la résolution des conflits qui repose aussi sur le renforcement des institutions judiciaires visant à assurer la paix, la justice sociale, la sécurité et la lutte contre la corruption. Dans un second temps, la thèse fait porter l'analyse sur le rôle que l'Organisation internationale de la Francophonie joue dans les opérations de rétablissement et de la consolidation de la paix et démontre comment cette organisation est devenue un acteur tant sollicité sur la scène internationale grâce à son influence, à son capacité de mobilisation, ses stratégies de médiation et de facilitation ainsi que sa politique d'accompagnement pour faciliter la justice transitionnelle et favoriser l'effectivité de la justice pénale internationale visant à punir les auteurs de guerre.
Keywords: Francophonie; Maintien de la paix; Organisation internationale de la francophonie; Règlement de conflits

Le recours aux modes alternatifs de règlement des litiges en matière de propriété intellectuelle - Tankeu, Jean (Université de Nantes, 2017)
Compte tenu de la complexité et de la dimension sensible de la gestion des affaires de propriété intellectuelle ainsi que de la diversité des modalités de protection et d’application des droits de propriété intellectuelle dans différents ressorts juridictionnels, les MARL sont aujourd’hui un moyen efficace de régler les litiges de propriété intellectuelle. Cela est particulièrement vrai en ce qui concerne les affaires de propriété intellectuelle qui impliquent des considérations commerciales. En effet, la propriété intellectuelle fait désormais partie intégrante du commerce international et de l’économie mondiale. D’où le développement du contentieux non juridictionnel international de la propriété intellectuelle avec pour fondement la création de plusieurs centre internationaux d’arbitrage et de médiation de droit commun et d’un centre spécialisé en arbitrage et médiation des litiges de propriété intellectuelle : le centre d’arbitrage et de médiation de l’OMPI. Cette montée en puissance des MARL en matière de propriété intellectuelle se justifie par l’émancipation de ces derniers par rapport à l’ordre public qui ne joue plus son rôle limitatif voir perturbateur. Il se voit aujourd'hui cantonné dans un rôle lui permettant d'assurer sa fonction naturelle de défense des intérêts légitimes de l'État, mais sans entraver les activités privées qui s'y conforment. Given the complexity and the sensitive dimension of the management of the Affairs of intellectual property as well as the diversity of methods of protection and enforcement of intellectual property rights in different legal jurisdictions, MARL today are an effective way of resolving disputes of intellectual property. This is especially true with regard to the intellectual property cases that involve commercial considerations. Indeed, intellectual property is more territorial in terms of application. She is now an integral part of international trade and the global economy. Where international no jurisdictional litigation of intellectual property development with based on the creation of several international center of arbitration and mediation of common law and a Center who specializes in arbitration and mediation of intellectual property disputes: WIPO mediation and Arbitration Center. This rise of ADR in intellectual property is justified by the emancipation of these compared to public order which no longer plays its role limiting see disruptive. He is now confined in a role enabling it to ensure its natural function of defence of the legitimate interests of the State, but without impeding private activities that conform.
Keywords: Arbitrage; Arbitragem; Arbitration; Intellectual property; MARD; Propriedade intelectual; Propriété intellectuelle; Règlement de conflits

Desenho de sistemas de disputas : criação de arranjos procedimentais consensuais adequados e contextualizados para gerenciamento e resolução de controvérsias - Faleck, Diego (Universidade de São Paulo, 2017)
A tese aborda a técnica de desenho de sistemas de resolução de disputas, entendida como a organização deliberada e intencional de procedimentos ou mecanismos processuais, que interagem entre si, e, quando aplicáveis, de recursos materiais e humanos, para a construção de sistemas de prevenção, gerenciamento e resolução de disputas. A delimitação do objeto da presente tese se justifica pela lacuna existente na análise convencional, direcionada a apenas um ou outro mecanismo de resolução de disputas, consubstanciados nos métodos formais mais familiares para os operadores do direito: adjudicação por um tribunal estatal, arbitragem, conciliação ou mediação e negociação. A tese argumenta que a utilização de uma nova lente sistêmica poderá ampliar substancialmente, para o operador do direito, a sua capacidade de invenção e implementação de estratégias adequadas à resolução de disputas. Tais lentes compreendem a mudança do enfoque de análise de um mecanismo particular para o reconhecimento de toda a ordem de mecanismos processuais e canais disponíveis às partes em um determinado contexto, como estes funcionam e principalmente como eles interagem - uma análise de sistemas. Sob esta perspectiva, a tese explora um outro importante pressuposto para a construção de arranjos procedimentais: a adequação. O trabalho argumenta que o fator que incrementará as chances da adequação da resposta processual ao contexto será o processo de concepção, construção e implementação do arranjo procedimental, sob a perspectiva sistêmica. O processualista deve estar atento aos passos inexoráveis que a tarefa de desenhar sistemas de resolução de disputas requer ; esses passos serão abordados detalhadamente no trabalho. A tese sustenta que, sem a devida reflexão e ação sobre os temas identificados em cada uma das etapas necessárias para o desenho de um sistema, o trabalho de construção da resposta processual será mais difícil e o risco de inadequação será agravado. The thesis addresses the topic of dispute systems design, regarding the intentional organization of resources and procedures, which interact with each other, to prevent, manage and resolve disputes. The investigation is important due to the gap in the conventional analysis in dealing with dispute resolution, that aims at one or other dispute resolution mechanism, related to the most familiar formal methods used by lawyers and parties: court adjudication, arbitration, conciliation, mediation or negotiation. The thesis argues that a systemic approach could substantially improve the means for invention and implementation of adequate strategies for dispute resolution in the context of the myriad of situations in which this is necessary. Such an approach requires that the focus of attention be shifted from a particular mechanism of dispute resolution to the broad array of available channels and mechanisms in a given context, how they work, and mainly, how they interact with each other and the people involved: a systems level analysis. Under such perspective, the thesis addresses another important aspect of dispute design: the adequacy. The thesis argues that the element that will increase the chances of adequacy of the procedural response to the context is the process of thinking, building and implementing the procedural scheme, under the systemic approach. The designer should be mindful of the inexorable steps that the dispute systems design initiative requires, which are addressed in detail in the work. The thesis demonstrates that, without careful and structured planning and execution regarding the main issues that lay at every necessary step of the dispute design process, the work of building an adequate procedural response may prove difficult and risky
Keywords: ADR; Alternative dispute resolution; Amicable Dispute Resolution; Arbitrage; Arbitragem; Arbitration; Conciliation; Direito processual; Dispute Resolution; Dispute Systems Design; Hybrid Methods; MARD; Mediación; Mediation; Mediação; Mediação e conciliação; Multi-step Clauses; Médiation; Negotiation; Procedural Mechanisms; Procedural Methods and Processes; Resolução de conflitos

Les enjeux de la déjudiciarisation - Cimamonti, Sylvie; Perrier, Jean-Baptiste (Mission de recherche Droit et Justice, 2017)

Dissenting Opinions in International Commercial Arbitrations - Mohanty, Gautam (Central European University, 2017)
A dissenting opinion with reference to International Commercial Arbitrations elementarily denotes the expression of disagreement by an Arbitrator in relation to both the reasoning and the result of the award granted by the majority of the Tribunal. Though still at a nascent stage, the practice of delivering dissenting opinions is one which needs to be duly noted and taken into due consideration because of the incidental and collateral questions that it nurtures. Fundamentally, a dissenting opinion raises concerns related to the effect, the nature and the rectitude of such opinions. One such collateral question is the enforceability of such dissenting opinions and the repercussions that follow in the context of an arbitral award delivered by the majority. In addition to the above raised question, through this thesis the author will also address other questions such as whether the act of delivering a dissenting opinion is an indicator of the increased sense of maturity of arbitrators in international commercial arbitration? Whether the dissenting opinion possesses any precedential value to the arbitration cases arriving prospectively? and How do such opinions contribute to the development of arbitration jurisprudence. Moreover, through this thesis the author will also attempt from a comparative perspective to examine and make an incisive analysis of the governing rules of arbitration across various arbitration regimes such as ICSID, LCIA which already have a wellestablished arbitration jurisprudence.

Le droit non-étatique dans les rapports internationaux privés : contribution à l'étude des fonctions du droit international privé - Heyraud, Yann (Université Paris 1, 2017)
La production de règles d'origine non étatique se développe dans les rapports internationaux privés. L'analyse de ces règles dans les activités commerciale et sportive construit progressivement une définition unifiée de la notion de droit non-étatique : ensemble des règles écrites et unilatéralement élaborées par des acteurs privés et/ou publics, ayant vocation à s'appliquer eu égard à l'activité considérée, indépendamment des frontières étatiques. Cette proposition est mise à l'épreuve des diverses interactions entretenues par le droit non-étatique, visant à en expliquer le fonctionnement. L'arbitrage atteste sa réception, la fréquence de son application, voire sa promotion, jusqu'à l'exclusion de législations nationales impératives. L'ordre juridique français, par principe, refuse la réception de ce droit, hormis action exceptionnelle des juges, du législateur ou d'organes auxquels il est reconnu compétence. À un niveau supra-étatique, la Cour de justice contrôle directement les règles non-étatiques susceptibles d'entraver les libertés garanties par l'Union européenne, dont la libre circulation des travailleurs. La Cour européenne des droits de l'homme a la possibilité de contrôler indirectement les règles non-étatiques transposées par des États, en raison d'atteintes potentielles aux libertés individuelles, dans le cadre de la lutte contre le dopage par exemple. Le droit international privé, par ailleurs, contribue à rendre compte de l'application du droit non-étatique, en renforce l'efficacité, et participe, potentiellement et à titre prospectif, de la résolution de conflits de normes produits par des règles non-étatiques. The production of non-state norms is growing in private international relations. The analysis of these norms in commercial and sporting activities is progressively building a unified definition of the notion of non-state norms: set of rules written and unilaterally drawn up by private and/or public actors, has intended to be applied with regard to the activity concerned, regardless of State borders. This proposal is put to the test of the various interactions maintained by non-state norms, in order to explain how these norms work. Arbitration attests to its receipt, the frequency of its application and even its promotion, up to the exclusion of imperative national rules. The French legal system, as a matter of principle, refuses to accept these non-state norms. Exceptionally, this principle is contradicted by the action of judges, legislators or bodies whose competence is recognized by the French legal system. At a -supra-state level, the Court of Justice directly controls non-state norms which may hamper the freedoms guaranteed by the European Union, including the free movement of workers. The European Court of Human Rights has the possibility of indirectly controlling non-state norms transposed by States, due to potential breach of individual freedoms, for example in the fight against doping. Moreover, Private International Law helps to explain the application of non-state norms, enhances their efficiency, and potentially and prospectively participates in the resolution of conflicts of norms produced by nonstate norms.
Keywords: Arbitrage; Arbitrage international; Arbitragem; Arbitration; Conflicts of norms; Conflit de normes; Droit international privé; Droit non-étatique; Lex mercatoria; Lex sportiva; New Law Merchant; Non-State Law; Private International Law; Private Regulation; Régulation privée; Transnational

Arbitrage et éthique : causes du mal, évolution récente et pistes d’amélioration – Regards sur le monde et sur l’océan Indien - Anilha, Fernande; Magamootoo, Julien (Revue juridique de l'Océan Indien, 2017)

Suggestions pour promouvoir la place de l’arbitrage en Afrique. Madagascar et la Tunisie comme illustration - Ben Hamida, Walid (Revue juridique de l'Océan Indien, 2017)

Alternative Dispute Resolution (ADR) and access to justice: An introduction - Betancourt, J. (Arbitration, 2017)
Text of a talk given by the author at the University of West London on 8 March 2016 on the topic of Alternative Dispute Resolution, its relation to the concept of access to justice and the idea of practising law in the interest of justice.

Juge judiciaire, acteur de l'essor de l'arbitrage : cas français, malgache et mauricien - Chuk Hen Su, Lalaina (Revue juridique de l'Océan Indien, 2017)

The Application of CISG in International Arbitration - Cisár, Ivan (FIRST BRNO ARBITRATION CONFERENCE 2017, 2017)
International arbitration allows great flexibility of the parties to structure their whole relationship. One of the key factors is the choice of the law applicable to the substance of the relationship. CISG is intended for the regulation of such relations between international businessmen. This paper builds on the empirical evidence of the International Arbitration Surveys conducted among various groups of practitioners on their reasoning con cerning choice of law applicable to the substance of the relationship and argues that although CISG is not chosen by them frequently (or arguably not chosen at all), this “omission” is not warranted.
Keywords: CHOICE OF APPLICABLE LAW; CISG; INTERNATIONAL ARBITRATION

Disqualification Decisions under the ICSID Convention and Arbitration Rules - Cleis, Maria Nicole (The Independence and Impartiality of ICSID Arbitrators, 2017)
This Chapter aims to distill a consistent approach to arbitrators’ independence and impartiality from past decisions on disqualification requests. In a first part, the interpretation of the manifest lack requirement provided for in Article 57 icsid Convention is scrutinized. The definition of this threshold (i.e. the burden of proof imposed on the challenging party) is crucial, because it determines the effectiveness of the right to an independent and impartial decision-maker. The second part of the Chapter inquires how specific categories of alleged conflict are dealt with. It seeks to derive consistency and predictability from the outcome or reasoning of disqualification

The Independence and Impartiality of ICSID Arbitrators: Current Case Law, Alternative Approaches, and Improvement Suggestions - Cleis, Maria Nicole (Nijhoff International Investment Law Series, 2017)
In The Independence and Impartiality of ICSID Arbitrators, Maria Nicole Cleis examines the standard of independence required under the ICSID Convention, as evidenced in existing disqualification decisions, and makes novel suggestions for reforms to ensure unbiased decision-making. Readership: All interested in International Investment Law and investor-State arbitration in particular. Readership includes academics, lawyers and arbitrators involved in investment-related disputes (including in-house counsel), treaty negotiators and NGOs.
Keywords: Arbitrage; Arbitragem; Arbitration; Civil procedure; International Arbitration; International disputes; International law

Guide du secrétariat de la CNUDCI sur la Convention pour la reconnaissance et l’exécution des sentences arbitrales étrangères (New York, 1958) - Commission des Nations Unies pour le Droit Commercial International (Nations Unies, 2017)

First Brno Arbitration Conference 2017: Current Issues of International Commercial Arbitration (Publications of the Masaryk University, theoretical series, editions Scientia, 2017)
Content research papers : - The Application of CISG in International Arbitration; - CISG and Arbitration in the Hungarian Legal Practice; - Time Limits in Arbitration Agreements : What Can We Expect, if We Fail to Meet Them? - Interpretation Hardships Regarding the CISG, in Particular Article 7; - Awarding Punitive Damages in Czech Arbitration Proceedings; - Award of Legal Costs in Arbitration with Focus on Regulation in the Slovak Republic; - Advantage or a Disadvantage? The Costs of Arbitration Court Proceedings in Hungary.

La déontologie de l’arbitre - Dupeyré, Romain (Revue juridique de l'Océan Indien, 2017)

Analyse comparative entre Maurice et Madagascar sur les spécificités liées à l’arbitrage international et à l’arbitrage institutionnel - Gunnoo, Dipna (Revue juridique de l'Océan Indien, 2017)
Les lois mauricienne et malgache relatives à l’arbitrage international s’inspirent toutes deux de la Loi type de la CNUDCI. En dépit de cette source d’inspiration commune, ces deux pays présentent plusieurs aspects divergents. Ces divergences, liées à l’arbitrage international, se retrouvent, non seulement, au sein des caractéristiques législatives et juridictionnelles de chacun de ces États, mais également au sein des caractéristiques des institutions arbitrales promues par ces deux pays. International arbitration laws in Mauritius and Madagascar are both largely inspired by the UNCITRAL Model Law. Despite this similar source of law, these countries have various differing aspects. In the field of international arbitration, discrepancies between these two States can be found, on one hand, in the legislative and jurisdictional features and, on the other hand, in the features of arbitration institutions showcased by these two countries.

Repenser la procédure civile : les enjeux théoriques de l'accès à la justice et l'hypothèse de la régulation sociale par l'intégration des modes extrajudiciaires de prévention et de règlement des différends (PRD) - Hountohotegbè, Sèdjro Axel-Luc (Université Laval, 2017)
La thèse analyse en théorie du droit l’évolution de la procédure civile sous l’angle des enjeux de l’accès à la justice. Elle formule l’hypothèse d’un modèle de régulation sociale qui opère un renversement de la perspective moniste positiviste classique par l’intégration des modes extrajudiciaires de PRD. La thèse répond à la question de recherche suivante : Quels fondements théoriques à l’évolution de la procédure civile pour l’amélioration de l’accès à la justice ? D’un point de vue méthodologique, la thèse opte pour une démarche théorique et documentaire. Elle emprunte aux principales Écoles de théories du droit, en particulier à l’École sociologique. Le cadre théorique s’appuie alors sur les théories du pluralisme juridique, des systèmes et du réseau. Ces théories irriguent la thèse tout entière et servent de grille analytique aux deux parties principales de celle-ci. Dans la première partie, la thèse délimite et précise le concept d’accès à la justice. En trois chapitres, cette première partie s’attèle méthodiquement à déconstruire les acceptions dominantes institutionnelles et restrictives du concept. Elle aboutit à l’élaboration d’une définition innovante à valeur théorique et pratique de l’accès à la justice. Dans la seconde partie, l’analyse porte sur l’évolution des paradigmes de la procédure civile. En trois chapitres, elle pose une critique du système dominant de règlement des conflits en général et de la procédure civile en particulier qui reposent sur le droit selon les principes de hiérarchie des normes. La thèse déconstruit cette vision, puis propose une théorie générale supportant la légitimité des modes extrajudiciaires de PRD. Finalement, la recherche suggère une évolution de la procédure civile et soumet à cet effet un modèle de système de justice alternatif intégrant les modes extrajudiciaires de PRD. Le modèle de régulation proposé est non antinomique et complémentaire au modèle dominant. Le modèle de régulation sociale construit dans la thèse s’articule autour de trois paradigmes fondamentaux à savoir la décentralisation, la multipolarité et la complémentarité. La thèse constitue un compendium d’analyses et soumet un cadre de référence des paradigmes de base d’un système de justice renouvelé pour l’amélioration de l’accès à la justice.
Keywords: Accès à la justice; Arbitrage; Arbitragem; Arbitration; MARD; Mediación; Mediation; Mediação; Médiation; Procédure civile; Règlement de conflits

Arbitrage et sécurisation juridique des investissements : l'arbitrage comme moyen de sécurisation des investissements à Madagascar - Jakoba, Raphaël (Revue juridique de l'Océan Indien, 2017)
Madagascar s’est doté d’un arsenal juridique cohérent et attractif relatif aux investissements. La panoplie de mesures est étoffée allant d’une loi spécifique sur les investissements (loi 2007-036 sur les investissements à Madagascar), à un cadre institutionnel tel que l’EDBM, et enfin des engagements internationaux (adhésion à la convention de Washington de 1965, ratification de plusieurs APPI (Accords pour la promotion et la protection réciproques des investissements) avec la France, le Benelux... À la lumière de cet arsenal en faveur des investissements, il est permis de dire que l’arbitrage, mode de règlement des différends pour les investissements, est placé au cœur d’une politique d’attraction et de sécurisation des investissements. Toutefois, la pratique malgache de l’arbitrage international tant commercial qu’en investissement révèle un certain nombre de dysfonctionnements et de défaillances qui impactent sur l’environnement des affaires. Madagascar has developed a coherent and attractive legal arsenal for investment. The range of measures was refined ranging from a specific investment law (Law 2007-036 on investments in Madagascar) to an institutional framework such as the EDBM, and international commitments (accession to the Washington convention of 1965, Ratification of several APPI [Agreements for the Promotion and reciprocal Protection of Investments] with France, the Benelux...). In the light of this arsenal in favor of investments, it can be said that arbitration, the method of settlement of Investment Disputes, is at the center of a policy of attracting and securing investments. However, the malagasy practice of international arbitration, either for commercial or investment arbitration reveals a number of dysfunctions and failures, impacting significantly the investment climate.

Alternative Dispute Resolution in Oil and Gas Contracts Law: An Analysis - Kareem, Kareem Kawa (Near East University, 2017)
The industry of oil and gas is not peculiar to question anymore, inferable from the global condition as well as its various dimensions. While trying to complete an agreement procedure, it would barely be clear to expect the thing that could happen in the emergence of a debate. Hazard moving and fragmented contracting lie at the heart of the organization relationship innate in the obtainment and financing of extensive scale undertakings, such as power plants, oil and gas pipelines, and condensed natural gas facilities. An examination of gas bonds gives exact proof of the hazard moving results of legally binding inadequacy. This thesis is a basic examination of the discipline we call the law of oil and gas. A number of the imperfections connected with this "specific" status. Jurisprudential with its "uncommon" status. Jurisprudential imperfections have created as courts leave from essential contract, property, or tort law in quest for natural resources ideas. The marvel isn’t restricted to natural resources law but instead can occur in any "law of" setting. This article delineates the issues connected with oil and gas law by dissecting legal ways to deal with perceiving and applying "inferred agreements" under the oil and gas rent. By contrasting the experience and results under the oil and gas lead to the result under an agreement law investigation, it is conceivable to assess whether a specific "oil and gas" govern is vital or prudent. In the past quarter-century, huge changes have happened in the ways legal advisors approach strife. There have been uncommon endeavors to create systems went for more proficient, not so much expensive, but rather more fulfilling determination of contention, including more broad and suitable utilization of intercession and other " alternative dispute resolution " (ADR) approaches. This review analyzes what is known and not considered about the development and effect of ADR in government and state courts, in the business division, and in work and shopper settings. The investigation inspects the relationship amongst ADR and court trial, additionally underlines the more extensive employments of and method of reasoning for intercession and different process decisions. This study concentrates on the oil and gas contract with question by ADR.

Le règlement par voie d'arbitrage des litiges relatifs aux investissements dans l'espace OHADA - Kenfack Douajni, Gaston (Revue juridique de l'Océan Indien, 2017)

Réflexion sur la notion et le régime de la médiation au sein des modes amiables de résolution des différends : à partir des expériences de médiation dans les ressorts des Cours d’appel d’Aquitaine (Agen/Bordeaux/Pau), de Paris et de Lyon - Larribau-Terneyre, Virginie; Lecourt, Arnaud; Brus, Florence; Alvarez Elorza, Alexis; Drouiller, Camille; Sane, Claude MIchel (Mission de recherche Droit et Justice, 2017)

International Arbitration - Liatowitsch, Manuel; Rosenthal, Jeffrey; Forneret, Martine; Scherker, Emily; Ashford, Peter; Janzik, Sabrina; Weldon, Matthew; Houston, Robert; Boog, Christopher; Gottlieb, Benjamin; Meijer, Gerard; Verberne, Valerie; et al. (The Year in Review, 2017)
Keywords: Arbitration; Dispute resolution; International Law

L'arbitrage et la lutte contre la corruption - Ligneul, Nicolas (Revue juridique de l'Océan Indien, 2017)

Primera ejecución en España de un laudo OHADA ¿Por qué tiene un juez español que forzar su cumplimiento? - Linares Rodríguez, Enrique (Arbitraje: revista de arbitraje comercial y de inversiones, 2017)
El Convenio de Nueva York de 1958 permite se busque el reconocimiento y la ejecución de un laudo OHADA en terceros Estados. Sin embargo, admite el empleo de la normativa interna para regir el procedimiento y deja a salvo cuestiones relacionadas con la inmunidad soberana de los Estados. Las nuevas leyes adoptadas en España en materia de cooperación jurídica internacional e inmunidad soberana, establecen la intervención del MAEC cuando un Estado extranjero sea demandado ante tribunales españoles como es el caso Commercial Bank / Guinea Ecuatorial. Esta previsión puede implicar un giro de la jurisprudencia hacia posturas más cercanas a la inmunidad absoluta. Como se verá en este artículo, aunque CBGE haya obtenido el execuátur del laudo en España y logrado el embargo del avión titularidad de Ceiba, las medidas coercitivas de ejecución podrán ser recurridas en revisión por el Estado, quien podrá plantear una estrategia fundamentalmente en dos direcciones: (i) bien demostrando la finalidad soberana del aparato embargado, para defender así su carácter inmune a la ejecución, o (ii) bien alegando que la persona jurídica afectada por el embargo no ha sido parte en el arbitraje y por tanto no es la deudora del laudo. La práctica jurisprudencial internacional ha demostrado que existen gran des posibilidades de que el tribunal termine levantando el embargo si se demuestra fehacientemente alguna de estas dos defensas.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Ejecución; Embargo; Guinea Ecuatorial; Inmunidad; Laudo arbitral

The notion of award in international commercial arbitration-lessons from French and English law - Marchisio, Giacomo (McGill University, 2017)
For the past twenty years, international commercial arbitration scholarship has mainly focusedon the private dimension of international arbitration. Part of a greater movement toward the privatization of justice and law, this understanding of the discipline has obscured arbitrators'adjudicative role. By reflecting on different adjudicative models and by analyzing the form andcontent of arbitral decisions, new light can be shed on our understanding of international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Award; Commercial Arbitration; English law; French law; International Arbitration; International commercial arbitration

L'arbitrage de droit commun régi par l'Acte uniforme relatif à l'arbitrage - Ngwe, Marie-Andrée (Revue juridique de l'Océan Indien, 2017)
L’arbitrage de droit commun est régi par l’Acte uniforme relatif à l’arbitrage, véritable loi de procédure harmonisée applicable dans les 17 États membres de l’OHADA. Aux côtés de l’arbitrage CCJA dont il est complémentaire, il a sa légitimité et sa vocation propre qui est de permettre le développement d’un arbitrage de proximité. Conforme aux standards internationaux, qu’il soit ad hoc ou institutionnel, il met au cœur du processus les parties, afin de créer une véritable culture locale de l’arbitrage. À ce titre, il donne un rôle essentiel aux institutions nationales d’arbitrage dont la connaissance de terrain et la proximité des acteurs permettent l’enrichissement de la lex arbitri, jusqu’à permettre aujourd’hui d’inspirer une réforme de cette loi uniforme de l’arbitrage OHADA qui tend vers toujours plus d’efficacité et de modernité. Il nous sera donné en particulier de faire part de l’expérience du Centre d’arbitrage du GICAM, Douala (Cameroun). The Uniform Act on arbitration is the ordinary law that governs arbitration. This Uniform Act is a harmonized procedural enactment that is applicable in the 17 member states of OHADA. It exists alongside, and is complementary to CCJA arbitration. But it has its own legitimacy and its own vocation, which is to allow the development of an arbitration of proximity. Whether considered from an ad hoc arbitration viewpoint, or an institutional arbitration viewpoint, the Uniform Act complies with international arbitration standards. It places the parties at the heart of the arbitral procedure in order to create a local culture of arbitration. In this regard, it provides an important role to national arbitration institutions whose understanding of the field and proximity to stakeholders permit the enrichment of the lex arbitri. Today, this role given to national arbitration institutions has inspired a reform of the Uniform Act on arbitration, which aspires for more efficiency and modernity. We shall, in particular, share the experience of the GICAM Arbitration Centre in Douala Cameroon.

Document Production and Disclosure in Investor-State Arbitration - Oepangat, Dioputra Ilham; Janet, Janet (Juris Gentium Law Review, 2017)
It is not uncommon for states to engage in arbitration proceedings with their investors (“Investor-State Arbitration” or “International Investment Arbitration”) administered under the International Centre for the Settlement of Investment Disputes. When these parties engage in document production during evidentiary proceedings, there arises an issue with regards to documents requested by the investor, which is considered as a “state secret” by the state. Based on the IBA Rules on the Taking of Evidence in International Arbitration (“IBA Rules”), states may have particular interest to refuse the production of a document. This is based on the argument that a document may be exempted from production if the document qualifies as a state secret by virtue of Article 9 of the IBA Rules. This paper will discuss appropriate measures to be taken by tribunals in order to allow for material and relevant evidence to be produced during proceedings, which may be crucial in being able to prove the case of the investor in the case of a conflict pertaining to the production of documents containing state secrets.
Keywords: Arbitrage; Arbitragem; Arbitration; Disclose; Document; IBA; ICSID; International; Investments; Prove; Secrets; Sensitive

La Charte confiance du Centre d’arbitrage et de médiation de Madagascar (CAMM) - Ramangaharivony, Gérard (Revue juridique de l'Océan Indien, 2017)
Les litiges font partie intégrante du monde des affaires. Les gérer efficacement constitue un défi majeur pour le maintien de la paix sociale et l’accroissement du business. Dans sa mission de sensibilisation aux Marl, le Centre d’arbitrage et de médiation de Madagascar (CAMM) a élaboré et proposé une Charte confiance de règlement des litiges. Cette Charte a pour objectif la continuité des affaires, le respect de la loi et un marché sain et prospère.

L'Etat dans l'arbitrage d'investissement - Ranjeva, Hery Frédéric (Revue juridique de l'Océan Indien, 2017)

Règlement alternatif des litiges commerciaux et économiques dans la zone francophone - Ravaloson, Johary (Revue juridique de l'Océan Indien, 2017)

Can third party funding deliver justice in international commercial arbitration? - Yu, Hong-Lin (International Arbitration Law Review, 2017)
Third party funding arrives at international commercial arbitration without clear guidelines. The recognition and acceptance of its legality is hampered by the omissions of all stakeholders' rights involved in international commercial arbitration. In balancing the funder’s contractual rights to gather information under the third party funding agreement and stakeholders' rights to know, the current research examined how non-disclosure of the third party funding agreement would prevent the arbitrators from fulfilling procedural justice required for the integrity of arbitration on their part and impede the opposing party’s right to know during the proceedings. The research highlights the issues from the delivery of procedural and substantive justice as well as suggesting legal and jurisprudential grounds in third party funding governance. It also points out that all issues examined will ultimately contribute to the failure in delivering justice in international commercial arbitration if third party funding is left to self-governance.
Keywords: Arbitration; International commercial arbitration; Third Party Funding

Composantes multidimentionnelles de l’arbitrage : de la considération locale à l’interculturalité internationale - Wehbe, Fatima Sara (Normandie Université, 2016)
La mondialisation a permis l’instauration de plusieurs institutions d’arbitrage. Cette multitude de choix offerte aux investisseurs pourrait induire les parties à choisir une institution défavorable quant à la résolution de leur litige. L’objectif de la thèse est de présenter un modèle de gestion pour les juristes qui facilite le choix de la juridiction la plus efficace ceci avec la mise en œuvre d’un tableau de notation associant des critères multidimensionnels accordant une notation selon le degré d’importance vue par les parties. A ce sujet, le tableau mis en place regroupe les quatre juridictions les plus connues internationalement qui sont les juridictions étatiques, la CCI, le CIRDI et la CNUDCI. L’arbitrage est composé de plusieurs fondements qui lui accordent sa spécificité. L’analyse multidimensionnelle permettrait donc de faire une analyse arithmétique des valeurs comparatives des composantes juridiques et extra-juridiques de l’arbitrage qui forment le tableau de notation afin de faciliter la prise de décisions des investisseurs. Afin de vérifier l’efficacité du tableau de notation, un questionnaire a été adressé aux investisseurs ainsi que des interviews effectuées avec des juristes ont permis de déceler l’impact de l’expérience sur le choix du centre le plus efficace. L’étude de cas de l’affaire COMMISIMPEX est un exemple de l’effet du choix inefficace sur la résolution du litige et explique comment l’expérience pourrait affecter la décision de l’institution d’arbitrage le plus efficace à la résolution du litige. Pour en conclure qu’il n’y a pas de juridiction intrinsèquement meilleure que les autres. Il faut donc procéder au cas par cas et selon ce que les parties recherchent suite à leur litige, pour en déduire la juridiction ou l’institution qui leur serait la plus favorable afin de leurs garantir le plus de droits lors de la résolution de leur litige. Globalization has established several arbitral institutions. They offer a multiple of choices to the investors that could induce the parties to choose an unfavorable institution.The aim of this thesis is to present a management model for jurist which facilitates the choice of the most efficient jurisdiction in resolving their dispute, with the implementation of a scoring table combining multidimensional criteria, giving a rating according to the degree of importance for the parties. In this regard, the table regroup four of the most well-known internationally jurisdiction, the State court, the ICC, the ICSID and the UNICITRAL. Arbitration is composed of several fundaments that give it its specificity. Multidimensional analysis thus would make an arithmetical analysis of the comparative values of the legal and extra-legal components of arbitration which form the scoring table to facilitate decision making of investors. To verify the effectiveness of the scoring table a questionnaire was sent to investors as well as an interview conducted with lawyers have identifies the impact of the experience on the choice of the most efficient arbitral center. The Case study of COMMISIMPEX is an example of the effect of inefficient choice on the resolution of the dispute and how the experience may affect the decision of the most effective arbitration institution to the resolution of the dispute. To conclude none of the jurisdiction is inherently better than the others. We must proceed case by case and according to what the parties are looking after their dispute, to deduce the court or institution that would be most favorable to them by guarantying more rights in the settlement of their dispute.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitration; Interculturality; Interculturalité; International commercial arbitration; Pluralisme juridique; Règlement de conflits

L’arbitrage institutionnel OHADA : Instrument émergent de sécurisation juridique et judiciaire des activités économiques - Diakité, Moussa (Université Toulouse 1 Capitole, 2016)
Devant le ralentissement des investissements en Afrique, il s’est avéré incontournable de reconstruire un ensemble juridique moderne adapté à l’exigence de protection des activités économiques. Les Présidents des pays, essentiellement de la zone franc, ont ainsi signé le 17 octobre 1993 le Traité relatif à l’harmonisation du droit des affaires en Afrique visant à garantir la sécurité juridique et judiciaire. Le droit issu de ce traité a donné naissance à divers Actes uniformes dont l’Acte uniforme relatif à l’arbitrage. L’objectif de notre étude a été d’analyser, principalement à partir de ce texte et sa pratique, dans quelle mesure les opérateurs économiques bénéficient, par l’arbitrage, d’une meilleure garantie d’encadrement de leurs activités. Si l’arbitrage apparait comme étant un instrument pertinent en termes de protection des investissements, c’est qu’il allie deux exigences fondamentales : la liberté ainsi que la sécurité. En effet, la liberté des parties et des arbitres est au fondement de la procédure arbitrale, garantissant aux opérateurs économiques l’assurance d’une justice plus adaptée aux exigences internationales. L’arbitrage doit également offrir une sécurité juridique dans la résolution des conflits permettant de sauvegarder les intérêts des parties tout en assurant l’efficacité de la sentence arbitrale.
Keywords: Arbitrage; Arbitrage OHADA; Arbitrage commercial international; Arbitragem; Arbitration; Investissements; Organisation pour l'harmonisation en Afrique du droit des affaires; Pays de l'OHADA; Sécurité juridique

Réflexion sur l’arbitrage dans l’espace OHADA - Diallo, Abdou (Université de Perpignan, 2016)
L’arbitrage est la motivation première de la création de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) pour lutter contre l’insécurité juridique et promouvoir son développement. Cet arbitrage s’inspire des règles matérielles de l’arbitrage international qui accorde une importance particulière à la volonté des parties.L’arbitrage dans l’espace OHADA est régi par le Traité, un acte uniforme et le règlement d’arbitrage de la Cour Commune de Justice et d’Arbitrage(C.C.J.A).Le droit de l’arbitrage a certes amélioré le cadre normatif surtout dans les pays qui n’en disposaient pas, mais au bout de plus d’une décennie d’existence, cet arbitrage est confronté à de nombreuses difficultés d’application. Ces difficultés proviennent de ces acteurs (parties, arbitres et juge national).Ainsi, notre réflexion vise à analyser les difficultés d’application à partir du contentieux arbitral et à proposer des mesures susceptibles d’améliorer le droit et la pratique de l’arbitrage.
Keywords: Afrique; Arbitrage; Arbitrage commercial international; Arbitragem; Arbitration; CCJA; Common Court of Justice and Arbitration; Cour Commune de Justice et d'Arbitrage; Exéquatur; Ohada; Organisation pour l'harmonisation en Afrique du droit des affaires

The UNCITRAL Model Law on International Commercial Arbitration: Interpretation, General Principles and Arbitrability - Viscasillas, Pilar Perales (Journal of Law, Society and Development, 2016)
This article explores the possible modification of the UNCITRAL Model Law on International Commercial Arbitration (MAL) to include the topic of arbitrability. This is an area in which the domestic legal systems differ, particularly in relation to the arbitrability of intra-corporate disputes. The article also deals with new art 2A, introduced into the Model Law in 2006, which deals with the interpretation and gap-filling system under the Model Law. The interpretation of MAL in accordance with its international character is a very important step towards uniformity and therefore the different tools required for a uniform interpretation are analysed. These include case law and scholarly writings; the meaning and importance of achieving both a uniform and an international interpretation of MAL are also considered. The article also analyses the whole text of MAL in order to arrive at the general principles on which the Model Law is based; when problems have to be solved, these principles should guide issues of interpretation that arise under this law.
Keywords: Arbitrability; Arbitration; General principles; Interpretation; UNCITRAL

Arbitrability and public policy: an African perspective. - Mante, Joseph (Arbitration international, 2016)
Growth in international trade has led to considerable expansion of the scope of matters capable of settlement by arbitration. In spite of sustained scholarly activity on arbitrability, the question of what is arbitrable remains controversial but relevant in many regions of the world, including Africa. Arbitrability has the potential to affect the validity of an arbitration agreement, strip an arbitrator of jurisdiction, or derail enforcement of an award. Given the significance of the concept, it is vital that entities involved in international transactions do not speciously extrapolate knowledge of what pertains in Europe and America across all jurisdictions and regions of the world. This study draws a comparison between arbitrability and its relationship with public policy in Europe and America on one hand, and the trend in Africa in an attempt to critically investigate the extent to which African states are willing to extend the scope of arbitrable subject matters. A number of trends on arbitrability are discernible. Most commercial disputes are arbitrable and this observation generally aligns with practice in Europe and America. Beyond this, there are three significant differences in the areas of scope of subject matter, approaches to arbitrability regulation and the role of public policy.
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Policy

Rethinking the Role of Courts and Judges in Supporting Arbitration in Africa - Onyema, Emilia (Rethinking the Role of Courts and Judges in Supporting Arbitration in Africa, 2016)
This second conference in the SOAS Arbitration in Africa Conference series examined how African judges can better support the growth of arbitration. The conference was hosted by the The Lagos Court of Arbitration in their premises in Lagos, Nigeria from 22-24 June 2016. This conference booklet contains some of the papers and slides, and photographs from the conference.
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Courts; Judges; Rôle; Support

Towards a suitable domestic arbitration process in Nigeria - Bamgbose, Ademola Jonathan (University of Warwick, 2016)
The Nigerian judicial system is currently in a state of distress. Not only has the judiciary been trailed by allegations of corruption, incompetence and god-fatherism amongst others, the wheels of justice in Nigeria are slowly grinding to a near halt. This is because of the large and growing case list of courts as well as the recurrent industrial strike actions embarked upon by court staff. As a solution to this crisis, stakeholders have put forward a number of suggestions, one of which is the use of alternative dispute resolution methods like domestic arbitration, as a solution to the problems of the judiciary and as a viable alternative to the court system. As we will however come to see in this thesis, Nigeria’s Arbitration and Conciliation Act 1988 (“Arbitration Act”), which is based on the UNCITRAL Model Law 1985, is not only outdated, it is also for many reasons not suitable and relevant to a developing country as Nigeria. For example, the existing Arbitration Act fails to take the legal and social idiosyncrasies of the Nigerian nation into consideration. Furthermore, the Act fails to incorporate the pre-existing and judicially recognized customary arbitration practice into the Act. In addition, the Nigerian Arbitration framework contains a number of anti-arbitration provisions, which have clearly inhibited the growth of domestic arbitration in Nigeria. Moreover, between 1988 and now, a number of beneficial changes have occurred within the sphere of arbitration and from which the Nigerian arbitration framework can draw lessons. All these among others, make the Nigerian Arbitration Act an unsuitable alternative to the court system in Nigeria. This thesis therefore recommends a bespoke domestic arbitration framework, which takes account of the legal and social idiosyncrasies of the Nigerian nation as well as recent but relevant domestic arbitration practices in similar jurisdictions as Nigeria. Among other recommendations, the proposed framework borrows a leaf from the deeply rooted and judicially recognised customary arbitration practice in Nigeria. Furthermore, in a bid to identify and incorporate relevant provisions and practices that have emerged within the sphere of domestic arbitration between 1988 and now, we undertake a comparative analysis of the Ghanaian Alternative Dispute Resolution Act 2010, the UNCITRAL Model Law 2006, the English Arbitration Act 1996 as well as the Uniform Act on Arbitration 1999 of OHADA. It is believed that this modern but tailored framework will encourage the use of domestic arbitration in Nigeria and by extension ameliorate the problems in the judicial system.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration (Administrative law); Ghana; Nigeria

L'intervention du juge dans la procédure arbitrale - Najib, Mohamed El Mehdi (Université de Bordeaux, 2016)
L'arbitre est un juge privé, il tranche, il juge, et il détient la balance de la justice, pourtant sesdécisions ne seront exécutoires que si le juge étatique compétent le décide. Ainsi soumise aucontrôle du juge, la sentence arbitrale s'intègre dans l'ordre juridictionnel. Elle doit doncrespecter l'ordre public et, plus généralement, les principes directeurs du procès. Certes, c’estune sentence oeuvre de justice et, au même titre que les décisions des tribunaux étatiques,bénéficie de l'autorité de la chose jugée.Les textes légaux et les règles qui gouvernent la procédure arbitrale ont une très grandeimportance tant pour les parties, que pour les arbitres. Ce sont en effet ces règles, et lapossibilité de les choisir, qui participent à la spécificité de l’arbitrage.La présente thèse identifie et analyse les diverses facettes de l'intervention du juge dans laprocédure d'arbitrage. S'il s'avère d'un précieux appui à l'arbitrage, le juge est aussi chargéd'en vérifier la régularité et d'en assurer l'efficacité.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration proceeding; Judge; Juges; Procédure arbitrale

A mediação incidental como meio de solução dos conflitos trabalhistas individuais: a questão da dispensa de trabalhadores detentores da garantia provisória no emprego - Santos, Ricardo Goretti; Leite, Carlos Henrique Bezerra (Espaço Jurídico Journal of Law, 2016)
Resumo: Este artigo versa sobre a prática da mediação incidental no processo do trabalho e sua potencial contribuição para a efetiva solução de conflitos decorrentes da dispensa de trabalhadores dotados de garantia provisória do emprego. Acusa o uso desordenado da conciliação incidental, indiscriminadamente aplicada na solução de conflitos individuais situados no âmbito de relações trabalhistas, tanto circunstanciais quanto continuadas. Busca responder ao seguinte problema de pesquisa: a prática da mediação judicial incidental na Justiça do Trabalho pode contribuir para a efetiva solução de conflitos decorrentes da dispensa do trabalhador dotado de garantia provisória do emprego? Estabelece as bases do fenômeno da difusão dos métodos alternativos de solução de conflitos, no contexto do movimento universal de acesso à justiça. Desenvolve considerações sobre particularidades da conciliação e da mediação, destacando os aspectos principais de distinção entre elas. Finalmente, avalia a aplicação dos métodos autocompositivos, considerando as particularidades das controvérsias decorrentes da dispensa de trabalhadores dotados de garantia provisória no emprego. Conclui que, por objetivar a exploração aprofundada dos interesses em jogo, o fortalecimento do diálogo e da relação entre as partes, além do empoderamento dos envolvidos, a mediação judicial incidental seria a via mais adequada para a administração de conflitos decorrentes da dispensa de trabalhadores com garantia provisória do emprego. Além isso, evidencia uma proposição legislativa sobre o tema, já submetida à apreciação da Comissão de Juristas responsável pela elaboração do Anteprojeto de Lei de Arbitragem e Mediação, do Senado Federal.
Keywords: Arbitrage (droit du travail); Arbitragem; Arbitration; Conciliation (droit du travail); Conciliação trabalhista; Despedida arbitrária; Garantia no emprego; Labour dispute; Mediation; Mediação trabalhista; Médiation; Resolução alternativa de conflitos

L’arbitrage en droit espagnol des sociétés, à l’aune du droit comparé - Correa Delcasso, Jean-Paul (La Lettre, 2016)
Dans la présente étude, l’auteur expose l’évolution qu’a connue la pratique de l’arbitrage en droit espagnol depuis ses débuts. Il analyse, d’un point de vue pratique, les principales solutions dégagées par la jurisprudence espagnole, en ce qui concerne l’arbitrabilité d’un grand éventail de litiges, question qui s’est traditionnellement posée en droit espagnol. Il compare la situation avec celle d’autres systèmes juridiques européens culturellement proches.

Admission de la question préjudicielle posée par le juge de l’annulation de la sentence - Posocco, Laurent (La Lettre, 2016)
Le juge de l’annulation de la sentence arbitrale internationale a la faculté de demander à la Cour de justice de l’Union européenne (CJUE) de statuer sur une question d’interprétation du Traité sur le fonctionnement de l’Union Européenne (TFUE) en vertu de son art. 267.

Bonne foi de l’avocat dans la mise en œuvre de la clause compromissoire - Posocco, Laurent (La Lettre, 2016)
Ayant fait ressortir que les parties avaient eu la volonté de se soumettre à l’arbitrage, l’exigence de bonne foi pouvait leur être opposée et que les pouvoirs du cabinet d’avocats émirati étant apparents, la croyance de la société d’avocats londonienne mandatée à l’engagement des parties était légitime, la cour d’appel en a exactement déduit que le tribunal arbitral était compétent.

La responsabilité de l’arbitre et son assurance - Raibaut, Jacques (La Lettre, 2016)
La figure de l’arbitre, comme celle du juge, paraît étrangère à la responsabilité tant domine l’image de la fonction recherchée par le justiciable : dénouer le conflit qui les oppose. Au-delà de la déception que peut susciter la décision rendue chacun admet que l’indépendance, l’impartialité et la compétence sont inhérents à cette fonction et justifient que l’arbitre bénéficie d’une immunité juridictionnelle de principe qui le met à l’abri du ressentiment d’une ou des parties.

La responsabilité des centres d'arbitrage - Elatafy, Sherif (Université Jean Moulin Lyon 3, 2016)
Les litigants sollicitent les centres d’arbitrage pour diriger l’arbitrage dans toutes ses phases afin de donner une garantie supplémentaire qui assure la validité de la sentence arbitrale. Compte tenu du rôle important que les centres d’arbitrage jouent pendant l’instance arbitrale, les litigants mécontents de la sentence arbitrale ou du jugement annulant la sentence tentent d’engager la responsabilité du centre d’arbitrage dès lors qu’il a surveillé, dirigé et participé au rendu de la sentence.De plus en plus la responsabilité des centres d’arbitrage est mise en cause devant les juridictions étatiques différentes, les fonctions et les pouvoirs exercés par les centres d’arbitrage ainsi que le régime de responsabilité leur est applicable font l’objet d’une attention critique de la part de la doctrine dans plusieurs systèmes juridiques. On s’interroge sur l’origine des rapports qui lient les centres d’arbitrage aux autres acteurs de l’arbitrage, sur les obligations et les pouvoirs conférés aux centres d’arbitrage, et sur les fonctions exercées par les centres d’arbitrage pour établir enfin un régime de responsabilité homogène et pertinent à l’égard des fonctions exercées par les centres d’arbitrage qui a une vocation à s’appliquer dans la majorité des systèmes juridiques. Parties to arbitration seek arbitral institutions to administrate their arbitration in order to have an extra guarantee that ensures the validity of the arbitral award. Given the role that arbitral institutions play during the arbitral procedure, parties unsatisfied either by the arbitral award or the annulment of the award tend to claim the liability of arbitral institution for the awards it had supervised, administered and participated in.The more the allegations of liability raise against the arbitral institutions before courts, the more the issue of arbitral institutions’ functions, powers and liability becomes controversial in different jurisdictions. Therefore, the present study tends to clarify the origin of the relationship existing between arbitral institutions and other parties involved in the arbitration at issue, the duties and powers assigned to the arbitral institutions and the functions performed by the arbitral intuitions, which helps eventually in establishing a kind of liability that complies with the functions performed by the arbitral institutions and can be applied in many jurisdictions.
Keywords: Acte juridictionnel; Administrative functions; Agreement to administrate an arbitration; Approbation; Arbitrage; Arbitrage commercial international; Arbitrage institutionnel; Arbitragem; Arbitral Awards; Arbitral institutions; Arbitration; Business contract; Centre d’arbitrage; Challenging arbitrator; Civil liability; Clause exclusive de responsabilité; Condition excluding liability; Consensual protection; Contrat de direction d’arbitrage; Contrat d’entreprise; Décision institutionnelle; Examen prima facie; Faute intentionnelle; Faute lourde; Fonctions administratives; Fonctions juridictionnelles; Forum; Gross negligence; Immunity; Immunité; Institutional arbitration; Institutional decision; Judicial conduct; Judicial functions; Prima facie examination; Protection conventionnelle; Responsabilité civile; Récusation d’arbitre; Sentence arbitrale; Willful misconduct

An Introduction and an Evaluation of Arbitration in Ivory Coast - Kalle, Aurélie (Recht in Afrika, 2016)
The paper deals with arbitration law in Ivory Coast and is mainly based on interviews with the most important authorities in this field. After a short introduction into the OHADA legal system the two main arbitration centres of Ivory Coast are presented. First, the paper treats the internationally known OHADA arbitration centre of the Common Court of Justice and Arbitration, hereinafter known as CCJA. It explains the bodies and the organisation of the CCJA, the arbitration procedure in detail, the enforcement of the arbitral award, the interim measures and the legal remedies against decisions of the CCJA. Second, the functioning of the Court of Arbitration of Côte d'Ivoire, hereinafter known as CACI, is explained. It is the second arbitration centre of Ivory Coast and it was created by the Ivorian Chamber of Industry and Commerce and settles mainly disputes between nationals. The analysis treats the same topics as mentioned for the CCJA centre, but is restricted to point out the differences or peculiarities of the CACI procedure, in order to prevent repetitions. Third, the paper analyses the advantages and disadvantages of the two arbitration centres and compares them to the proceedings of the Commercial Court of Abidjan. It avoids the comparison of yet well-known arguments such as confidentiality of arbitration proceedings or the parties' free choice in regard to the place of arbitration and the language, etc. The work rather limits itself to concretely address the problems or the advantages of each dispute solution considering the latest developments in the judicial system. The purpose of the report is to give a practical introduction into the Ivorian arbitration law, in particular to foreign lawyers. It should provide them with solid theoretical knowledge of the different dispute solutions. With the help of concrete comparisons and explanations of the actual situation regarding the civil and commercial judicial system it should enable them to find the most suitable dispute solution for their clients.
Keywords: Arbitrage; Arbitragem; Arbitration; Côte d'Ivoire; Ivory Coast

La sentence arbitrale et le juge étatique : approche comparative des systèmes français et iranien - Danay Elmi, Manijeh (Université Paris 1, 2016)
En France et en Iran, le droit de l’arbitrage est le fruit d’une longue maturation historique. L’arbitrage en Iran plonge ses racines dans l’Antiquité. En raison de la culture du règlement pacifique des différends qui dominait alors, l’arbitrage s’est imposé comme le mode privilégié des règlements des différends. Dans le domaine de l’arbitrage commercial international, l’Iran s’est inspiré de la loi-type de la CNUDCI de 1997. Ce pays a également adhéré en 2001 à la Convention de New York. Le point de convergence entre les deux ordres juridiques français et iranien : ils ont cherché à instaurer des règles plus favorables pour la reconnaissance et l’exécution des sentences arbitrales, chacun ayant adopté une démarche différente. La première partie de cette étude est consacrée à la réception de la sentence arbitrale dans les deux systèmes. Seule la sentence définitive peut faire l’objet du contrôle et de l’exécution. Plus concrètement, la qualification en sentence internationale ou étrangère déterminera les règles applicables à la reconnaissance et l’exécution de celle-ci. La sentence arbitrale identifiée et reconnue est susceptible d'être contrôlée par le juge qui déterminera le sort de la sentence. La deuxième partie de notre analyse décrit ce contrôle qui peut être direct à l’occasion du recours en annulation ou indirect lors de la demande de reconnaissance et d’exécution. Ce mécanisme conduit in fine à protéger les droits de la partie gagnante et à empêcher l’abus, par la partie condamnée, des voies de recours. In France and Iran, the law of arbitration is the result of a long historical development. Arbitration in Iran finds its roots in the Antiquity. Because of a culture favoring the pacific settlement of disputes, which was prevailing at that period, arbitration imposed itself as the privileged mode in resolving disputes. In the field of international commercial arbitration, Iranian legal system has been inspired by the UNCITRAL Model Law in the promulgation of its LICA in 1997. This country has also adhered to the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards in 2001. The converging point between the Iranian and French legal systems is the following: they have tried to establish the rules favoring the recognition and enforcement of arbitral awards, any of them adopting a different approach. The First Part of this study is allocated to the reception of the arbitral award in the two legal systems. Solely the final award could be subject to control and enforcement. More concretely, the qualification of the arbitral award as international or foreign award will determine the applicable rules in the matters of recognition and enforcement. The arbitral award, identified and recognized, could possibly be controlled by the judge who will determine its fate. The Second Part of our analysis describes the said control that could be direct, on the occasion of the action for setting aside the award, or indirect, when requesting the recognition and enforcement of the award. This mechanism will lead in fine to protecting the winning party’s rights and avoiding any abuse of the means of recourse by the losing party.
Keywords: Arbitrage; Arbitrage (droit); Arbitrage commercial international; Arbitration; Arbitre; Droit comparé; Droit international; France; International commercial arbitration; Iran; Iranian legal system; Ordre public droit iranien; Reconnaissance et éxécution de sentence; Sentence arbitrale

Contrariétés entre jugements étatiques et sentences arbitrales dans l'espace OHADA - Castellane, Béatrice (Penant : revue trimestrielle de droit africain, 2016)

La cláusula med-arb en la actualidad: mediación y arbitraje vinculados - Cuéllar Tijerina, Ervey Sergio (Universitat Pompeu Fabra, 2016)
La intención de esta investigación, es realizar un breve análisis de las ventajas y desventajas que representa, la inclusión en los contratos comerciales, de una cláusula contractual que prevea la resolución de los posibles conflictos que pudiera suscitarse entre las partes, con la interpretación o el cumplimiento del contrato, a través de un ADR, que vincule en un solo proceso a la mediación y al arbitraje (Cláusula Med-Arb). Lo anterior, se pretende verificar a la luz de las disposiciones emitidas por los principales organismos en el comercio internacional, y su perspectiva de aplicación en el Derecho Español.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Derecho civil; MARD; Mediación; Mediation; Mediação; Médiation

Enforceability of Arbitral Awards Containing Interest: A Comparative Study between Sharia Law and Positive Laws - Althabity, Mohammad M. (University of Stirling, 2016)
The dynamics of our globalised world open the way for international trade and transactions between different countries; this may lead to conflicts in laws where transactions and trade may be subject to different legal systems. One of the biggest issues in international commercial law is disputes over the charging of interest, for example with regard to late payment, interest-based loans, or compensation for damages. Interest disputes are considered to be a complex area of law and even more complex in the international field. At the international level, interest claims may be connected to many areas of commerce and thus governed by various laws, which are different from one country to another; moreover, each country has its own interest rate and such rates are changeable according to the nature of law and economics under some jurisdictions. Furthermore, the concept of interest itself is affected by influences such as religious beliefs and economic, political and cultural trends. Interest can be treated as a substantive or a procedural matter. The settlement of these disputes therefore faces difficulties. Arbitration, as a method for settlement of disputes, is characterised by special features that assist in resolving these issues; but it faces some obstructions, especially in international commercial arbitration. The practices of arbitral tribunals and national courts in this regard are different. The results of different interpretations, approaches, and theories with regard to arbitration, at the pre-arbitration, during arbitration and post-arbitration stages, may also differ widely due to the diversity of financial and legal systems such as Common Law, Civil Law and the Islamic legal system – Sharia Law – across different countries. Each legal system has a different methodology and theories, even within an individual country under one legal system, and a state within a federal system has its own laws, which may have different interpretations in this respect. The New York Convention of 1958 on enforcing foreign arbitral awards was established in favour of arbitral awards and for the purpose of unifying international rules of arbitration. This Convention provides some procedural and substantive rules for the enforcement of foreign arbitral awards, but also provides some grounds for refusal. These rules have been affected by different interpretations under different jurisdictions and legal systems, which lead to different perspectives on the matter of charging interest and settlement by arbitration. The outcome of applying the NYC under these interpretations often has the opposite of its intended effect: the rejection of foreign arbitral awards. Due to such ambiguities, courts occasionally intervene in arbitration in all its stages. The interventions of national courts occur in three stages: enforcement of the arbitration agreement, enforcement of the contract under the applicable law to the agreement, and enforcement of the foreign arbitral award. The confusion between substantive and procedural laws also creates confusion with respect to public policy, non-arbitrability and enforceability. In addition, there may be a lack of clarity on the scope of arbitration with respect to the parties’ agreement, whether or not the parties have agreed to the interest rates and periods and whether or not they have agreed to the authority of the arbitrator. These issues affect the enforceability of an arbitration agreement, the law applicable to the disputed contract, the freedom of parties, the authority of the arbitrators and the enforceability of the awarded interest. The thesis studies how arbitral awards containing interest have been interpreted across the three aforementioned legal systems under the NYC 1958 in Saudi Arabia, Egypt, the UAE, England, France, and the US and the enforceability of such awards.
Keywords: Arbitrage; Arbitral award enforcement; Arbitration; Chari'a law; Sentence arbitrale; Sharia Law

LLCs and the Private Ordering of Dispute Resolution - Molk, Peter; Winship, Verity (The Journal of Corporation Law, 2016)
An emerging question in U.S. business law is how the organizational documents of a business entity set the rules for resolving internal disputes. This practice is routine in commercial contracts, which may specify where or how disputes must be resolved. Recent use of litigation provisions in corporation charters and bylaws have sparked controversy, ultimately leading to legislative action to preserve shareholder suits from contractual waiver. Yet despite accounting for the majority of business organizations and sharing features with corporations, non-corporate business entities and their internal dispute resolution process have been largely ignored. How do these non-corporate entities set ex ante rules for resolving disputes among their constituents? This paper begins to map this uncharted area with an empirical study of the practice of limited liability companies (LLCs). We find widespread use of contract to alter the default dispute resolution practices. This study helps not only to inform the evolving statutory and judicial framework for LLC regulation, but also to predict how corporations may respond in the future to recent judicial and legislative changes.
Keywords: Arbitration; Dispute resolution; Fee shifting; Forum; LLCs; Litigation; Operating agreements

State interference through domestic courts in international commercial arbitration - Badenhorst, Casper Hendrik Jacobus (University of Johannesburg, 2016)
Keywords: Arbitrage; Arbitragem; Arbitration; International and municipal law; International commercial arbitration

Direct actions and arbitration: all at sea - Briggs, Adrian (Lloyd's Maritime and Commercial Law Quarterly, 2016)

L'arbitrage commercial international par rapport à la juridiction étatique en matière de mesures provisoires et conservatoires : étude analytique et comparative - Emara, Fehr Abdelazim (Université Laval, 2016)
Depuis le milieu du XXe siècle, l'arbitrage commercial international a connu un développement phénoménal et acquis une importance significative dans le monde des transactions commerciales internationales. Il est effectivement devenu la juridiction mondiale la plus acceptable, la plus fiable et la plus usuelle pour résoudre les différends relatifs au commerce et aux investissements internationaux. Toutefois, il a rencontré des difficultés en ce qui concerne les mesures provisoires et conservatoires ce qui explique la tendance des parties à éviter d’y avoir recours devant les arbitres, au profit des juridictions étatiques pour obtenir les mesures d’urgence dont ils avaient immédiatement besoin. L’inexistence d’un régime procédural capable de bien régir cette matière était la raison principale qui a réduit l’efficacité de l’arbitrage. Pourtant, ce fait a changé grâce aux modifications majeures qui ont été apportées à la Loi type de la CNUDCI en 2006. Cette loi a établi un régime arbitral spécifique aux mesures provisoires et conservatoires. À un stade ultérieur, les règlements modifiés récemment par les centres d’arbitrage qui agissent sur la scène internationale ont beaucoup développé ce régime en le mettant en pratique. Maintenant, en présence d’un régime arbitral particulier régissant les mesures provisoires et conservatoires, il est opportun d’en évaluer en profondeur l’efficacité par rapport à celle du régime étatique classique régissant la même matière. Voilà l’objectif de cette thèse de doctorat qui présente nombre des propositions doctrinales et normatives dans le but d’améliorer autant que possible ce régime arbitral récent.
Keywords: Acte conservatoire; Arbitrage; Arbitrage commercial international; Arbitragem; Arbitration; Cours d'État; Droit comparé; Mesures provisoires

La prérogative de l'arbitre de relever un moyen d'office - Gaucher, Natalia (Aix-Marseille Université, 2016)

Arbitration and Justice Denial on Foreign Direct Investment - Hendrawan, Daniel (Indonesian Journal of International Law, 2016)
The economic growth in Indonesia is thrive. The Economic growth can not be separate of the role of investment in Indonesia. The population in Indonesia very much and also the location of the Indonesian state strategic pretty much made Indonesia enjoyed by citizens of Indonesia itself and also foreign nationals who wish to also invest in Indonesia. In Indonesia there is a domestic investment and foreign investment. In this paper will be devoted to foreign investment. Foreign investment that currently exist in Indonesia has a sizeable amount and spread from Sabang to Merauke, and also has sometimes caused the dispute. Dispute occurs either the foreign investment by government or also foreign investment with other parties outside the government well with other foreign investment, and also in the company itself. Foreign investment dispute settlement is not only done through the court owned by the government, but there are also ways of alternative dispute resolution outside the court . One of the alternative dispute resolution outside the court is Arbitration. Arbitration carried out as part of efforts to achieve settlement of the problem in terms of investment activity . Arbitration itself is set in the legislation applicable investment in Indonesia . The parties in capital investment may create a separate section in the agreement governing the settlement of disputes in the case of investments completed by Arbitration. In the event that the parties have arranged to settle the case with Arbitration, then the court is not allowed to try again or to interfere in the decision Arbitration. Arbitration is one of the solutions if justice denial occur in the settlement of foreign direct investment issue.
Keywords: Alternative; Arbitrage; Arbitragem; Arbitration; FDI; Foreign direct investment

Milletlerarası ticari tahkime ilişkin UNCITRAL model kanununda yargılama yetkisi kavramı ve tahkim mahkemesinin yargılama yetkisinin sınırları - Ki̇tapçi, Hakan (Selçuk Üniversitesi, 2016)
Keywords: Arbitration; Authority; International Arbitiation Law; Judgement; Milletlerarası Tahkim Kanunu; Tahkim; UNCITRAL Model Kanunu; UNCITRAL Model Law; Yargılama; Yetki

Developing efficient dispute resolution solutions for international commercial disputes: ways to address concerns associated with the combined use of mediation and arbitration by the same neutral - Nigmatullina, Dilyara (The University of Western Australia, 2016)
Securing fast, inexpensive and enforceable redress is vital for the development of international commerce. In a changing international commercial dispute resolution landscape, the combined use of mediation and arbitration, and particularly a combination where the same neutral acts as a mediator and an arbitrator (same neutral (arb)-med-arb), has emerged as a dispute resolution approach offering these benefits. However, to date there has been little agreement on several aspects of the combined use of processes, which the literature often explains by reference to the practitioner’s legal culture. There is a heated debate in the international dispute resolution community as to whether it is appropriate for the same neutral to conduct both mediation and arbitration. When the same neutral acts as a mediator and an arbitrator, caucuses become a primary concern. This is largely due to the danger that an arbitrator will appear to be, or actually be biased, and the risk that the process may offend the principles of due process.A review of the literature shows that the combined use of mediation and arbitration raises more questions and concerns than it offers answers and solutions. This thesis proposes remedies for this situation. The purpose of this thesis is twofold. First, to investigate ways to address concerns associated with the same neutral (arb)-med-arb, which should allow parties to benefit from time and cost efficiencies of the process and the ability to obtain an internationally enforceable result. Second, to examine whether the perception and use of the same neutral (arb)-med-arb varies depending on the practitioner’s legal culture. The research involved an analysis of legal sources complemented by a two stage empirical study conducted through questionnaire and interview.The thesis identifies three major ways to address concerns associated with the same neutral (arb)-med-arb: 1) the involvement of different neutrals in combinations, 2) procedural modifications of the same neutral (arb)-med-arb, and 3) the implementation of safeguards for using the same neutral (arb)-med-arb. It demonstrates that not all of these ways will achieve the goals of fast, inexpensive and enforceable dispute resolution. The results support the conclusion that the perception and use of the same neutral (arb)-med-arb varies throughout the world depending on the practitioner’s legal culture. This and other factors ultimately affect the choice of ways to address concerns associated with the same neutral (arb)-med-arb. Further to these significant results, the thesis argues that the same neutral (arb)-med-arb is not a ‘one-size-fits-all’ process. Other combinations discussed in the thesis require more attention from practitioners and academics.This thesis makes a substantial and original contribution to the understanding of combinations in international commercial dispute resolution in four ways. First, the empirical study is the first study to investigate specifically the use of combinations in international commercial dispute resolution. Its results shed light on the use of combinations in international commercial dispute resolution, their common triggers, the way in which the processes are combined most frequently, and the most common forms of recording the outcome of combinations. Second, the thesis synthesises existing ways of addressing concerns associated with the same neutral (arb)-med-arb in international commercial dispute resolution and groups them into the three major categories mentioned above. Third, having identified that there is scope for a more widespread use of combinations in international commercial dispute resolution, the thesis provides recommendations on how to enhance the use of combinations. Finally, the thesis highlights several areas where future research is needed.
Keywords: Arbitrage; Arbitragem; Arbitration; Combined processes; Commercial; Dispute resolution (Law); International; Legal culture; MARD; Mediación; Mediation; Mediação; Médiation; Same neutral

Due Process of Law in International Commercial Arbitration with Special Reference to Production of Documents - Zaheeruddin, Mohammed (Journal of Law and Criminal Justice, 2016)
Arbitration provides speedy mode of settlement of disputes between the parties. In the course of arbitration, the arbitration tribunal has an obligation to give a fair opportunity to the parties to present their case. The fair hearing or due process of law in arbitration requires that both parties must be treated equally and given opportunity to be heard, which include a party may request the other party for production of documents, which are relevant to the case. Hence, the international arbitration rules contained the provisions to order a party, on its own or on the request of a party, to produce the documents relevant to the outcome of the case. Unless otherwise agreed by the parties, any denial of this opportunity may be considered as a violation of due process of law, consequently a party may challenge the enforcement of the award.
Keywords: Arbitrage; Arbitragem; Arbitration; Discovery; Due process of law; Production of document; UNCITRAL

دور المحكم في الخصومة التحكيمية - حمودي, سمية (جامعة الوادي university el-oued, 2016)
تناولت هذه الدراسة أهم عنصر من عناصر عملية التحكيم، ألا وهو دور المحكم في خصومة التحكيم، وذلك من خلال معرفة شروط وإجراءات اختاره ومركزه القانوني وسلطاته والتزاماته . و قد بدأت الدراسة بمقدمة تضمنت العناصر الرئيسية للبحث وتناولنا ف الفصل الأول التعريف بالمحكم من خلال بيان معناه وتميزه عن القاضي والخبير والمصالح والوكيل، كذلك بيان الشروط الواجب توافرها في المحكم، كما تم توضيح المركز القانوني للمحكم في خصومة التحكم وكذا بيان طرق تشكيل هيئة التحكيم. كما تناولنا سلطات المحكم، سواء كانت ناشئة عن اتفاق التحكيم، أم المخولة له بموجب القانون، وبيان الالتزامات المرمية على عاتقه أثناء مباشرته لمهمته، وكل ذلك من خلال الفصل الثاني. ومن أهم النتائج التي خلصت إليها الدراسة، هي أن المحكم يتمتع بسلطات واسعة في خصومة التحكيم، إلا أن هذه السلطات الواسعة ليست مطلقة بلا قيود، وإنما يفرض على المحكم عدة التزامات منذ قبوله مهمة التحكيم وحتى صدور الحكم الفاصل في النزاع مرورا بالتزاماته أثناء سير الاجراءات مع مراعاة احترام المبادئ الأساسية للتقاضي. Cette étude portait sur l'élément le plus important du processus d'arbitrage, à savoir le rôle d'arbitre dans l'arbitrage des différends, et grâce à la connaissance des conditions et des procédures choisies statut juridique, pouvoirs et obligations. L'étude a commencé par une introduction comprenait les principaux éléments de la recherche et nous traitée dans le premier arbitre de définition de chapitre à travers les moyens de déclaration et de le distinguer du juge et expert, des intérêts et de l'agent, ainsi que la déclaration des conditions à remplir par l'arbitre, a également clarifier le statut juridique d'un arbitre dans le contrôle des différends, ainsi qu'une description des moyens de la formation du tribunal. Comme nous approchions les autorités de l'arbitre, que ce soit en raison de la convention d'arbitrage, ou qui lui sont conférés en vertu de la loi, et la déclaration des obligations jetées sur lui-même pendant l'exécution de leur mission, et tout au long du deuxième trimestre. Parmi les résultats les plus importants de l'étude, il est que l'arbitre dispose de larges pouvoirs à l'arbitrage des différends, mais ces larges pouvoirs est pas absolue, sans restrictions, mais a imposé à l'arbitre plusieurs engagements depuis accepter la tâche d'arbitrage et jusqu'à la délivrance de l'arbitre décisif dans le conflit par ses obligations au cours de la procédure, avec en tenant compte du respect des principes de base du litige
Keywords: Arbitrage des différends; Arbitration; Arbitre; Obligations de l'arbitre; Pouvoirs de l'arbitre; Statut juridique; Tribunal arbitral; التزامات المحكم; الخصومة التحكيمية; المحكم; المركز القانوني; سلطات و; هيئة التحكيم

Online dispute resolution: The future of justice - Mania, Karolina (International Comparative Jurisprudence, 2015)
The purpose of this study is to present the main facets of online dispute resolution, including a definition of the term, the types of resolution available, and the most recent legal regulations in this area. The article is an in-depth study of this field, discussing online mediation and electronic arbitration, their uses and their relationships with e-commerce. The strengths and weaknesses of online dispute resolution are identified and used to help formulate de lege ferenda stipulations. The paper is divided into three parts. Part I looks at preliminary aspects of online dispute resolution (ODR), including a definition of the term and an examination of its phases of development, implementation examples and the relationship between ODR and technology. Part II is devoted to examining the two most frequent forms of ODR: online mediation and electronic arbitration. Part III is an analysis of consumer disputes arising from commercial transactions made using electronic communications. As an example of the implementation of ODR, the author emphasises the importance of new European regulations on that and alternative dispute resolution (ADR): Directive 2013/11/EU of the European Parliament and of the Council of 21 May 2013 on alternative dispute resolution for consumer disputes and amending Regulation (EC) No 2006/2004 and Directive 2009/22/EC (Directive on consumer ADR), and Regulation (EU) No 524/2013 of the European Parliament and of the Council of 21 May 2013 on online dispute resolution for consumer disputes and amending Regulation (EC) No 2006/2004 and Directive 2009/22/EC (Regulation on consumer ODR).
Keywords: ADR; Alternative dispute resolution; Consumer dispute; E-commerce; Electronic arbitration; ODR; Online Dispute Resolution; Online mediation

Les conflits d'intérêts en arbitrage commercial international - Castres Saint Martin, Constance (Université Paris 2, 2015)
Le conflit d'intérêts est un sujet passionnant notamment en raison de son omniprésence dans l'actualité. Approximative, l'expression empruntée au magma lexical des politiciens et juristes anglo-américains s'est récemment diffusée en France dans le monde des affaires et aussitôt reprise par le jargon médiatique pour désigner des éventuelles interférences de l'intérêt privé dans l'exercice de pouvoirs de nature privée ou publique. Il n'existe en l'état actuel du droit positif français aucune réglementation spécifique de ces « conflits d'intérêts », pas plus en droit privé qu'en droit public, alors même qu'on se préoccupe de leur prévention tandis que leur sanction relève de qualifications plus générales. Il convient donc de s'interroger sur la définition et la valeur opératoire de cette notion et le régime juridique qui pourrait lui être réservé, ce que l'on se propose d'entreprendre dans la sphère du droit privé et par préférence dans le champ de l'arbitrage commercial, particulièrement exposé aux appétits hégémoniques des droits anglo-américains. Conflict of Interests is a fascinated subject due to its pervasiveness in the economic life. This approximated expression, borrowed from the politicians and Anglo-American lawyers' jargon, has recently spread into the French business world and was taken up by the media to designate the interferences of private interest in the exercise of powers of private or public nature. In the current state of French Law, there is no specific rule governing conflicts of interests, neither in Private Law, nor in Public Law. Indeed, politicians and scholars paradoxically only focus on their prevention, whereas their sanctions fall within the scope of broader notions. The aim of this research is to lay down the definition, the operative value and the regime of conflict of interests. The scope of this research shall be, within Private Law, Commercial Arbitration Law, which is particularly exposed to the hegemony of Anglo-American laws.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitral abuses; Arbitration; Confiance légitime (droit); Confidence principle; Conflict of interests; Conflit d'intérêts; Conflits d'intérêts; Disclosure; Due process; Dérives arbitrales; Impartiality; Impartialité; Independence; Indépendance; Issue conflict; Justice arbitrale (administration); Principe de confiance; Procès équitable; Révélation; Transparence; Transparency

La médiation en santé : Contribution à une étude des conflits et des différends dans la relation de soins - Gibelin, Anne (Université de Montpellier, 2015)
La médiation peut se définir comme l’action de celui qui est médiateur et qui s’interpose entre deux ou plusieurs personnes pour résoudre un conflit ou un différend. Dans le domaine de la santé et plus particulièrement dans la relation de soins, des conflits et des différends peuvent survenir. La santé touche en effet à l’état des personnes, à leur intimité, à leur intégrité et les relations qui en découlent avec les professionnels de santé sont nécessairement empreintes d’une certaine sensibilité. C’est pourquoi ce secteur est considéré comme pourvoyeur potentiel de tensions. Il est donc intéressant d’étudier la résolution des conflits ou différends inhérents à la relation de soins, par un mode singulier et alternatif de règlement des différends : la médiation. L’étude de la nature juridique de ce processus est indispensable pour le différencier des autres modes alternatifs et exposer clairement ses forces et ses faiblesses. Ceci permettra ensuite de lui appliquer un régime juridique adéquat. En raison des manquements actuels, particulièrement au regard de l’encadrement du statut de médiateur, le constat d’un inévitable remaniement du régime de la médiation devra être effectué. Celui-ci devra impérativement allier souplesse et encadrement du mécanisme dans le but d’une efficacité optimale.
Keywords: Différends; Mediation; Médiation; Relation; Relations médecin-patient; Règlement de conflits; Santé; Soins

International Standards for Commercial Mediators - To, Christopher (University of Stirling, 2015)
This paper talks about the international standards for commercial mediators. It introduces the standards of eight different jurisdictions and afterwards, evaluates whether there should be one accrediting standard for all international commercial mediators. In the introduction chapter, the paper talks about the problems with the current legal system and then explains the growth of mediation in today’s society. By discussing the nature and practice of mediation, whether mediation should be compulsory or voluntary in light of Article 6 of the European Convention on Human Rights, rationale of the various jurisdictions covered, the paper then talks about the attributes that make a good mediator as well as the accreditation and training of mediators. From chapter two to chapter nine, the paper focuses on eight jurisdictions in which mediation is firmly enshrined within one legal culture to those that are just embarking on the concept (namely Australia, New Zealand, Indonesia, Malaysia, India, Hong Kong, California and Canada). Each chapter talks about the developments of commercial mediation, law and institutions as well as training and accreditation of mediators within their respective jurisdictions. In the concluding chapter, it discusses whether there should be one accrediting standard for international commercial mediators by exploring the advantages and disadvantages of having one accrediting standard as well as the author’s analysis and point of view on the subject.
Keywords: Commercial mediator; International standards; Mediation; Mediator; Médiateur

The Role of Arbitration Institutions in the Development of Arbitration in Africa - Onyema, Emilia (Arbitration Institutions in Africa Conference, 2015)
This conference which held at the premises of the African Union Commission, Addis Ababa on 23 July 2015 examined the functions of arbitration institutions in Africa. The conferenced discussions focused on sharing experiences by users and providers for the effective administration of arbitration references in the continent. The conference was organised by Dr Emilia Onyema of the School of Law, SOAS. KEY ARTICLES : - Regional Arbitration Institution for ECOWAS: Lessons from OHADA Common Court of Justice and Arbitration ; - The Role of Arbitration Institutions in the Development of Arbitration in Africa ; - “Africa’s Century” – The rise of International Arbitration in Africa and what it means for users of Arbitral Institutions in Africa ; - Reawakening Arbitral Institutions for Development of Arbitration in Africa ; - Opening Up International Arbitration in Africa ; - Africa as a Viable Space for Arbitration: Role of National Courts and Laws - The Role of Counsel in Promoting African Arbitral Institutions ;
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Conference

Disputes in the Digital era : the evolution of dispute resolution and the model ODR system - Lekkas, Zissis (Université Toulouse 1 Capitole, 2015)
Le sujet de la thèse est la résolution en ligne des litiges (ODR) et l'objectif de la thèse est de proposer un modèle de système ODR basé sur l'expérience du mouvement de résolution des différends. ODR n’est pas un phénomène isolé de ces derniers temps, mais en raison de l'évolution des conflits et la résolution des différends. Initialement, les différends survenus entre les parties à la proximité géographique et pour laquelle les tribunaux traditionnels sont le principal moyen de résolution. Cependant, comme les gens ont commencé à voyager de plus grandes distances et de communiquer de loin, les conflits ont évolué comme ils ont augmenté en nombre, sont devenus frontière plus complexe et de plus en plus transversale. Résolution des différends évolués en règlement des différends parallèle et alternatif (ADR) a été utilisée. Cependant, les conflits ont évolué une fois de plus quand le monde est entré dans l'ère numérique. Non seulement les conflits sont devenus encore plus transfrontalier, mais de nouveaux conflits sont apparus qui proviennent exclusivement dans le cyberespace. Afin de satisfaire aux exigences de l'ère numérique, la résolution des différends fit sortir le concept de l'ODR. ODR est née de la combinaison de l'ADR et de la technologie de l'information et de la communication (TIC) de l'ère numérique. D'autres moyens de règlement des différends ont été transférés dans le monde virtuel et ont donné naissance à la résolution des litiges en ligne. ADR et ODR sont examinés largement, et l'examen comprend leurs concepts, leur origine, les principales formes de négociation, de médiation et d'arbitrage et leurs équivalents en ligne, ainsi que leurs avantages et leurs inconvénients. La thèse illustre l'évolution des conflits et la résolution des différends de l'ère analogique, lorsque la résolution des différends était face à face, à l'ère du numérique, lorsque les différends sont réglés dans le cyberespace. Il démontre que l'ODR est une nécessité de l'ère numérique, mais aussi qu'il a le potentiel pour être un moyen révolutionnaire, efficace et réussi à résoudre les différends; d'une manière qui sera l'avenir de la résolution des différends. Sur la base de l'expérience accumulée par l'examen de l'évolution de la résolution des différends et sur ? Lla base des conclusions tirées, la thèse formule une proposition pour le système ODR. La thèse décrit le système ODR, de son processus en trois étapes et la nécessité de l'arbitrage en ligne, sur le réseau ODR, la régulation du système ODR, l'architecture technologique des fournisseurs ODR, leur financement, ainsi que les mesures nécessaires de la sensibilisation et la confiance afin que ODR remplit son plein potentiel.
Keywords: Arbitrage; Arbitragem; Arbitration; Commerce électronique; Modes électroniques de règlement des litiges; Online Dispute Resolution; Système ODR

A arbitragem em juízo - Valença Filho, Clávio de Melo (Universidade de São Paulo, 2015)
Situado no centro do sistema jurídico transnacional da lex mercatoria, o árbitro é autoridade estrangeira em relação ao juiz nacional do foro. O sistema da lex mercatoria se distingue do nacional pela sensibilidade de suas reações aos ruídos provenientes do sistema da economia, não pelo vinculo a território. O árbitro não tem foro, tem setor; fora dele, a arbitragem se adapta mal. Por impor limites à função jurisdicional do Estado-juiz, a convenção de arbitragem constitui regra de competência internacional do juiz do foro e, de competência internacional indireta do árbitro e dos juízes estrangeiros. Profere sentença inexistente o juiz nacional que atropela as regras de sua jurisdição internacional. Também não ingressam no sistema do foro as decisões proferidas por quem não se adeque às regras de jurisdição internacional indireta do foro. Isso ocorre quando a sentença arbitral ou o julgamento estrangeiro em lide cujo objeto é a própria arbitragem agridem a intensidade que o foro atribui aos efeitos negativos da competência-competência e da convenção de arbitragem. O efeito negativo da competência-competência não decorre da convenção de arbitragem, mas da proteção que o ordenamento outorga à mera aparência. Os efeitos da convenção de arbitragem dizem respeito ao mérito das lides, o negativo e o positivo. Aquele, como o negativo da competência-competência, ostenta natureza de direito público subjetivo. Este, de direito privado subjetivo. Todos constituem direito subjetivo em sentido técnico, na medida em que permitem provocar o Estado-juiz com o fito de apoiar a instauração da instância ou assegurar o afastamento do próprio Estado-juiz. O paralelismo processual tem origens distintas segundo ocorra entre autoridades vinculadas ao mesmo sistema ou a sistemas distintos. Na primeira hipótese, decorre de error in judicando; na segunda, é consequência natural da ausência de harmonia entre os sistemas. Entre árbitro e juiz, não se resolve com remédios concebidos para o conflito de competências, como a litispendência ou o incidente constitucional perante o STJ. Só uma estrutura convencional de acoplamento entre sistemas permitiria a harmonização. Já o efeito negativo da convenção de arbitragem pode ser mitigado em função de risco de denegação de justiça, para devolver ao Estado-juiz a jurisdição de urgência ou a necessária ao julgamento de pretensões do devedor em dificuldades. A abertura da falência não interfere na capacidade do credor ou na natureza de seus bens ou direitos, não suspende a tramitação da arbitragem e não impede a instauração de novas instâncias. É válida a convenção de arbitragem estipulada após a falência e a massa tem o direito de participar da arbitragem, junto com o devedor. The transnational legal system of lex mercatoria is not linked to a given territory. Its differentiation from the civil justice system is based upon its capacity to react to the needs of the economy. The fact that the arbitrator is positioned in the center of the lex mercatoria system makes the arbitrator foreign to the courts and its legal system. By imposing limits upon the jurisdictional State function, the arbitration agreement and its regulation serves as an international jurisdiction rule for the forum court. It also works as an indirect international jurisdiction rule through which the national court inspects the jurisdiction of an arbitrator or a given foreign court. National courts decisions that are rendered in disregard of international jurisdiction rules are non-existent. Foreign decisions that are incompatible with indirect international jurisdiction rules must be set aside by the forum courts. This is the case when arbitral awards and foreign judgments related to arbitration are disrespectful to the forum criterions binding the negative effect of the competence-competence and to the negative effect of the arbitration agreement. The negative effect of competence-competence is not a consequence of the agreement to arbitrate, but of the protection that the legal system gives to its mere appearance. The effects of the arbitration agreement concern the merits of the disputes, the negative and the positive. The former, as well as the negative effect of the competence-competence principle, are in nature of subjective public law. The latter is of the nature of subjective private law. All constitute subjective rights in the technical sense, in the way in which they allow the court system to support the commencement of proceedings or to ensure the removal of the national courts. Procedural parallelism has different origins depending upon whether it occurs among arbitrator and courts belonging to the same legal system of the court deciding the conflict or to a different one. In the first hypothesis, it originates from error in judicando; in the second, it is a natural consequence of the lack of harmony between the systems. Between arbitrator and judge, such lack of harmony cannot be resolved through the remedies created to address jurisdictional conflict, such as lis pendens or the constitutional incident before Brazils STJ. Only by coupling different legal systems through conventional structure would harmonization arise. The negative effect of the arbitration agreement is mitigated by conferring upon courts jurisdiction for the grant of interim and provisional measures based on the risk of denial of justice. By its turn, a bankruptcy filing does not interfere with the creditors capacity nor with the nature of its assets or rights, and it does not suspend the arbitration proceeding or the commencement of new proceedings. The agreement to arbitrate after the initiation of bankruptcy proceedings is valid and the estate-in-bankruptcy may participate in the arbitration along with the debtor.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; Arbitre; Argentina; Bankruptcy; Brasil; Civil Procedure; Conflict of jurisdictions; Direito comparado; Estados Unidos; Falência; França; Insolvency; Judge; Lex mercatória; Processo civil; Urgent measures

Economic and Empirical Analysis of Contractual Dispute Resolution - Miller, Samuel Mark (Vanderbilt University, 2015)
This dissertation uses Python-based programming to retrieve and analyze a sample of approximately 400,000 material contracts that companies filed with the Securities and Exchange Commission between 2001 and 2013, focusing on the dispute resolution mechanisms specified therein. The first chapter considers the effectiveness of two state-level efforts to attract dispute resolution business, examining how specialized “business courts” and the Revised Uniform Arbitration Act affected arbitration and choice-of-forum clause use in these material contracts. The second chapter examines whether and how companies and executives “customized” their arbitration clauses in response to Internal Revenue Code Section 409A, which increased both the likelihood and the complexity of potential disputes between these parties. The third chapter considers how companies and executives responded when the Supreme Court overturned the Ninth Circuit’s anomalous refusal to enforce employment-related arbitration clauses. Each chapter finds that contracting parties adjusted their dispute resolution provisions in response to the policy change(s) at issue – suggesting that for the sophisticated parties in my dataset, these provisions receive careful thought and are not mere “boilerplate.”
Keywords: Arbitrage; Arbitragem; Arbitration; Contracts; Dispute resolution; Econometrics

Arguments in favour of reconceptualising the fair and equitable treatment (FET) standard in international investment arbitration : developing countries in context - Islam, Rumana (University of Warwick, 2015)
The Fair and Equitable Treatment (FET) standard is the most important and, because of its flexible nature and its status as a ‘catch-all’ provision, most controversial investment protection standard in international investment treaties. The standard imposes the most far-reaching obligation of any aspect of such treaties. This thesis’ core contention is that the current investment tribunals’ interpretation of the FET standard prioritises the interests of foreign investors and neglects the perspectives of host developing countries. Therefore there is a pressing need to reconceptualise the interpretation of the FET standard. In service to depicting the perspectives of host developing countries, this thesis advances an understanding of classifications such as ‘developing’ and ‘developed’ that reflects the issues and challenges that these countries face in the investment dispute context, such as their lack of resources, administrative capacity, technology, and infrastructure, as much as the economic and social level of development international organisations generally emphasise in their classifications. It addresses socio-political circumstances such as political instability, social unrest, conflict and its aftermath, social and political transition, and economic crises and their impact on host developing countries in the investment dispute context. Through a detailed study of the approaches they have taken to such issues in their interpretation of the breach of FET standard in disputes involving host developing countries, it shows that current investment tribunals have taken inconsistent and inadequate approaches to the issues host developing countries face. It argues that a reconceptualised interpretation of the FET standard which acknowledges the developmental issues and challenges this thesis has identified would accommodate the needs of the host developing countries while continuing to give reasonable protections to foreign investors and therefore serve the needs of the system as a whole.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Developing countries; Dispute resolution (Law); Equity; Foreign investment; Free trade agreemtment; International business enterprises; Investments; Unfair competition

Partes e terceiros na arbitragem - Costa, Guilherme Recena (Universidade de São Paulo, 2015)
A tese discute o problema dos terceiros na arbitragem. Ela distingue os planos substantivo (contratual) e processual (jurisdicional) da arbitragem e, portanto, o status de parte e terceiro com relação, respectivamente, à convenção de arbitragem e ao processo arbitral. Depois de desenvolver as premissas teóricas na Parte 1, a Parte 2 expõe as teorias contratuais e societárias por meio das quais um não-signatário pode ficar vinculado à convenção de arbitragem, com destaque para a extensão a todos os acionistas da companhia da cláusula compromissória estatutária, bem como para a aplicação do princípio da boa-fé objetiva (teoria dos atos próprios, estoppel) para impedir com que determinados signatários burlem a convenção de arbitragem ao incluir terceiros no polo passivo da demanda ou, ainda, para impor a arbitragem a não-signatários que derivaram um benefício do contrato inter alios. Na Parte III, a atenção volta-se para o processo e a sentença arbitral. Expõe-se uma teoria dos efeitos da sentença, buscando-se explicar a sua potencial eficácia ultra partes com base: a) na necessidade de realizar o direito da contraparte à tutela jurisdicional (adquirente do direito litigioso, sucessores post rem judicatam); e b) na identificação de nexos de prejudicialidade-dependência permanente entre as relações jurídicas no plano do direito material (terceiro titular de situação dependente). Refutam-se, em passo seguinte, teorias que preconizam o valor absoluto da sentença. Oferece-se, como núcleo da tese, uma reconstrução dogmática das modalidades de intervenção de terceiro, buscando adaptá-las à arbitragem para alcançar, em cada situação, um justo equilíbrio entre as expectativas contratuais das partes originárias e a natureza privada da arbitragem, de um lado, e os efeitos da sentença perante terceiros, de outro. Conclui-se que, em alguns casos, legitima-se o terceiro a intervir voluntariamente, mesmo contra ou independentemente da vontade das partes, se ele estiver sujeito aos efeitos da sentença. Em hipótese excepcionalíssimas, ademais, a parte pode sujeitar um terceiro aos efeitos de intervenção, provocando a sua assistência no processo arbitral. The thesis addresses the problems of third parties in arbitration. It distinguishes the substantive (contractual) and procedural dimensions of arbitration and, hence, the status of parties and third parties in connection with, respectively, the arbitration agreement and the arbitral proceedings. After spelling out theoretical premises in Part 1, Part 2 covers the contractual and corporate theories by which a non-signatory may be bound by the arbitration agreement, highlighting the extension to all shareholders of the agreement in the corporate bylaws, as well as the application of the equitable doctrine of estoppel to bar certain signatories from avoiding the arbitration agreement by including third parties as defendants or even to impose arbitration onto non-signatories who derived a benefit from the contract inter alios. In Part III, my attention turns to the proceedings and the arbitral award. I set out a doctrine of the effects of judgments, seeking to explain their potential effects on third parties based: a) on the prevailing need to preserve the counterpartys right to a binding declaration on its asserted claims (acquirers, successors post rem judicatam); b) the identification of substantive ties between legal relationships that make the third parties rights permanently dependent on the situation between the parties. I then refute theories ascribing absolute value to the award vis-à-vis third parties. As the core of the thesis, I offer a doctrinal reconstruction of third party interventions, seeking to adapt them to arbitration in order to achieve, in each situation, a fair balance between the contractual expectations of the original parties and the private nature of arbitration, in one hand, and the effects of the award on third parties, on the other. I conclude that a third party should be allowed to intervene, albeit against the will of the parties, if it is subject to the concrete effects of the arbitral award. In exceptional situations, moreover, a party may vouch in a third party, who will then be bound by the determinations of factual and legal issues made in the award.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration Agreement; Coisa julgada; Direito processual civil; Effects of arbitral awards; Non-signatories; Third parties; Third party intervention; Tierces parties

Convergence of international trade and investment law in practice : how should investor-state arbitral tribunals engage with trade norms? - Chevry, Jonathan (European University Institute, 2015)
This thesis aims to provide an analytical framework to which investor-State arbitral tribunals can refer in cases where international trade law is invoked. The starting point of the present study is the trend in commentary on international trade and investment law, which makes the argument that international trade and investment law should be reconciled due to the clear "convergence" between (some of) their constitutive elements. This convergence argument is not misguided: there are similarities between the underlying principles of global trade and investment and, as such, a better coordination of these principles would be helpful for several reasons. Such reasons include legal certainty, reduction of transaction costs, better coherence in the operation of international agreements that now combine both trade and investment provisions, to name a few. However, no matter how reconcilable or converging the two disciplines may be, their enforcement mechanisms are structurally different and are likely to remain so even if the reforms towards a modernization of the investment dispute settlement (currently discussed at the EU policy level) are eventually implemented in the near future. In light of this last point, it is possible to claim that integration between trade law and investment law will only have limited or even negative effects if the trade and investment adjudicators continue to exercise their functions in an isolated manner, without taking cognizance of (i) the norms contained in the other discipline and (ii) the other adjudicator's scope of authority. Effective convergence of trade and investment entails a two-way process pursuant to which one adjudicator can use (i.e. take into account, refer to, apply, interpret and enforce) the law of the other and vice-versa. The thesis envisages one of the two dimensions of this process, namely the use of trade law by the investment adjudicator. Looking into the details of the convergence argument, the role of investment dispute settlement mechanism and the use of trade norms over the past two decades by litigants and arbitrators, the present study identifies both the legal techniques and obstacles these actors shall apply or go beyond in order to use trade norms in the most appropriate way and, more importantly, benefit from this use.
Keywords: Arbitrage; Arbitragem; Arbitration; Foreign investment; Foreign trade regulation; International commercial arbitration

Milletlerarası ticari tahkimde hakemlerin bağımsızlığı ve tarafsızlığı - Kayali, Di̇dem (Ankara Üniversitesi, 2015)
Milletlerarası ticarî sözleşmelerden kaynaklanan uyuşmazlıklar söz konusu olduğunda akla ilk gelen çözüm yöntemi tahkimdir. Zira milletlerarası ticarî tahkimin devlet yargılamasına göre önemli avantajları bulunmakta, hakemlerin bağımsızlığı ve tarafsızlığı ise bu avantajların en önemlilerinden biri olarak karşımıza çıkmaktadır. Bu çerçevede, tahkim süreci başlarken hakemlerin bağımsız ve tarafsız olmaları ile süreç tamamlanana kadar bu şekilde kalmaları gerektiği hususu milletlerarası ticarî tahkimin en temel ilkesi olarak genel kabul görmüş; millî kanunlarda, milletlerarası metinlerde ve milletlerarası tahkim kurumlarının düzenlemelerinde doğrudan ya da dolaylı bir şekilde yerini almıştır. Bu çalışmada da bağımsızlık ve tarafsızlık kavramlarından ne anlaşılması gerektiği, bu kavramların uygulamada nasıl yorumlandığı, tahkim yargılamasındaki önemi ve nasıl korunduğu, yukarıda bahsedilen düzenlemeler ile millî mahkemeler ve milletlerarası tahkim kurumlarının kararları ışığında incelenmiştir. When disputes emerging from international commercial contracts are in question, arbitration is the first resolution method that comes to mind. This is because international commercial arbitration has significant advantages compared to the state jurisdiction where impartiality and independence of arbitrators is considered to be one of the most important ones of those advantages. In this framework, the necessity that arbitrators ought to be impartial and independent from the very start till the end of the arbitration process has gained general acceptance as the basic principle of international commercial arbitration and directly or indirectly has taken its place in national laws, international texts and regulations of international arbitration institutions. In this study, the meaning of independence and impartiality, how they are interpreted in practice, the importance of these concepts in international commercial arbitration and how they are protected are examined in the framework of above mentioned regulations and decisions of national courts and international arbitration institutions.
Keywords: Arbitrage; Arbitration; Arbitrators; Arbitre; Bağımsızlık; Hakemler; Impartiality; Impartialité; Independence; International Arbitiation Law; International Trade; International disputes; Milletlerarası Tahkim Kanunu; Tahkim; Tarafsızlık; Uluslararası ticaret; Uluslararası uyuşmazlıklar

Building legal bridges: fostering eastern Africa integration through commercial arbitration - Muigua, David K. (Alternative Dispute Resolution, 2015)
This paper explores the feasibility of commercial arbitration as a means to foster the process of Eastern Africa integration. The author proffers an argument in the context of Eastern Africa integration, that commercial arbitration offers a better platform for dealing with commercial disputes that are bound to arise considering the differing personal or state interests in the ongoing Eastern Africa integration, as compared to national Courts. This discourse is premised on the fact that the five member countries making up the East African Community (EAC) have different legal systems and this presents a major challenge in harmonising the various legal systems. This also affects the possible use of courts in managing the potential transnational commercial disputes due to the potentially different rules of procedure and practice. The paper briefly examines the state of commercial arbitration in the EAC Member States with a view to identifying the existing frameworks and any impediments in their effectiveness. Finally, the author makes a case for utilizing commercial arbitration to build bridges and foster Eastern Africa integration for development.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration

Convention on the Recognition and Enforcement of Foreign Arbitral Awards (New York, 1958) - UNCITRAL (United Nations, 2015)

L'Acte Uniforme OHADA relatif à l'Arbitrage (AUA) à l'épreuve des standards transnationaux de la justice arbitrale : approche comparée de droit international privé - Sossou, Cassius Jean (Université de Genève, 2014)
Après plus de deux décennies d'expérimentation, le moment est venu pour l'Organisation pour l'Harmonisation en Afrique du droit des Affaires ou OHADA de marquer une pause et de récapituler l'application de ses valeurs normatives aux différents domaines relevant du champ matériel d'application du Traité ayant fondé l'organisation. L'intérêt et l'utilité d'un tel bilan passent, entre autres, par la relecture de sa norme juridique sur l'arbitrage ad hoc qu'est l'Acte Uniforme OHADA relatif à l'Arbitrage (AUA). Ce bilan doit pouvoir se faire non pas au regard de ce qui a été dit et analysé. Il s'impose plutôt d'examiner la perspective de ce qui lui reste d'exceptionnel et d'inédit. Sur ces aspects inédits, il manque une analyse comparée au plan du droit international, maillon manquant des différentes approches abordées. C'est à cet exercice intellectuel que s'est livrée notre étude, procédant à la relecture à l'aune des standards transnationaux de la justice arbitrale par le prisme d'autres normes sur l'arbitrage international, qu'elles soient d'origine étatique ou conventionnelle, de la pratique internationale et dans une certaine mesure de la jurisprudence.
Keywords: Arbitrage; Arbitrage (droit international privé); Arbitrage international; Arbitragem; Arbitration; Convention d'arbitrage; Droit international privé; International; Juridiction arbitrale; Justice arbitrale; OHADA; Organisation pour l'harmonisation en Afrique du droit des affaires; Procédure arbitrale; Schiedsentscheid; Schiedsgericht; Schiedsgerichtsbarkeit; Schiedsrichterliches Verfahren; Schiedsvereinbarung; Sentence arbitrale; Standards transnationaux; Tribunal arbitral

Les procédures de règlement de la double imposition résultant de la correction des prix de transfert entre entreprises associées - Hublot, Marie-Laure (Université Paris 2, 2014)
Avec l’accroissement des échanges transfrontaliers entre entreprises associées et des moyens de contrôles des transactions internationales par les administrations fiscales, les risques de différends en matière de prix de transfert augmentent nécessairement. Si ces conflits ne sont pas résolus, ils peuvent entraîner des doubles impositions, principalement économiques, et constituer des obstacles pour la libre circulation des biens et des services dans une économie globalisée. Les contribuables et les Etats ont donc besoin de procédures efficaces pour résoudre ces situations, unanimement dénoncées par les organisations internationales et les contribuables. Or les procédures actuelles ne sont pas totalement satisfaisantes. La Commission européenne, puis l’O.C.D.E ont récemment mené des travaux d’envergure visant à en améliorer les mécanismes. Le règlement de la double imposition en matière de prix de transfert est incontestablement un sujet d’actualité. Ces travaux invitent à une analyse critique de l’ensemble des mécanismes internationaux de règlement de la double imposition résultant de la correction des prix de transfert. Ces procédures sont étudiées, les causes de dysfonctionnement recherchées et des mesures d’amélioration sont proposées, notamment à la lumière des récents travaux des organisations internationales. La première partie est consacrée à la procédure amiable dans le cadre des conventions fiscales bilatérales. L’analyse menée suit une approche chronologique des étapes de la procédure, depuis son ouverture jusqu’à la mise en oeuvre de l’accord amiable. La seconde partie traite des voies nouvelles de règlement des doubles impositions que constituent la médiation, la conciliation et l’arbitrage en matière fiscale. Une large place est consacrée à l’arbitrage qui est analysé tant sur le plan conventionnel, puisqu’il a été récemment intégré dans les conventions modèles O.C.D.E. et O.N.U., que dans le cadre de la convention européenne d’arbitrage. Cette étude fait largement référence à l’approche de l’O.C.D.E. et des principaux Etats partenaires de la France. Néanmoins, il ne s’agit pas là d’un exercice de droit comparé mais seulement d’une mise en exergue d’autres pratiques pour servir le propos. With increasing cross-border trade between associated enterprises and means of control of international transactions by the tax authorities, the risk of disputes over transfer pricing necessarily increase. If these conflicts are not resolved, they can lead to double taxation, mainly of economic nature, and constitute obstacles to the free movement of goods and services in a globalised economy. Taxpayers and States therefore need effective procedures to resolve these situations, unanimously denounced by international organizations and taxpayers. However, current procedures are not entirely satisfactory. The European Commission and the O.E.C.D. have recently completed extensive work to improve the mechanisms. Dispute resolution in transfer pricing is certainly a hot topic. A critical analysis of all international settlement mechanisms of double taxation arising from transfer pricing adjustments is conducted. These procedures are examined, the causes of dysfunction sought and improvement measures are proposed, particularly in light of recent work of international organizations. The first part is devoted to the mutual agreement procedure under bilateral double tax treaties. The analysis is carried out following a chronological approach of the stages of the procedure, from its opening till the implementation of the mutual agreement. The second part deals with the new ways of resolving transfer pricing double taxation that are mediation, conciliation and arbitration in tax matters. Emphasis is on arbitration that is analysed both in conventional terms, as it has recently been integrated into the O.E.C.D. and U.N. model conventions, and as part of the European arbitration convention. This work makes extensive reference to the O.E.C.D and France key partners’ approaches. Nevertheless, it is not a work of comparative law but only examples to illustrate other practices
Keywords: Ajustement corrélatif; Arbitrage; Arbitrage commercial international; Arbitration; Conciliation; Double imposition; Droit international privé; Entreprises associées; Entreprises communes; Impôt; MARD; Mediación; Mediation; Mediação; Médiation; OCDE; Prix de cession interne; Prix de transfert; Procédure amiable; Procédure d'arbitrage

Alle origini della mediazione - Donati, Viola (Università di Pisa, 2014)
L’esigenza di alleggerire il carico dei tribunali mediante forme di soluzione diverse e alternative al processo giurisdizionale trae le sue origini da esperienze culturali remote: l’arte della composizione del conflitto rappresenta un'attività di cui l’uomo si è fin da subito dovuto occupare, per lo meno dal momento in cui ha cominciato a vivere all’interno di una comunità, proprio perché si tratta di un’attività che sfiora tutti gli aspetti della vita sociale. La mediazione ha origini antichissime, infatti la necessità di sviluppare nei secoli procedure alle quali ricorrere per garantire un'ordinata convivenza e armonia sociale risale già all'antica Roma del V secolo A.C.: la prima delle XII Tavole (il più antico diritto scritto dell’antichità romana), richiama il tentativo di compromesso da esperirsi davanti al pretore con cui le parti in lite trovano un accordo sull’oggetto del contendere, nel qual caso il giudice è tenuto a consacrarlo con l’emanazione della sentenza mentre in caso di mancato raggiungimento di un accordo allora si sarebbero adite le vie giudiziali instaurando il processo. Le origini della mediazione trovano fondamento in tempi antichi anche in Paesi dell’estremo oriente ed in particolare in Cina dove la mediazione fu lo strumento principale nella risoluzione delle dispute: Confucio sosteneva che il modo migliore per dirimere una disputa fosse la persuasione morale e il raggiungimento di un accordo, piuttosto che la coercizione del Sovrano. L’idea stessa di “compromesso” è profondamente radicata nella cultura cinese, infatti non tener in alcun conto gli interessi dell’altra parte è considerato particolarmente deplorevole sul piano etico-giuridico ed il pensiero confuciano è promotore della mediazione, tanto che l’istituto continua tuttora ad essere praticato nella Repubblica Popolare Cinese. In tempi più recenti, dopo l’unificazione del Regno d’Italia e la conseguente stesura del codice di procedura civile del 1865, il legislatore ha dedicato ampio spazio alla composizione bonaria delle controversie, disciplinando la conciliazione nel titolo preliminare all'art.1, dando vita così alla figura professionale del giudice conciliatore: caratteristiche essenziali del procedimento consistevano nella compresenza della funzione conciliativa con quella giurisdizionale nel giudice conciliatore, la municipalità del giudice stesso e infine la completa assenza di formalità (il rito si svolgeva verbalmente) per consentire a tutti un facile accesso alla procedura. Se invece apriamo il Codice di procedura vigente, per trovare un accenno alla conciliazione bisogna aspettare l'art. 320, e questa sfiducia a cui è andata in contro la figura del giudice conciliatore è arrivata fino ai nostri giorni. Negli USA la mediazione fu introdotta come sistema volontario (nelle controversie sindacali tra le compagnie ferroviarie e i loro dipendenti) nel 1887, con la legge sul commercio tra gli Stati (Intestate Commerce Act), e a partire dalla fine degli anni ’60 trovò un applicazione sempre maggiore. Ma la svolta fondamentale si ebbe nel 1998, in occasione della modifica del Titolo 28° della Carta dei Diritti e nell'Alternative Dispute Resolution Act, che consacrarono il successo della cultura alternativa della gestione del conflitto nella società americana. Oggi il ricorso agli A.D.R. ha portato ad una riduzione del contenzioso giudiziario di quasi il 90%. Visto l’esito positivo avutosi oltreoceano, nell’aprile del 2002 la Commissione Europea ha presentato un Libro Verde relativo ai modi alternativi di risoluzione delle controversie in materia civile e commerciale per promuovere l’utilizzo della mediazione, ed in seguito alla Direttiva n. 2008/52/CE il governo italiano ha emanato il D.lgs. 28/2010 al fine di coordinare le disposizioni vigenti in materia di mediazione e conciliazione in ambito civile e commerciale, solo che appena due anni dopo, il 6 dicembre 2012, la Corte costituzionale ha dichiarato l'illegittimità del decreto per eccesso di delega legislativa, così che il governo Letta ha cercato di disciplinare nuovamente l'istituto con la Legge n.98/2013, sebbene stavolta la mediazione sia stata prevista come temporanea perché contemplata come obbligatoria per i soli quattro anni successivi alla sua entrata in vigore, a metà dei quali il ministero di giustizia avvierà un monitoraggio per valutare se la sperimentazione della procedura di mediazione ha funzionato. Speriamo che intanto la “cultura della mediazione” cominci a diffondersi anche in Italia.
Keywords: ADR; Conciliation; Conciliazione; MARC; MARD; Mediación; Mediation; Mediazione; Mediação; Médiation

Arbitration in administrative contracts : comparative law perspective - Lin, Ching-Lang (Institut d'études politiques, 2014)
Il a été longuement discuté de savoir si le système d'arbitrage est applicable pour régler les litiges administratifs qui concernent certains contrats administratifs ou d’autres sans rapport avec le contrat administratif. Dans cette thèse, les trois questions spécifiques sont analysées tour à tour : (1) Est-il possible pour un arbitre ou un tribunal arbitral de trancher des questions relevant du droit administratif? (2) Y a-t-il, ou devrait-il y avoir, des limitations à l'autorité des arbitres et des tribunaux arbitraux? (3) Enfin, après la délivrance d'une sentence arbitrale, quel rôle devrait jouer l'État dans la phase de contrôle judiciaire? La première question concerne l'arbitrabilité et a été discutée dans la première partie (FIRST PART: ARBITRABILITY). La deuxième question a été discutée dans la deuxième partie (SECOND PART: PARTICULAR QUESTIONS OF ADMINISTRATIVE MATTERS IN ARBITRATION PROCEDURE). Enfin, sur la dernière question a fait l’objet d’une troisième partie (THIRD PART: JUDICIAL REVIEW AND EXECUTION OF ARBITRATION AWARD). Dans cette thèse, nous avons comparé les systèmes de quatre pays (Canada, Chine, France, Taïwan). En conclusion, nous pouvons donc conclure que l’évolution de la conception du contrat administratif implique de nombreux aspects, y compris les aspects juridiques, économiques, politiques et même culturels. Le développement de la fonction de contentieux administratif, comme ‘’subjectivement orienté" ou "objectivement orienté" aura une incidence sur l'acceptation de l'arbitrage en matière administrative. Dans l'ensemble, l'arbitrage sera plus acceptable dans les systèmes dont la fonction est plus ‘’subjectivement orientée" que dans ceux dont la fonction est "objectivement orientée". While arbitration has traditionally been considered as a means to resolve private disputes, its role in disputes involving administrative contracts is a crucial question in administrative law. In brief, the three specific questions are (1) Can arbitrators or arbitral tribunals decide issues involving administrative law? and (2) Is there, or should there be, any limitation on the authority of arbitrators or arbitral tribunals? (3) Moreover, after the issue of an arbitration award, what role should the State play in the judicial review phase? The first question, the issue of arbitrability, is discussed in part 1 (FIRST PART: ARBITRABILITY). The second question will be discussed in part 2 (SECOND PART: PARTICULAR QUESTIONS OF ADMINISTRATIVE MATTERS IN ARBITRATION PROCEDURE). Finally, on the question of what happens after the arbitration award, we will discuss judicial review in part 3 (THIRD PART: JUDICIAL REVIEW AND EXECUTION OF ARBITRATION AWARD). We compare legal systems between the four countries: in France, in Canada, in China and in Taiwan. We believe that an administrative contract, at least in its function and conception, is gradually becoming different from a private contract. Innovation with respect to administrative contracts will also reflect the concentration and function of the administrative litigation systems in each country. In addition, the “objective” or “subjective” function of administrative litigation will also affect the degree of arbitrability, as well as arbitration procedures. Taken together, arbitration will be more acceptable in systems whose function is more “subjectively oriented” than in those whose function is “objectively oriented". Finally, “the arbitration of administrative matters” traditionally has been an important question in administrative and arbitration law. In the future, we will continue to see it shine in the doctrine and jurisprudence of both the administrative and arbitration law fields.
Keywords: Administrative litigation system; Arbitrability; Arbitrabilité; Arbitrage; Arbitragem; Arbitration; Arbitration award; Contentieux administratif; Contrats administratifs (exécution); Judicial review; Litige; Légalité objective; Objective and subjective function; Prerogative of administrations in contracts; Sentence arbitrale (contestation); Études comparatives

Imparcialidade dos árbitros - Elias, Carlos Eduardo Stefen (Universidade de São Paulo, 2014)
O presente estudo tem como objetivo superar as diversas noções genéricas a respeito da imparcialidade do árbitro e assim atribuir-lhe um conceito próprio, estabelecido a partir do reconhecimento da vital importância do exercício da influência das partes na relação jurídica processual. O estudo parte da premissa de que todas as experiências pretéritas do árbitro (como as de qualquer indivíduo) constituem condição necessária para que este forme pré-conceitos e assim conheça e decida um conflito e que, por isso, tais experiências e conceitos pretéritos sempre existem e sempre influenciam o julgador. Também é premissa de análise o ambiente institucional em que a arbitragem se desenvolve e no qual os profissionais buscam auferir capital simbólico que lhes possibilite êxito nas nomeações para a função de árbitro. Essas premissas impedem que se aprove a noção genérica da imparcialidade como equidistância, ausência de interesse próprio na solução do litígio ou ausência de outras influências no convencimento do árbitro além dos argumentos lançados pelas partes no litígio, e impõem o reconhecimento de um conteúdo apoiado na inexistência de barreira à influência que os argumentos das partes exercerão na decisão do árbitro (a despeito, portanto, de quaisquer outras influências às quais o julgador como todo indivíduo está sujeito). A identificação de um conteúdo para a imparcialidade é, todavia, insuficiente para a solução de problemas práticos, razão pela qual o presente estudo sugere sua operacionalização por norma concreta extraída de regras vinculantes que imponham um comportamento (art. 14, caput, da Lei de Arbitragem brasileira) ou um estado de coisas (art. 13, § 6º da Lei de Arbitragem brasileira) que atenda a certas premissas de estrutura e de conteúdo. As premissas de estrutura têm como finalidade garantir a coerência e coesão sistemáticas da norma concreta, ao passo que as premissas de conteúdo (extraídas de casos reais) buscam a coerência interna da norma, ou seja, a coerência entre o juízo hipotético-normativo e o juízo sobre o evento fático subjacente. Essas premissas são examinadas à luz do ambiente institucional no qual a arbitragem se desenvolve, caracterizado principalmente pela interdependência e contínuo contato entre profissionais, a constante troca de papéis a que tais profissionais se sujeitam (ora como árbitros, ora como advogados) e a assimetria de informação. Propostos um conteúdo e um método de operacionalizá-lo para a solução de casos concretos, o presente estudo procura desatrelar a imparcialidade e seus efeitos da noção geral de independência do árbitro, sem apelar para a imprecisa dicotomia subjetividade-objetividade. Reconhece, ainda, que do árbitro são demandadas posturas diferentes daquelas preconizadas aos juízes, razão pela qual a aplicação de regras equiparativas (tal como o art. 14, caput, da Lei de Arbitragem brasileira), além de não esgotar todas as hipóteses de ataque à imparcialidade, deve ser precedida de diversas adaptações. Reconhece, também, o sentido e o alcance do binômio ciência-aceitação na prática arbitral. Por fim, o estudo trata da diversa natureza entre o dever de revelação e a imparcialidade impostos ao árbitro, de cujas violações derivam consequências também distintas. The present study aims to overcome several general notions concerning the impartiality of the arbitrator and thus gives it a proper concept, drawn from the recognition of the vital importance of parties to exercise influence on the procedural legal relationship. The study assumes that all past experiences of the adjudicator (as any individual) constitute a necessary condition for him to create pre-conceptions and so understand and decide a conflict - and that therefore these experiences and past concepts always influence the adjudicator. The institutional environment in which the arbitration is developed and in which practitioners seek to derive symbolic capital that enables them to succeed in the nominations for the role of arbitrator is also a premise of analysis. This premise prevents from approving the generic notion of impartiality as "equidistance", "the absence of self-interest in the outcome of the case" or "the absence of other influences in the convincing process of the adjudicator beyond the arguments submitted by the parties in dispute", and requires the recognition of content based on the "absence of barriers to the influence that the arguments of the parties shall exercise on the arbitrator's decision" (regardless of any other influences to which the judge as any individual is exposed). Identifying content for impartiality is, however, insufficient for the solution of actual problems, and due to that, the study suggests its operation by a norm extracted from binding rules imposing conduct (art. 14, caput of Brazilian Arbitration Law) or a state of affairs (art. 13, § 6 of the Brazilian Arbitration Law) that meets certain premise of structure and content. The premise of structure is designed to provide systematic consistency and cohesion of the norm, and the premise of content (drawn from actual cases) seeks internal consistency of the standard, i.e., the consistency between the description of the event anticipated in the norm and the description of the underlying factual event. This premise is examined in the light of the institutional environment in which the arbitration is developed, mainly characterized by interdependence and continuous contact between professionals, the constant exchange of roles among such professionals (either as arbitrators or as lawyers) and information asymmetry. Proposed both a content and a method to operationalize it for the solution of actual cases, this study seeks to release fairness and its effects from the general notion of independence of the arbitrator, without resorting to imprecise objectivity-subjectivity dichotomy. It also recognizes that the institutional environment requires postures from the arbitrators that differ substantially from those required from judges; due to this reason, the application of rules that apparently prescribe the same standards or behaviors for both (such as art. 14, caput, the Brazilian Arbitration Law) does not fill all the hypothesis capable of menacing the impartiality and must be preceded by various adaptations. It also recognizes the meaning and scope of the binomial information-acceptance in arbitral practice. Finally, the study addresses the diverse nature of the duty of disclosure and impartiality imposed on the arbitrator, whose respective violations also imply different consequences.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; Arbitre; Civil Procedure; Due process; Impartiality; Impartialité

L’internationalisation du droit public des affaires face à l'arbitrage international : approche comparée en droit franco-maghrébin - Baisset, Didier (Annales de l’Université d’Alger, 2014)
Indiscutablement la sphère du droit public des affaires se déploie aujourd'hui dans un espace mondialisé, où les rapports entre les opérateurs se nouent en des termes qui différent radicalement de ceux qui posèrent les premiers linéaments de la matière au début du XXe siècle. Cela est en réalité lié aux tendances de fond qui touchent le monde contemporain. C'est donc dans un contexte profondément modifié par la globalisation, que les relations d'échanges internationaux et les litiges auxquels elles peuvent donner lieu s'envisagent désormais. On assiste ainsi, depuis déjà plusieurs décennies, à l’émergence d’un véritable droit public international des affaires. A cet endroit, le cas des marchés publics et des partenariats public-privé internationaux est particulièrement révélateur des mutations profondes qui taraudent la matière au niveau international. En effet, l'internationalisation des échanges économiques s'inscrit dans une réalité qui modifie en profondeur l'organisation des acteurs économiques et opère une vaste mutation des modalités d'intervention de la puissance publique; elle se fait maintenant dans un champ économique à l'échelle supra-nationale.

La participation à l'arbitrage des personnes morales de droit public : L’exemple de l’OHADA - Fénéon, Alain (Annales de l’Université d’Alger, 2014)
Dans beaucoup de législations nationales sur l’arbitrage, le principe de la non-arbitrabilité des litiges impliquant les personnes morales de droit public, en particulier l’Etat et les collectivités territoriales, est clairement posé, et ce depuis longtemps. Cette position s’explique aisément dans le système juridique français comme dans ceux qui s’en inspirent. La distinction entre la justice des particuliers et celle de l’administration, c’est à-dire de l’Etat, y est fermement établie.

Arbitrage en droit, arbitrage en équité : perspectives historiques - Juhel, Christophe (Annales de l’Université d’Alger, 2014)
L’expression « modes alternatifs de règlement des conflits » en vogue depuis quelques années et reprise dans l’intitulé de ce colloque est trompeuse. Elle procède d’une vision ethno-centrée moderne et plus spécifiquement occidentale et continentale du règlement des conflits. En effet, le qualificatif « alternatif » est employé par référence au mode de règlement des conflits actuellement privilégié par les sociétés modernes, notamment de la famille romano-germanique: la justice étatique. Or, historiquement, les sociétés traditionnelles les plus anciennes ne connaissaient pas de justice publique mais seulement des modes traditionnels et privés de résolution des litiges pacifiques comme la médiation, la conciliation et l’arbitrage, c’est-à-dire ceux que nous désignons « modes alternatifs de règlement des conflits », ou non pacifiques comme la vengeance privée.

Assessment Report of Arbitration Centres in Côte D’ivoire, Egypt and Mauritius - ORPF (African Development Bank, 2014)

Étude des règles d'indemnisation du préjudice dans l'arbitrage international : vers une indemnisation adéquate du préjudice - Mohamed Gamaleldin, Hossam (Université Paris 1, 2014)
Le recours à l'arbitrage par les opérateurs du commerce international a une finalité très importante, qui est celle de l'indemnisation appropriée et efficiente du préjudice. En vue d'évaluer celle-ci, notre étude adopte une recherche juridique détaillée en matière de réparation pour aboutir à un résultat satisfaisant concernant le principe le plus adapté en tant que cadre commun de l'opération d'évaluation de l'indemnisation du préjudice par les arbitres internationaux, en mettant notamment la lumière sur l'arbitrage CIRDI et CCI. À cette fin, il était nécessaire de suivre une analyse juridique tant sur les règles fondamentales que contingentes de l'indemnisation dans le souci d'avoir une perspective entière du processus de l'évaluation du quantum du préjudice. Un passage transversal était ainsi inéluctable sur les règles juridiques relatives à la réparation en droit privé français ainsi qu'en système juridique de Common Law. Au demeurant, un examen sur la codification de ces règles a été suivi dans le cadre des instruments internationaux de droit uniforme. Toutes ces réglementations ont inspiré le droit de l'arbitrage et ont servi comme des sources de celui-ci en matière de la réparation. Ces développements nous ont conduits à percevoir que l'indemnisation doit être adéquate en prenant en compte non seulement les préjudices subis, conformément au principe général de l'indemnisation intégrale, mais aussi tous les intérêts lésés. Sachant que certains préjudices ne sont pas mathématiquement évaluables, une indemnisation arbitraire s'impose dans ce cas. Un nouveau concept d' « indemnisation adéquate» du préjudice pourrait alors dans l'avenir s'imposer dans le droit de l'arbitrage international.
Keywords: Adequate compensation; Arbitrage international; Damages suffered; Dommages-intérets; Full compensation; Indemnisation adéquate; Indemnisation intégrale; International arbitration; Intérêts lésés; Mercatoria; Prejudices; Process of the evaluation; Processus d'évaluation; Préjudices; Règles d'indemnisation; Réparation (droit international)

L’arbitrage, une justice citoyenne, émancipée et pragmatique - Raibaut, Jacques (Académie de Législation, 2014)
Keywords: ARBITRAGE; Arbitration

Alternative Dispute Resolution (ADR): An Overview of Some Common Mechanisms, and their Strengths and Weaknesses in Context - Perrin, Harry (The Plymouth Law & Criminal Justice Review, 2014)
Alternative Dispute Resolution, or ’ADR’, offers parties in dispute an alternative to traditional court-based litigation, which is often seen as slow, costly and ineffective. ADR frequently involves a neutral third party who will settle or facilitate resolution of the dispute. This paper examines three common ADR mechanisms, adjudication, arbitration and mediation, and explores their relative advantages and disadvantages in different contexts.
Keywords: ADR; Adjudication; Alternative dispute resolution; Arbitration; Construction adjudication; Mediation; Negotiation

Mediation advocacy - Shaw, Annabel (Victoria University of Wellington, 2014)
Mediation has been a part of New Zealand’s employment statutory framework in one form or another for over a century, and has been the first port of call for employment disputes under the current Employment Relations Act for nearly 15 years.¹ I have been working as a mediator in this context for almost seven years in more than 1,000 mediations. Lawyers are playing a significant part in the field of mediation, with a large number representing clients in this forum on a regular basis. In an evaluation of 100 of my mediations over a ten-month period, 85% of parties were legally represented. This rate is consistent with anecdotal reporting across the employment mediation service. Lawyer representation in mediation is not unique to the employment context. There are various mediation schemes provided for under many New Zealand statutes as well as a wide raft of non-statutory mediation occurring in numerous settings. In my experience as a mediator with human rights and leaky building mediations, as well as working as a lawyer in a large commercial law firm, I am aware lawyers are representing clients in many other areas of mediation as well. Although there is a significant amount of mediation occurring and a large number of lawyers regularly appearing in mediation, my experience is that the majority of lawyers act in mediation as if they were in litigation and take an adversarial approach. My thesis is that lawyers have not adapted effectively to mediation and taken on the role of mediation advocacy. This paper explores the topic by first describing, in Part II, what I observe as lawyers’ adversarial approach in mediation. It then looks at other research to assess whether this experience is reflective of a wider issue. It finds there is evidence to support my observations. Part III analyses why lawyers are operating in an adversarial way in mediation and proposes several reasons this may be the case. Part IV puts forward what I propose is appropriate mediation advocacy. It sets out the knowledge, roles and skills required from lawyers when representing clients in mediation. Part V suggests what might be done to assist a shift away from the common, adversarial approach to effective mediation advocacy. This paper is written within the context of employment mediation in New Zealand. However, it draws on research from different jurisdictions and areas of practice so the conclusions it comes to may have more general application. The topic is not whether lawyers should be in mediation. I am not arguing that lawyers do not have a part to play in mediation. A lawyer well versed in mediation advocacy can play a highly effective part in the process. Leonard Riskin, one of the key authors on the topic of lawyers in mediation, expresses this even more strongly, saying he believes lawyers’ involvement is fundamental to mediation’s success.² Further, this paper is focused on lawyers representing parties in mediation and does not consider lawyers as mediators.
Keywords: Advocacy; Dispute resolution; Employment disputes; Lawyers; Mediation

Dispute resolution in transnational securities transactions - Andreotti E Silva, Tiago (European University Institute, 2014)
This PhD thesis explores how the legal infrastructure for dispute resolution in transnational securities transactions can be improved, considering the regulatory and legal limits of the financial sector in each jurisdiction under study (US, Europe and Brazil). The two main objectives of the work are to a) identify the problems that currently exist for a dispute resolution mechanism in the securities area that can be used transnationally and b) propose solutions that can create a safe legal environment that can be used by the investor in case regulatory rules or the terms of the transaction are breached. The work is justified by the fact that financial markets are legal constructions, making legal certainty and the mechanisms available to enforce the terms of a transaction and apply regulatory rules, especially to the investor that is part of the transaction, essential for the own existence of financial markets. Therefore, the existence of transnational financial markets also depends on the existence of a transnational legal infrastructure, at least broad enough to protect the interest of investors. The argument developed through the work is that the creation of a transnational legal infrastructure depends on the type of dispute that is considered, since not only each type of dispute has its own peculiarities, but the national dispute resolution systems are also built based on the type of dispute that will be submitted to it. To create transnational dispute resolution systems for securities transactions, I propose the use of collective mechanisms of dispute resolution based on the initiative of private parties, the use of arbitration and the establishment of cooperation networks among national alternative dispute resolution mechanisms used to solve financial disputes.
Keywords: Dispute resolution (Law); Financial market; International finance; Security (Law)

L’arbitrage OHADA - Kenfack Douajni, Gaston (Droit OHADA et droits communautaires africains, 2014)
L’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) a été créée par le Traité de Port-Louis (Ile Maurice) le 17 octobre 1993, modifié à Québec (Canada) le 17 Octobre 2008. L’OHADA a pour but de promouvoir les investissements dans ses 17 États parties à travers la sécurisation juridique et judiciaire de l’environnement des affaires, par la production de normes juridiques, simples, adaptées et modernes en droit des affaires, au nombre desquelles les instruments relatifs à l’arbitrage. Premier ouvrage de la collection droits OHADA et droits communautaires africains, l’Arbitrage OHADA procède à une présentation synthétique et à une analyse exhaustive des instruments OHADA relatifs à l’arbitrage, que sont l’Acte uniforme relatif au droit de l’arbitrage et le Règlement d’arbitrage de la Cour commune de justice et d’arbitrage de l’OHADA (Règlement CCJA). Outre les textes normatifs posant les bases de l’arbitrage OHADA, cet ouvrage met aussi à la disposition du lecteur la jurisprudence de la CCJA et commente les premières applications pratiques de l’arbitrage OHADA. Il est en cela indispensable à tous les praticiens de l’arbitrage OHADA. Mais au-delà, par la réflexion qu’il développe sur les difficultés rencontrées et les espérances suscitées par la mise en œuvre de l’arbitrage OHADA et – en définitive – sur l’apport de l’arbitrage dans le développement du droit OHADA et l’amélioration du climat des affaires en Afrique, cet ouvrage intéresse un public bien plus vaste (Universitaires, Barreau, Magistrature, Opérateurs économiques) et est appelé à constituer la référence en matière d’arbitrage pour l’ensemble des usagers du droit OHADA.
Keywords: Arbitrage; Arbitragem; Arbitration

L'arbitrage maritime : une étude comparative entre Londres et Paris - Khaldi, Jihane (Aix-Marseille Université, 2014)
Keywords: Arbitrage; Arbitration

Les modes alternatifs de règlement des conflits : à la recherche d'une clé d'accès à la justice administrative congolaise - Nyaluma Mulagano, Arnold (Université Catholique de Louvain, 2014)
L'accès au juge de l'administration est un droit consacré par les textes nationaux et internationaux au profit de tout administré congolais. L'effectivité de ce droit reste néanmoins aléatoire. A chaque étape de la procédure, le justiciable rencontre des difficultés énormes, parfois infranchissables. Les MARC comportent-ils une réponse à cette crise ? L'assertion de départ était tentante : l'Afrique étant reconnue comme une terre du règlement négocié, l'on a pris comme hypothèse de travail que le vent planétaire favorable aux MARC pourrait trouver, en droit administratif congolais, un terrain de prédilection. Le contrôle juridictionnel de l'administration congolaise est effectué par les juridictions de l'ordre administratif et les juridictions de l'ordre judiciaire, civiles et militaires. La Constitution du 18 février 2006 a instauré un ordre autonome de juridictions administratives. En attendant leur installation effective, le contentieux administratif relève, à titre transitoire, de sections incorporées au sein des juridictions de l'ordre judiciaire. Le texte actuellement en vigueur n'organise que la procédure devant la section administrative de la Cour suprême de justice. Le juge administratif intervient, à titre principal, dans le contentieux de légalité et, à titre subsidiaire, dans le contentieux d'indemnités. Il est également doté du pouvoir de contrôler l'acquisition et l'exercice des mandats publics. Les juridictions judiciaires se répartissent entre les juridictions de droit commun et les juridictions militaires. Les juridictions civiles interviennent principalement dans la mise en jeu de la responsabilité de l'administration et exceptionnellement dans le contrôle de la légalité des actes des autorités administratives. Le juge militaire connaît de la responsabilité de l'administration à l'occasion de la répression des infractions commises par les militaires et les policiers. Les constats réalisés dans la présente étude permettent d'affirmer que le contrôle juridictionnel de l'administration congolaise constitue une justice marginale, éloignée du citoyen et rejetée par lui. La défaillance des acteurs judiciaires, les carences institutionnelles et les inadéquations normatives éloignent la justice administrative congolaise des missions élémentaires de service public qu’elle devrait pourtant assumer. Les décisions de justice souffrent d'une faible qualité et d'une inexécution chronique. Tout ceci disqualifie le recours juridictionnel et dévalorise la notion de légalité. La médiation institutionnelle, la médiation processuelle, la conciliation et l'arbitrage constituent-ils une réponse à ces difficultés ? Alors que l'Afrique est réputée terre de MARC, c'est plutôt en Belgique qu'ils se développent. La médiation institutionnelle y joue un rôle régulateur incontestable. Par contre, le régime de la médiation processuelle reste peu incitatif. L'habilitation légale imposée au sujet des personnes morales de droit public ne permet pas l'éclosion de ce MARC en droit administratif belge. L'habilitation légale est également requise pour la participation de l'administration à la conciliation. Cette habilitation est intervenue à maintes reprises. Les cas étudiés démontrent une faible contribution de la conciliation aux litiges ponctuels. Elle semble mieux convenir aux litiges des masses dont les faits sont incontestés. En droit public belge, l'arbitrage est limité aux litiges contractuels. L'arbitrabilité des litiges extra-contractuels est soumise à une habilitation légale. La modification intervenue pour étendre le régime d'arbitrage à l'ensemble du litige contractuel et non plus seulement aux différends relatifs à l'élaboration ou à l'exécution ne suffit pas à lui assurer une grande efficacité. En règle générale, l'hésitation du législateur belge s'explique par le succès du juge de l'administration. La R.D.C. figure parmi les rares pays africains qui ignorent l'institution d'Ombudsman. La médiation traditionnelle à travers la palabre africaine a été évincée par l'administration coloniale et post-coloniale. Par contre, la conciliation se développe en droit administratif depuis les années 2000. Chaque nouveau texte réserve un espace à la conciliation. Longtemps cantonné au droit privé et aux litiges internationaux, l'arbitrage apparaît progressivement dans certains secteurs du droit administratif congolais à partir des années 2000. L'adhésion de la R.D.C. à l'OHADA consolide l'arbitrabilité des litiges impliquant l'administration. L'environnement socio-juridique congolais semble ainsi ouvert aux MARC. Il s'observe, en outre, une convergence favorable de la jurisprudence, de la doctrine et des acteurs politiques. Leur efficacité devant les difficultés d'accès à la justice administrative congolaise reste néanmoins sujette à caution. En l'absence d'une volonté de transparence administrative, il est à craindre que la tendance favorable au règlement négocié ne conduise à l'instauration de MARC en trompe l'œil, sans impact réel sur les difficultés d'accès à la justice administrative congolaise. Au terme de cette étude, il apparaît que la perspective d'un meilleur accès à la justice administrative passe plutôt par une alternative citoyenne. Celle-ci semble distiller des vertus susceptibles de favoriser l'implémentation des MARC et la rationalisation du contrôle juridictionnel de l'administration congolaise. La justice citoyenne préconisée dans cette thèse désigne la faculté pour l'administré et l'agent public de régler directement leur conflit sans s'en référer à l'appareil judiciaire. Elle repose sur deux piliers : la défiance et le dialogue. La justice citoyenne alimente la responsabilité et l'émancipation des citoyens. Les réponses inventées par les citoyens et les agents publics révèlent une véritable résilience qui augure une perspective intéressante pour l'accès à la justice administrative congolaise. Apprivoiser et intégrer cette justice pragmatique dans le giron de la justice étatique devrait ouvrir des horizons nouveaux pour les justiciables congolais. L'interaction entre ces MARC et le contrôle juridictionnel devrait faire bouger les lignes et générer ainsi une certaine amélioration de la justice administrative. En examinant la question au départ d'initiatives citoyennes, la thèse réinterroge le paradigme dominant dans la réforme de la justice en RDC et dans les Etats qui partagent le même contexte.
Keywords: Accès à la justice; Administration; Arbitrage; Arbitragem; Arbitration; Congo (République démocratique); Décision; Justice administrative; MARD; Mediación; Mediation; Mediação; Modes alternatifs; Médiation; Palabre africaine; RDC

Les contours de l’arbitrage - Posocco, Laurent (La Lettre, 2014)
Les frais d’arbitrage peuvent compromettre l’accès au juge. L’exclusion de l’arbitrage comme méthode de recours à l’encontre d’une ordonnance du juge commissaire. Il ne revient pas aux parties d’apprécier la nature interne ou internationale de l’arbitrage.
Keywords: ARBITRAGE; Arbitration

L'arbitre et le droit - Prujiner, Alain (Revue de règlement des différends de McGill, 2014)
L’auteur se penche sur la relation qui existe entre l’arbitre et le droit, en focalisant sur les questions de procédure et de droit applicable au fond du litige en arbitrage international. L’auteur montre que les arbitres ne se réfèrent plus automatiquement au droit international privé de l’Etat du siège afin de déterminer le droit applicable à la procédure ou au fond du litige, ni même au droit international privé d’un Etat en particulier. Au contraire, l’auteur avance que la tendance est à l’internationalisation des règles de droit international privé : l’arbitre puise directement les règles de rattachement d’un ordre juridique transnational autonome, qui dispose de ses propres règles de droit international privé, tant pour le fond du litige que pour la procédure arbitrale. The author addresses the relationship between the arbitrator and the law, with an emphasis on the law and procedure that is applicable to international arbitration. It is demonstrated that arbitrators no longer automatically refer to the private international law of the state that is the seat of arbitration to determine the applicable law, nor to private international law rules of a particular country. On the contrary, there is a trend towards internationalizing the rules of private international law: the arbitrator obtains the governing law directly from an autonomous transnational legal system that has its own substantive and procedural rules in private international law.

Mediación mercantil. Mediación mercantil empresarial - Rojas Roldán, María de la Encarnación (Universidad Internacional de Andalucía, 2014)
Trabajo de Curso de Experto Universitario en Mediación Civil, Familiar, Mercantil y Organizaciones Complejas (2013). Tutora: María Sonia González Ortega. El objetivo del presente trabajo es abordar la Mediación en el seno de las organizaciones, teniendo en cuenta que estas constituyen sistemas de interrelación entre personas, donde confluyen numerosos intereses. Se trata por tanto, de abordar la resolución de los problemas no solo existentes sino de los emergentes, aportando herramientas eficaces en el desarrollo de la actividad empresarial, que permitan gestionar y modular los conflictos, de forma que los mismos, se transformen en oportunidades de mejora y de crecimiento empresarial.
Keywords: Mediación; Mediation; Médiation

Le consentement dans l'arbitrage des litiges sportifs - Yamdjie, Elie (Université de Nice Sophia-Antipolis, 2013)
Le consentement dans l’arbitrage des litiges sportifs témoigne des mutations profondes que subissent les piliers du droit dans le domaine économique. L’unilatéralisme visible des puissances sportives supplante nettement le bilatéralisme où, en principe, la fusion paisible des volontés donne naissance aux conventions. Mus par la recherche de l’efficience, les pouvoirs privés sportifs s’emparent du consentement, le mettent résolument à leur service au point que leur arbitrage se rapproche plutôt du sens qu’y donnent les économistes. La convention issue de ce consentement rime plutôt avec les contrats économiques. L’automaticité des effets liés à ce consentement nie à l’arbitrage ainsi institué le minimum de légitimité dont il a besoin. Le juge du for en a enfin pris conscience et c’est heureux ! Mais c’est sur les arbitres du TAS que repose le plus grand travail nécessaire à sa légitimation.
Keywords: ABUS; Acceptation; Arbitrage; Arbitragem; Arbitraje; Arbitration; Litiges; Règlement de conflits; Sports; Tribunal arbitral du sport

Arbitrating and Mediating Disputes: Benchmarking Arbitration and Mediation Regimes for Commercial Disputes Related to Foreign Direct Investment - Pouget, Sophie (World Bank, 2013)
An effective commercial arbitration regime matters for foreign investors. It gives parties the autonomy to create a dispute resolution system tailored to increasingly complex disputes. Foreign investors view arbitration as a way to mitigate risks by providing legal certainty on enforcement rights, due process, and access to justice. The Arbitrating and Mediating Disputes indicators assess the legal and institutional framework for commercial arbitration, mediation, and conciliation regimes in 100 economies. All surveyed economies recognize arbitration as a tool for resolving commercial disputes and only nine economies have not acceded to the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards. In the Arbitrating and Mediating Disputes indicators, High Income OECD and Eastern Europe and Central Asia are the regions that reformed their laws on alternative dispute resolution the most between 2011 and 2012. The data also show that, globally, arbitration proceedings take 326 days on average, while recognition and enforcement proceedings of foreign arbitral awards take 557 days on average. The Arbitration and Mediating Disputes indicators are significantly correlated with perception data on the importance of alternative dispute resolution, as well as other measures such as total foreign direct investment inflows and inflows per capita, the Doing Business 2013 Enforcing Contracts data, the World Bank Group's Governance Indicators, the World Economic Forum's Global Competitiveness Indicators, and the Multilateral Investment Guarantee Agency's World Investment and Political Risk data. The paper concludes by identifying several opportunities for improvement, such as greater flexibility for domestic arbitration regimes, faster arbitration proceedings, and better domestic court capabilities.

Arbitrage commercial international et développement : étude du cas des États de l’OHADA et du Mercosur - Yougoné, Franck Nicéphore (Université Bordeaux 4, 2013)
L’OHADA et le Mercosur sont deux organisations régionales qui ont été créées afin d’accentuer l’intégration et de favoriser la sécurité judiciaire et juridique pour les opérateurs du commerce international. En d’autres mots, leur objectif est d’aider au développement économique des pays membres. Dès le fonctionnement de ces deux organisations, le recours à l’arbitrage a été privilégié comme mode de règlement des différends liés au commerce international. Partant de là, il nous est apparu envisageable d’établir un lien entre la notion de développement et celle arbitrage commercial international. Presque vingt ans après la création de l’OHADA et du Mercosur, cette étude se propose d’évaluer les liens entre l’arbitrage et le développement. Cette évaluation se base sur l’observation de l’influence de l’arbitrage sur le processus d’intégration et sur l’apport de cette technique aux efforts d’amélioration de la sécurité judiciaire et juridique dans le milieu du comme international.
Keywords: Alignment; Arbitrage; Arbitrage commercial international; Certainty; Commerce international; Damage; Development; Dommage; Développement; Harmonisation; Integration; International commercial arbitration; Intégration; Investissements; Investments; Judicial security; Mercado común del Sur; Organisation pour l'harmonisation en Afrique du droit des affaires; Repair; Réparation; Sécurité judiciaire; Sécurité juridique; Uniform; Uniformisation

Les Preuves dans l'arbitrage international - Richani, Joseph (Université de Cergy Pontoise, 2013)
L'arbitrage est un mode de résolution des litiges par l'intermédiaire d'un tribunal arbitral composé d'un ou plusieurs arbitres. Il permet, comme devant les tribunaux étatiques, de régler un litige en vertu d'une sentence rendue à l'issue d'une procédure arbitrale dans laquelle chacune des parties doit prouver ce qu'elle allègue afin d'établir la conviction des arbitres. C'est par le recours aux divers modes de preuve inspirés des différents systèmes juridiques notamment du système de Common Law et du système de droit civil que les plaideurs pourront atteindre cette finalité.En revanche, parce que l'arbitrage international ne possède ni for ni législation spéciaux, l'administration des preuves dans une instance arbitrale internationale revêt un caractère sui generis de fait que l'arbitrage international a reconnu un système de preuve qui a utilisé les avantages des divers systèmes juridiques. Ainsi, on retrouve que la preuve écrite, qu'elle soit sur support papier ou sur support électronique, est administrée selon le model civiliste qui donne la primauté à une preuve préconstituée à l'avance. Mais, en ce qui concerne la preuve par témoin, l'influence des droits de Common Law paraît claire surtout que dans la plupart des cas, le pouvoir de nommer et d'interroger les témoins revient aux plaideurs qui utilisent la méthode d'Examination lors de l'interrogation des témoins. C'est aussi le cas de l'expertise qui est souvent considérée comme une preuve orale dans laquelle il revient aux parties le pouvoir de désigner les experts et de les interroger suivant l'interrogatoire direct et le contre interrogatoire tout comme des témoins. Ainsi, les preuves dans l'arbitrage international peuvent être reparties en preuves écrites et preuves orales dont les premières sont constituées de l'écrit sur support papier ou sur support électronique et les secondes sont formées par la preuve par témoin et la preuve par expertise. The arbitration is a method of resolving disputes through an arbitration tribunal composed of one or several arbitrators. He allows resolving a dispute under a sentence delivered after an arbitration procedure in which all parties have to prove what they adduce to convince the tribunal. It is by using various modes of proof inspired specially from the system of Common Law and the system of Civil Law that parties can achieve this purpose.On the other hand, because the international arbitration has neither a territory nor legislation, it was created a system which combines between best practices of Common Law and Civil Law. So, the written evidence is produced according to the practice of Civil Law which gives primacy to a proof written in advance. But for the oral testimony, it is the common Law which dominates the administration of this proof by giving parties the right to nominate and interrogate witnesses. This is also what happens when arbitrators decide to use an expertise in which the parties have the power to nominate experts and interrogate them as witnesses. So, the evidence in international arbitration can be divided into written evidence made up by the writing on paper medium and electronic medium and oral evidence formed by proof by witness and proof by expertise.
Keywords: Act; Acte; Arbitrage; Arbitrage international; Arbitragem; Arbitration; Evidence; Expert; International Arbitration; Preuve; Temoin; Witness

The Enforcement of Arbitral Awards in Cameroon - Tumnde, Taylor (Social Science Research Network, 2013)
The increase in international trade creates a growing number of disputes between parties from different countries. Arbitration has become the most preferred mechanism to solve disputes in international trade. If a party does not voluntarily comply with an award, the successful party must apply for recognition and enforcement of the award in order to obtain the remedies. Cameroon is one of the major business markets in West and Central Africa, several companies committed to arbitral procedures are likely to have assets in Cameroon. This means that if a party fails to honour an award, an enforcement procedure may begin within a Cameroonian court. The enforcement procedures in Cameroon are sufficient and do comply with international standards. The most used and important instruments for recognition and enforcement are the United Nations Convention on the Recognition and Enforcement of Foreign Arbitral Awards of 1958 and the Uniform Act on Arbitration 1999 in the OHADA territory, to which Cameroon is a signatory State. According to this Convention and the Uniform Act, an arbitral award may be refused enforcement under certain grounds laid down in them. There are various types of arbitral awards contemplated by the Cameroonoan legislature and will be herein examined to see how they can be enforced in Cameroon. An analysis of the legal situation in Cameroon confirms that there are problems associated with the enforcement of arbitral awards. These problems are not, however, connected with the concept of arbitral awards, but rather with the entire judicial system in Cameroon. Even though an enforcing party can do little to overcome these problems, certain measures can be taken in order to ease the enforcement procedure
Keywords: Arbitrage; Arbitragem; Arbitral Awards; Arbitration; Cameroon; Enforcement; OHADA

A comparative study of law and practice of arbitration in Kenya, Nigeria and Zimbabwe, with particular reference to current problems in Kenya - Torgbor, Edward Nii Adja (Stellenbosch University, 2013)
Arbitration as a mode of dispute settlement has been growing steadily all over the world. The momentum for commercial arbitration in particular was provided by the 1985 UNCITRAL Model Law on International Commercial Arbitration (“the Model Law”). Legislation based on the Model Law has been enacted in many countries. The arbitration laws of three of these countries, Kenya, Nigeria and Zimbabwe, are selected for consideration in this dissertation because of their common origins, similar statutes, similar problems, shared experiences, and their regional distribution. As the writer’s arbitration practice is based in Kenya, that jurisdiction is the primary, albeit not the only, source and foundation for this work, the focal point of reference and the citations from the law and practice incorporated in this research. The work consists of three chapters. Chapter one is a brief introduction and an overview of arbitration. This is followed by the statement of the research question, the justification for the research, methodology and the structure and content of the dissertation. Chapter two describes the legal and contextual framework for the investigation of the research questions in the selected jurisdictions of Kenya, Nigeria and Zimbabwe. Customary Law arbitration is included as a significant feature of African arbitration law. The UNCITRAL Model Law, the Arbitration Act, 1995 (Kenya), the Arbitration and Conciliation Act, 1988 (Nigeria), the Arbitration Act, 1996 (Zimbabwe), the Arbitration Act, 1996 (England), and the South African Draft Arbitration Bill are all used as legislative or statutory points of reference in the discussion of the research questions. Chapter 3 contains the main focus of the dissertation in which six recurrent arbitration problems in Kenya are discussed in the context of domestic arbitration. The research investigates (i) the illusiveness of consent as the basis for consensual arbitration (ii) jurisdictional challenges (iii) the procedural powers of the arbitral tribunal (iv) the disruptive effect of adjournments and postponements on the arbitral process (v) constraints on the granting of interim relief and (vi) the enforcement of the arbitral award. Original, creative and innovative proposals in response to these problems include: the express legislative recognition of the manifestation of consent in both the verbal and written forms of the arbitration agreement, the use of the constructive dispute resolution technique, statutory recognition of customary law arbitration, the use of an expedited arbitration procedure, the award of exemplary and punitive damages in arbitration, a code of sanctions to facilitate the arbitration process, and a simplified method of enforcement and execution of the arbitral award. The dissertation concludes with reflections on the future of arbitration in Africa, and the need for modernization and harmonization of arbitration laws for peaceful resolution of disputes and serious conflicts across Africa. The aim of this study is best illustrated by a short story: In the early nineties there was a man, untrained in any known discipline, who strutted court corridors, trade centres and market places, carrying a placard advertising himself to lawyers, traders and marketers as “An Arbitrator and Private Judge”. He attracted business, charged a handsome percentage fee on the value of the claim, was duly paid, until officialdom caught up with him and put paid to his burgeoning career as “Arbitrator-Judge”. But the reckless enthusiasm spawned by his wit and imagination, and the idiosyncratic practices in dispute resolution persisted and are manifest in Kenyan arbitration culture today. The need to remove bad practices, avoidable impediments, and inefficiency in the arbitration culture of Kenya in order to make its procedures and processes more efficacious, is the heart of this study.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Comparative law; Dispute resolution; Kenya; Nigeria; Zimbabwe

L'exécution des sentences arbitrales étrangères selon la Convention de New York de 1958 - Al Mana, Ahmad (Université Paris 1, 2013)
L'arbitrage est devenu le mécanisme de règlement des différends dans les contrats internationaux. L'arbitrage international offre aux parties non seulement la possibilité d’éviter les juridictions étatiques, mais facilite également l'exécution internationale des sentences arbitrales. Dans ce cadre, la Convention de New York de 1958 sur la reconnaissance et l’exécution des sentences arbitrales étrangères constitue sans aucun doute le traité le plus important dans le domaine de l'arbitrage international, et a connu un succès remarquable au cours de sa ratification par 147 États. Cette étude apporte une analyse approfondie sur la mise en application et l’interprétation par les différentes juridictions des dispositions prévues par cette Convention, surtout en matière de reconnaissance et d’exécution des sentences arbitrales étrangères. Arbitration has become the dispute resolution mechanism in international contracts. International arbitration does not only offer to the parties the possibility of avoiding the States jurisdictions, it also facilitates the international enforceability of arbitral awards. In this respect, the New York Convention of 1958 on the Recognition and Enforcement of Foreign Arbitral Awards constitutes without a doubt the single most important treaty in the field of international arbitration, and has enjoyed remarkable success through its ratification by 147 States. This study presents a thorough analysis of the application and interpretation of the provisions, provided by the Convention, by different jurisdictions especially in the area of the recognition and enforcement of foreign arbitral awards.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitration; Contrats internationaux; Convention de New York; Convention de New York de 1958; Exécution (droit); L'atteinte à l'ordre public; L'exécution; L'immunité des États; L'inarbitrabilité; La reconnaissance; New York Convention of 1958; Recognition; Sentences arbitrales

Common Court of Justice and Arbitration: A Supranational Institution for the Administration of Commercial Disputes in Africa - Ogwezzy, Michael C. (Nordic Journal of Commercial Law, 2013)
Due to the expansion of business transaction across the globe, the private sector demands an adequate legal framework that is sufficiently clear, modern, predictable and transparent to permit investment with a sense of security. The Organisation for the Harmonisation of Business Law in Africa (Organisation pour l’harmonisation en Afrique du Droit des Affaires) is generally known by its French acronym OHADA. As long-standing idea, the foundation of the OHADA Treaty was first laid during a meeting of finance ministers of the members of the franc CFA1 area held in Ouagadougou, Burkina Faso, in April 1991. A group of experts, led by Senegalese Justice Keba Mbaye, was appointed to conduct a feasibility study on a form of legal collaboration designed to promote economic integration and attract investments.2 Identifying low investment as a major obstacle to economic growth, Keba Mbaye presented his report to the French-speaking African summit in Libreville, Gabon, in October 1992, recommending the creation of a supranational organization comprising the entire franc area. The recommendation was adopted and a steering committee of three experts were appointed and tasked with drafting an international instrument as well as identifying the areas of law to be harmonized. The OHADA was established through the treaty of Port Louis in Mauritius on 17th October, 19933 The treaty is open to any Member State of the Organization of African Unity (AU) as well as any other non-member of the AU invited to join with the common agreement of all the Member States.4 The OHADA has progressively become the common business law in anglophone and francophone African countries, taking the best from the civil law and the common law systems.5 The OHADA provides its Member States with 1) a single, modern, flexible and reliable business law adapted to each country’s economy; 2) arbitration as an appropriate and trustworthy way to settle disputes; and 3) an opportunity for training judges and judicial staff and ensuring their specialisation. In May 2003, the uniform OHADA business law came into force in the sub-Saharan African States of Benin, Burkina Faso, Cameroon, Central African Republic, Comoros, Congo, Ivory Coast, Gabon, Guinea, Guinea Bissau, Equatorial Guinea, Mali, Niger, Senegal, Chad, Togo and later the Democratic Republic of the Congo. The OHADA Treaty secures a legal framework for the conduct of business in Africa.6 Pursuant to Article 53 of the OHADA Treaty, any member State of the African Union may become a member, if it wishes to do so.7 Many countries are currently giving active consideration to joining the OHADA common system of business law.8 Most of the countries have a French colonial heritage, with the exception of the Democratic Republic of the Congo (former Belgian colony), Guinea-Bissau (former Portuguese colony), Equatorial Guinea (former Spanish colony), and Togo and Cameroon (formerly under partly British and partly French colonial rule). French is also an official language in most of the countries and many OHADA sources are only available in French. 9 It is interesting to know that the Council of Ministers of the OHADA organisation which is the legislative organ of the organisation have adopted the following uniform business law: the general commercial laws, corporate laws and rules concerning different types of joint ventures, laws concerning secured transactions, debt recovery and enforcement laws, bankruptcy laws, arbitration law, accountability law, and law regulating contract for the carriage of goods by roads.10 The OHADA treaty established the Common Court of Justice and Arbitration (CCJA) which is a supranational11 judicial institution based in Abidjan, Ivory Coast.12 2.

Les contrats de joint ventures sino-étrangères devant l'arbitre international - Willems, Jane (Université Angers, 2013)
Cette thèse a pour objet de déterminer à quelles conditions l’arbitre international, saisi d’un litige relatif à un contrat de joint venture sino-étrangère, est susceptible d’apporter une solution aux cocontractants et une contribution à la construction du droit de l’arbitrage des investissements étrangers en Chine. L’examen des conditions d’accès à l’arbitrage et de la détermination et de la mise en oeuvre, par l’arbitre international, des règles de droit permettra de cerner les limites du caractère véritablement international de l’arbitrage auquel est soumis le contrat de joint venture sino-étrangère. La limitation de l’autonomie des parties en droit chinois de l’arbitrage et en droit international privé chinois impose des contraintes à l’arbitre international, siégeant en Chine ou à l’étranger tant pour apprécier la validité de la clause compromissoire et l’existence et l’étendue ratione personae et ratione materiae du consentement à l’arbitrage, que pour déterminer et appliquer les règles de droit auxquelles est soumis le litige. L’examen des solutions apportées par l’arbitre international permettra d’apprécier son apport substantiel à la clarification des conditions de formation du contrat de joint venture sino-étrangère, qu’il s’agisse des conditions de fond, tirées de la qualification des parties et de l’existence et de la sincérité de leur consentement au contrat de joint venture, que des conditions de forme, tirées de l’approbation des contrats d’investissement. Cet apport est confirmé en matière d’obligations des parties, par la reconnaissance et la diversification des obligations pécuniaires, de participation et de coopération auxquelles sont tenus les associés de l’entreprise commune
Keywords: Arbitrage; Arbitration; Chine; Clause compromissoire; Conventions d'arbitrage international; Droit commercial (droit international); Entreprises communes; Investissements étrangers; Joint-stock company; Joint-venture

Applicable law in investor-state arbitration: the interplay between national and international law - Elisabeth Kjos, Hege (Oxford Monographs In International Law, 2013)
This book examines the law, national and/or international, that arbitral tribunals apply on the merits to settle disputes between foreign investors and host states. In light of the freedom that the disputing parties and the arbitrators have when designating the applicable law, and because of the hybrid nature of legal relationship between investors and states, there is significant interplay between the national and the international legal order in investor-state arbitration. The book contains a comprehensive analysis of the relevant jurisprudence, legal instruments, and scholarship surrounding arbitral practice with respect to the application of national law and international law. It investigates the awards in which tribunals referred to consistency between the legal orders, and suggests alternatives to the traditional doctrines of monism and dualism to explain the relationship between the national and the international legal order. The book also addresses the territorialized or internationalized nature of the tribunals; relevant choice-of-law rules and methodologies; and the scope of the arbitration agreement, including the possibility of host states presenting counterclaims in investment treaty arbitration. Ultimately, it argues that in investor–state arbitration, national and international law do not only coexist but may be applied simultaneously; they are also interdependent, each complementing and informing the other both indirectly and directly for a larger common good: enforcement of rights and obligations regardless of their national or international origin.
Keywords: Arbitral tribunals; Choice-of-law rules; Foreign investors; Host states; International law; Investor-state arbitration; National law; OAPEN

Written Arbitration Agreements: What Written Arbitration Agreements? - Yu, Hong-Lin (Civil Justice Quarterly, 2013)
First paragraph: This article considers the issue of an oral arbitration agreement in relation to the New York Convention. As Townsend once said "[a]rbitration offers a means to an end, and the end is to the resolution of disputes." This end would be extremely difficult to achieve without the approval of national courts. Fortunately, with 146 signatory countries signed on the New York Convention on the Recognition and Enforcement of Arbitral Awards 1958 (The New York Convention), the success of this Convention has attracted businessmen into using arbitration to resolve their disputes. Nevertheless, a voluntary arbitration cannot be commenced without a valid arbitration agreement. Setting out to achieve harmonisation in the enforcement of arbitration agreements, art.II of the New York Convention provides the written requirements to be followed by all 146 signatory countries. Accordingly, written requirements for arbitration are imposed upon all signatory countries and they are obliged under the convention to recognise all arbitration agreements which are made in writing.
Keywords: Arbitration agreements; Comparative law; Convention d'arbitrage; France; New York Convention awards; New Zealand; Oral contracts; Scotland

I sistemi di risoluzione stragiudiziale delle controversie in materia bancaria e finanziaria - Cannavo, Mauro (Università di Pisa, 2012)
Il presente elaborato mira ad analizzare le forme di tutela accordate in sede europea al “consumatore” si servizi finanziari, al fine di verificarne, da un lato, l’adeguatezza rispetto all’evoluzione normativa che ha interessato tale segmento del mercato (Capitolo I) e, dall’altro lato, le modalità e le tecniche di diffusione nell’ordinamento italiano (Capitolo II) e in quelli dei principali Paesi Europei (Capitolo III). L’indagine muove dal processo di integrazione comunitaria avviato nel 1999 con l’elaborazione del “Financial Service Action Plan”, mettendo in luce come tale azione stia progressivamente contribuendo, attraverso la predisposizione di nuove regole e principi, alla creazione di un “diritto privato europeo”. In tale contesto, infatti, lo spazio rappresentato dal mercato dei servizi finanziari è significativo e di eccezionale rilevanza. Si è osservato, infatti, come l’integrazione dei mercati finanziari – avviata dalle Istituzioni europee, tra l’altro, attraverso l’aggiornamento della normativa comunitaria sui servizi di investimento (direttiva MiFID) – abbia avviato, e progressivamente sostenga, la massima armonizzazione delle regole economiche e giuridiche applicabili alle relazioni con i clienti, anche attraverso l’introduzione di nuovi meccanismi di tutela dei consumatori, volti a preservare la parte “debole” del rapporto contrattuale dai fisiologici rischi connessi alla prestazione dei servizi finanziari. In tale contesto, si è evidenziato come l’omogeneizzazione delle regole dei mercati finanziari abbia comportato, da un lato, l’aumento del flusso di risparmio destinato agli investimenti cross-border, nonché il progressivo coinvolgimento dei consumatori nelle transazioni finanziarie ma, dall’altro lato, abbia contribuito ad esporre maggiormente gli stessi ai rischi connessi agli eventi di crisi che hanno interessato le economie a capitalismo avanzato (ad esempio, il default della banca d’affari Lehman Brother’s). L’esposizione della clientela a situazioni di instabilità, peraltro, è fortemente avvertita anche sul versante dei servizi bancari tradizionali, non soltanto in ragione della diffusione del modello di banca universale e multicanale, ma che per effetto dell’attesa internazionalizzazione dei player del mercato, conseguente al livellamento del relativo “campo da gioco”. Si è perciò sottolineato come la proliferazione delle controversie intermediario-cliente nei diversi segmenti del comparto bancario-finanziario abbia mostrato come il nuovo sistema di tutele introdotto dal legislatore comunitario non sia stato in grado, da solo, di garantire la massima protezione dei consumatori dai rischi connessi alla fruizione dei servizi finanziari. A tale proposito, ci si è interrogati – anche alla luce della copiosa letteratura nazionale ed europea in materia – riguardo ai rimedi esperibili per superare le criticità legate alle procedure giudiziali di risoluzione delle controversie transfrontaliere (i.e. la durata dei tempi processuali, ovvero il costo per accedere alla giustizia), giungendo ad individuare nei sistemi alternativi di risoluzione delle controversie (c.d. ADR) una valida alternativa rispetto alla tutela giudiziale ordinaria. Ancora nel corso del Capitolo I, si è dato conto di come tali meccanismi di mediazione e conciliazione – caldeggiati e, in parte, disciplinati dalle istituzioni comunitarie – potranno, da un lato, comportare la semplificazione e la deburocratizzazione degli apparati giudiziari e, dall’altro, offrire un ulteriore presidio di tutela per i cittadini europei, particolarmente esposti ai rischi connessi ad attività complesse come la prestazione dei servizi di investimento. Come evidenziato nel corso del Capitolo II, non sorprende che in un settore fisiologicamente esposto al rischio di contenzioso come il comparto dei servizi finanziari, le Istituzioni comunitarie abbiano introdotto e progressivamente sospinto la diffusione in Europa dei modelli di ADR, appunto come strumenti di risoluzione delle controversie alternativi agli ordinari rimedi di natura giudiziaria. E sulla spinta comunitaria, anche il legislatore italiano sta progressivamente introducendo nel nostro ordinamento nuove modalità e nuovi sistemi per la risoluzione stragiudiziale delle controversie insorte in sede di prestazione dei servizi finanziari: tra le prime, la disciplina della mediazione finalizzata alla conciliazione delle controversie in materia civile e commerciale (di cui al d.lgs. 4 marzo 2010, n. 28); tra i secondi, i due nuovi organismi di derivazione pubblica, rappresentati dall’Arbitro Bancario Finanziario attivo presso la Banca d’Italia e la Camera di Conciliazione e Arbitrato, costituita presso la Consob. Si è visto, quindi, che le esigenze di tutela della clientela hanno condotto negli ultimi anni all’emanazione di regole e principi, come la disciplina della trasparenza del 2003 (successivamente novellata nel 2009 e, da ultimo, nel 2011 per recepire le nuove regole in materia di contratti di credito ai consumatori) e le regole di funzionamento dei sistemi di risoluzione stragiudiziale delle controversie, che operano proprio a completamento del quadro delle iniziative di tutela della clientela bancaria e finanziaria, come strumenti di redress rapidi, economici ed efficaci. Sempre nel corso del Capitolo II, quindi, si analizzano le caratteristiche principali dell’organismo nazionale deputato alla risoluzione stragiudiziale delle controversie bancarie, costituito dall’Arbitro Bancario Finanziario, al fine di rappresentare la natura giuridica di tale meccanismo, il relativo ambito di applicazione territoriale ed oggettivo, nonché individuando i rimedi esperibili dagli intermediari avverso le decisioni pronunciate dall’ABF. L’indagine prosegue attraverso l’indicazione degli elementi essenziali della Camera di Conciliazione e Arbitrato, istituita presso la Consob al fine di redimere le controversie insorte in sede di prestazione dei servizi di investimento, anche attraverso un approfondito confronto con la natura giuridica e l’ambito di applicazione dell’ABF. Infine, nel Capitolo III dell’elaborato – dopo aver esaminato le principali ragioni poste alla base della diffusione degli strumenti ADR in Europa, le principali iniziative legislative (direttiva mediation) e di autoregolamentazione (reti EEJ-NET e FIN-NET) in materia – si offre un’analisi dei principali sistemi ADR attivi in Europa, attraverso una dettagliata indagine comparatistica che ha interessato gli ordinamenti francese, spagnolo, tedesco e inglese. La menzionata indagine, in particolare, ha messo in luce le principali differenze e le numerose analogie presenti tra i sistemi ADR attivi nell’Unione europea, principalmente con riguardo alla natura giuridica dei rispettivi organismi, alle funzioni svolte, alle condizioni di accesso ai sistemi, nonché alle caratteristiche delle relative decisioni.
Keywords: ABF; ADR; Arbitrage; Arbitragem; Arbitration; Arbitrato; Arbitro; Banca; Cliente; Collegio; Conciliazione; Consob; Controversie; Finanziario; Intermediari; Intermediazione; MARD; Mediación; Mediation; Mediazione; Mediação; Médiation; Reclamo; Ricorso; Stragiudiziale

L'émergence du droit international des investissements : contribution des traités bilatéraux d’investissement et de la jurisprudence du CIRDI - Danic, Olivia (Université Paris 10, 2012)
La relation dialectique qui unit les traités bilatéraux d’investissement et la jurisprudence du Centre International de Règlement des Différends relatifs aux Investissements (CIRDI) a fait émerger un droit international des investissements. La rencontre de ces deux dynamiques a permis de dépasser leur caractère a priori isolé et fragmenté, pour aboutir à un véritable système juridique international, doté d’une structure, d’une logique et de principes propres. En effet, rien ne pouvait laisser envisager une telle évolution, le régime de l’investissement international se fondant sur une multitude de traités bilatéraux et sur une instance arbitrale ne faisant qu’héberger des tribunaux éphémères. Les mouvements de va-et-vient qui unissaient ces deux phénomènes ont permis de lui donner des normes quasi-universelles, mais aussi un véritable juge à la compétence extensive et surtout de lui insuffler l’unité, l’efficacité, la cohérence et la complétude, faisant de plus en plus ressembler le droit international des investissements à un véritable ordre juridique qui, même s’il relève du droit international, lui permet également d’évoluer. The relashionship between bilateral investment treaties and the case-law of the International Centre for Settlement of Investment Disputes (ICSID) has led to the emergence of international investment law. It seems surprising, at first, that these two distinct phenomena, being isolated and fragmented, would reach a certain degree of unity so that a real international legal order could appear, with its own structure, reasoning and principles. No one could foresee such an evolution, the regime of international investment being founded on a large number of bilateral treaties and on an international institution which only provides facilities for arbitration of international investment disputes. The unity of the system has been discovered through the back and forth movements between treaties and arbitration which gave rise to international investment law. This system has now almost universal norms, an international judge and satisfies the criteria of unity, efficiency, consistency and completeness, producing a real legal order functioning in accordance with its own logic. There is no doubt that this evolution will influence the course of international law.
Keywords: Arbitrage; Arbitrage (droit); Arbitration; Bilateral Investment Treaties (BITs); CIRDI; Centre international pour le réglement des différends relatifs aux investissements; Droit international; ICSID; International law; Investissements; Investissements étrangers (droit international); Investment; Investments; Jurisprudence; Legal order; Ordre juridique; Traité bilatéral d’investissement

La responsabilité sociétale des entreprises et la médiation - Mattei, Laetitia (Université Paris 9, 2012)
Les crises actuelles, sous leurs multiples aspects, mettent en lumière la responsabilité des entreprises dans notre société, bousculant ainsi l'un des dogmes néolibéraux résumé par la célèbre formule de Milton Friedman (1970) : « La responsabilité sociétale de l’entreprise est d’accroître ses profits». C’est en réaction à ces crises et grâce au rôle actif de la société civile qui condamne désormais certaines pratiques, que le concept de responsabilité sociétale des entreprises (ci-après RSE) a émergé. L’enjeu est donc, aujourd’hui, de mettre en place un marché responsable entre l’entreprise et ses parties prenantes. Le législateur, par la loi Grenelle I, dispose que la médiation sera un des outils de mise en oeuvre de la RSE. Il en appelle donc au développement du droit processuel qu’est la médiation pour mettre en oeuvre ce droit substantiel qu’est la RSE. La médiation, à la fois préventive et curative, est donc un outil de mise en oeuvre de la RSE. Le couple RSE et médiation permet ainsi de combiner efficacité économique, respect social,sociétal et environnemental
Keywords: Company; Entreprise; Grenelle Environnement 2007; Législation; MARD; Mediación; Mediation; Mediação; Médiation; Paris; Parties prenantes; Parties prenantes (gestion d'entreprise) -- France; Procédure (droit); Responsabilité; Responsabilité sociétale; Responsibility; Sociétal; Stakeholders

The Influence of ICC Arbitral Decisions on Canadian Law: Comparative Study between Civil Law and Common Law Jurisdictions - Hedaraly, Saleha (Université de Montréal, 2012)
L’objectif de cette recherche est de démontrer que les décisions arbitrales de la Chambre de commerce internationale peuvent être considérées comme une source potentielle de droit au Canada. Il existe actuellement une incertitude quant au droit matériel utilisé en arbitrage international pour résoudre les différends commerciaux. Bien que l’utilisation de la lex mercatoria pour résoudre un litige soit une option, elle se heurte à de nombreuses incertitudes terminologiques et conceptuelles. L’utilisation d’une approche méthodologique de la lex mercatoria permettrait une classification de ses sources en deux branches: (1) le droit statutaire international et (2) le stare decisis des tribunaux d’arbitrage commercial international. Une telle approche méthodologique conférerait plus de certitude quant à l’application d’un droit uniforme. De plus, elle faciliterait l’étude de l’interlégalité entre les règles de la lex mercatoria et le droit matériel interne. Plus particulièrement, elle permet de comparer les similitudes et les différences des règles du droit matériel entre les décisions arbitrales internationales, le droit statutaire international et les juridictions canadiennes de common law et de droit civil. Cette comparaison rend possible une évaluation de l’influence potentielle des décisions arbitrales de la Chambre de commerce internationale sur le droit matériel canadien et si cette influence est plus importante en droit civil ou en common law. This paper’s objective is to demonstrate that the International Chamber of Commerce’s arbitral awards may be considered as a potential source of law in Canada. There currently exists an uncertainty as to the substantive law used in international commercial arbitration. While the use of lex mercatoria to solve commercial disputes is often referred to, several terminological and conceptual uncertainties undermine its credibility. The use of a methodological approach to lex mercatoria allows for a twofold classification of its sources through: (1) international legislation and (2) stare decisis from international arbitral tribunals. This methodological approach provides a greater certainty for the application of a uniform law which, in turn, allows for the study of interlegality between rules of lex mercatoria and substantive domestic law. Furthermore, this methodological approach facilitates the demonstration of the similarities and differences between international arbitral decisions, international legislation as well as Canadian common law and civil law jurisdictions. This comparative analysis will allow the study of the potential influence of the arbitral decisions of the International Chamber of Commerce on substantive Canadian law and whether this influence is more important in civil law or common law.
Keywords: Approche méthodologique; Arbitrage; Arbitragem; Arbitral decisions; Arbitration; CCI; Civil law; Common law; Droit civil; Droit commercial transnational; Décisions arbitrales; ICC; Interlegality; Interlégalité; Lex mercatoria; Methodological approach; Sentences arbitrales; Transnational commercial law

The legal and institutional framework for the enforcement of online consumer arbitration awards: evidence from Australia and Sri Lanka - Kananke, Chinthaka Liyanage (La Trobe University, 2012)
Keywords: Australia; Commercial law; Conflict of laws; Consumer protection; Dispute resolution; Electronic commerce; Sri Lanka

A proposal to guide future draft article provisions for a model harmonised international commercial arbitration law code (HICALC) in the Middle East and North Africa or a uniform Arab arbitration law - Ayad, Mary Boulos (Macquarie University, 2012)
MENA law codes are a well-crafted blend of civil and Islamic law in which civil law principles do not contravene with Islamic provisions. They were originally based on Sanhuri’s codes to varying degrees. Yet, common law principles derived either from English common law or Islamic customary usages are unidentified and thus ignored. Here, this lacuna is rectified through a comparative analysis of the primary data (eg, cases, statutes and arbitral award decisions), adding common law and uncodified Islamic custom to MENA law codes. The purpose of this comparative analysis is to allow common legal principles found at civil, common and Islamic law to be distilled in the service of creating a new harmonised international commercial arbitration law code (HICALC) or uniform Arab arbitration law (UAAL) for adoption in the MENA.1 These principles already form part or all of the legal systems in the MENA. They can be readily assimilated into a harmonised or uniform code. Would this new harmonised code lead to higher arbitral award enforcement in the MENA? According to the evidence the answer is yes. The author understands that at the present time the HICALC articles are ambitious and as such they are a beginning point and can initially be taken as a harmonised international commercial arbitration common rule (HICACR). A brief overview of the history of harmonisation is given. An assessment of the status of the laws and traditions of the MENA was carried out. A comparative analysis of the relevant differences and similarities of the case study countries (Egypt and the United Arab Emirates) was carried out to show the gaps in the laws and areas requiring reform. An analysis of enforcement of arbitral awards was carried out. The unique problems that ICA and IIA encounter in the MENA as derived from an analysis of cases and the laws therein are expounded in consideration of matters pertaining to enforcement. A comparative analysis of universal principles which must be included in a new code, including custom, was carried out. An analysis of the unique features and unique needs of the MENA was carried out in order to inform the Draft Article Provisions. An analysis of important international legal instruments dealing specifically with international arbitration and the gaps therein is given. The draft articles for a HICALC or uniform Arab arbitration law were derived as a result of these multiple layers of analysis. The matters of compétence de la compétence, expropriation, interest, public policy and sovereign immunity are highlighted as the most important areas requiring urgent reform. The results of this research are suggested Draft Article Provisions for a model Harmonised International Commercial Arbitration Law Code (HICALC) or a uniform Arab arbitration law. Future drafters may refer to and revise these articles for implementation. The synthesis of theory and practice addresses doctrinal matters that arise in international investment arbitrations and international commercial arbitration, with a focus on investor–State arbitrations. This synthesis provides a new theoretical conception of the jurisprudence of international arbitration, particularly in regard to the matters of res iudicata, precedent and expansion of arbitral tribunal powers and jurisdiction.
Keywords: Arab countries; Arbitrage; Arbitragem; Arbitration; Arbitration Law; Arbitration and award; Commercial law; Commercial law (Islamic law); Common rule; Dispute resolution; HICACR; HICALC; Harmonised International Commercial Arbitration; International commercial arbitration; MENA law codes; Middle East; North Africa; UAAL; Uniform Arab arbitration law

L'Influence de l'accueil de la sentence arbitrale par le juge algérien sur l'efficacité de l'arbitrage commercial international - Hocine, Farida (Université Mouloud Mammeri, 2012)
Keywords: Algérie; Arbitrage commercial; Arbitrage international; Arbitragem; Arbitraje; Arbitration; Efficacité de l'arbitrage; Juge algérien; Sentence arbitrale

From Port Louis to Panama and Washington DC: Two Regional Approaches to International Commercial Arbitration - Bashi Rudahindwa, Jonathan (European Journal of Law Reform, 2012)
In recent decades, regional efforts have been made to reform and harmonize the rules governing international arbitration. These efforts have resulted in the adoption of regional instruments governing commercial arbitration in specific areas. This paper analyzes the arbitration regimes created at a regional level in Africa and America, and particularly focuses on arbitral institutions that were created within the Organization for Harmonization of Business Law in Africa (OHADA) and within the Organization of American States (OAS). The objective of the paper is to identify any advantages provided by either regime, which can help improve regional and international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration

Efetividade das estipulações voltadas à instituição dos meios multiportas de solução de litígios - Guerrero, Luis Fernando (Universidade de São Paulo, 2012)
Este estudo examina as estipulações voltadas à instituição de meios multiportas de solução de controvérsias, mecanismo responsável por materializar a vontade da partes em solucionar os seus conflitos via métodos alternativos ou adequados de solução de controvérsias, tendo relevante papel na materialização do escopo social do processo. Há uma clara dicotomia entre os denominados métodos de solução de controvérsias consensuais, nos quais a própria participação das partes levará à solução e à conformação do litígio e, de outro lado, os métodos adjudicatórios de solução de controvérsias, no qual haverá um terceiro imparcial escolhido pelas partes ou de acordo com mecanismos por elas estabelecido e que será responsável pela solução da controvérsia. Existem ainda métodos combinados ou mistos, em que são aglutinados elementos dos métodos denominados primários, quais sejam negociação, conciliação, mediação e arbitragem. Clara a diferença entre essas categorias de métodos de solução de controvérsias, deve-se analisar, ainda, se há alguma diferença no tocante à vinculação das partes a cada uma das mencionadas categorias de solução de controvérsias e, com grande importância, de que modo métodos consensuais podem interferir no surgimento e desenvolvimento de métodos adjudicatórios. Em relação à vinculação dos métodos de solução de controvérsias adjudicatórios, a grande referência no direito brasileiro é a arbitragem, que conta com legislação própria e deve muito de seu sucesso no atual estado dos métodos de solução de controvérsias no direito brasileiro a alterações relativas à sua vinculação e efetivação. Nitidamente, há uma inserção das cláusulas de solução de controvérsias, seja qual for o método utilizado no âmbito da ciência processual. A base de tais cláusulas é de direito privado, fundamentando-se em institutos bastante conhecidos: transação e compromisso que ganharam a categorização jurídica de contrato após o Código Civil de 2002. Do ponto de vista da adoção desses instrumentos jurídicos como veículos da utilização dos métodos de solução de controvérsias, são previstas técnicas diversas de uso. A primeira é extrajudicial, baseada na planificação de solução de conflitos, que pode ser feita pelas partes e seus advogados, e uma segunda, que é extrajudicial baseada no caseflow e no case management, nos quais o Judiciário assume o papel de coordenador e aplicador de tais métodos. A relação entre os métodos de solução de controvérsias ganha caráter dinâmico na medida em que determinados sistemas de solução de controvérsias são combinados para uma dada questão. Trata-se das chamadas cláusulas escalonadas que têm por escopo acompanhar a escalada de litigiosidade que possa surgir em determinada discussão jurídica, combinando métodos consensuais e adjudicatórios de solução de litígios. Em qualquer situação, de acordo com os termos dos arts. 158 e 466-B do Código de Processo Civil que podem analogamente ser comparados com os arts. 4.º e 7.º da Lei de Arbitragem, há a total vinculação das partes ao método de solução de controvérsias escolhido. Questão bastante tormentosa é a inserção e a inter-relação dos métodos de solução de controvérsias, especialmente com o processo civil e os efeitos que daí podem decorrer. Nesse aspecto, sendo um método consensual, as partes que a ele aderiram terá que realizá-lo antes da busca de um método adjudicatório de adesão voluntária, como é a arbitragem, ou um método adjudicatório inevitável, como é o Judiciário. Trata-se do efeito negativo das cláusulas ADR. Contudo, há que verificar que efeitos seriam gerados aos métodos adjudicatórios pela não realização de um método consensual precedente. Os métodos de solução de controvérsias poderiam ser encarados como pressupostos processuais, condições da ação ou questões prévias, promovendo diferentes resultados em um processo judicial ou arbitral. Há que se buscar a solução que melhor se adequar a um contexto de solução de controvérsias. Desta feita, os MASCs devem ser colocados como hipóteses suspensão dos processos arbitral ou judicial, suspensão essa que deve durar até a realização do referido método acordado anteriormente, garantindo-se a sua eficácia. No tocante a este ponto, o Estado tem um relevante papel político e legislativo de modo a incentivar a utilização de tais métodos e garantir-lhes a eficácia. Além disso, a parte que se furtar está sujeita a consequências contratuais que podem ser previstas, tais como a imposição de multas e cláusulas penais. Vislumbram-se também hipóteses de perda de uma chance, com o agravamento do litígio e prejuízos que podem advir do tolhimento da chance de um método de solução de controvérsias produzir um resultado. De qualquer modo, aquele que pretendia utilizar o método, para se valer dessas possíveis indenizações, tem o dever de mitigar o próprio dano como resultado da mesma cláusula geral de boa-fé que, ao reverso, obrigou o ex-adverso a utilizar o método e foi violada. Pode-se pensar nesse contexto, ainda, a possibilidade de métodos alternativos de solução de controvérsias serem estabelecidos por meio de cláusulas que prevejam a venda de excussão entre as partes ou mesmo medidas corporativas, tais como ocorrem na BM&F Bovespa, apenas de acordo com a manifestação de vontade das partes de adesão ao referido sistema, sendo uma prova da força e extensão do vínculo surgido de uma estipulação de solução de controvérsias, ainda que consensual. Há, de qualquer modo, uma execução por transformação em que a manifestação de vontade apresentada pelas partes pode ser efetivada pelo magistrado permitindo a utilização dos métodos de solução de controvérsias a partir do momento em que ocorreu a adesão das partes. Por fim, a confidencialidade que pode ser aplicada aos métodos de solução de controvérsias tem natureza contratual, não interferindo na eficácia das cláusulas ADR. This study examines the stipulations aimed to establishing alternative settled mechanism responsible for materializing the will of the parties to resolve their disputes through alternative or appropriate dispute settlement with a relevant role in the materialization of the social scope of the process. There is a clear dichotomy between the called consensual methods of dispute resolution in which the participation of the parties will lead to the solution and the conformation of the dispute and, on the other hand, the called adjudicatory methods in which an impartial third party will be chosen by parties or in accordance with mechanisms established by them and will be responsible for resolving the dispute. There are also mixed or combined methods, which contains elements of the primary methods, namely, negotiation, conciliation, mediation and arbitration. Differences between these categories of methods of dispute settlement shall be analyzed, even if there is any difference with respect the binding feature of those methods and, with great importance, so that consensual methods can interfere in the emergence and development of adjudicatory methods. In relation to binding adjudicatory methods of dispute settlement, the most important reference in Brazil is Arbitration. Its Law is responsible for it succed as a method of dispute resolution in the Brazil, specially for ten. changes to their binding feature and enforcement of its result, now recognized as a sentence. The legal basis of such clauses is private law and are based on well-known institutions: transaction and commitment that are a contractual legal categorie after the Civil Code. From the standpoint of using, these legal instruments are vehicles and are expected to use different techniques. The first rendition is based on planning for conflict resolution that can be made by the parties and their lawyers and a second which is based on caseflow and case management, in which the judiciary takes over the role to coordinate and implement these methods. The relationship between the methods of dispute settlement became dynamic when individual methods of dispute settlement are combined to a given question. These are the called staggered terms which seeks to track the escalation of litigation that may arise in a particular legal issue, combining both consensual and adjudicatory dispute resolution methods. In any event, in accordance with the terms of the arts. 158 and 466-B of the Civil Procedure Code that can similarly be compared with the arts. 4o and 7o of the Arbitration Act, there is the share of binding feature of the method of dispute resolution chosen. Question very stormy is the interrelationship of the insertion of dispute resolution methods, especially consensual and adjudicatory methodse. In this aspect, a method is agreed, the parties have to do it before the search for an adjudicatory method. This is the negative effect of ADR clauses. However, there it is found that the effects would be generated by methods Adjudicative not performing a method consesual precedent. The methods of dispute settlement may be seen as procedural requisites, conditions of action or issues prior action by promoting different results in a lawsuit or arbitration. We must seek the solution that best fits the context of a multi door dispute settlement. The conclusion is that the ADR methods should be placed as hypotheses of suspension for arbitration or judicial processes. That suspension should last until the completion of this method previously agreed, assuring its effectiveness. Concerning this point, the State has an important political and legislative role in order to encourage the use of such methods and guarantee their effectiveness. In addition, the part that is subject to evade contractual consequences that can be provided such as the imposition of fines and penalty clauses. In case of ADR clauses breach the lost of a chance theory shall applyo, with increased litigation and damages that may arise from the chance of stunting a method of dispute resolution to produce a result. Anyway, who intended to use the breach of the other party to take advantage of possible damages, has the duty to mitigate the loss itself as a result of the same general clause on good faith that, in reverse, enforces the former adverse to using the method and was violated. One might think in this context also the possibility of alternative methods of dispute settlement be established by means of clauses providing for the sale of excussion between the parties or even intracorporis issues such as occur in the BM&F Bovespa, only in accordance with the manifestation the will of the parties to accede to such a system, a testament to the strength and extent of the relationship arising from a stipulation of settlement of disputes, even if consensual. The intetion to use an alternative dispute resolution shall be given by the partíreis but in case of breach of this obligation the interested party can obtain an mandatory decision by the Judge indicating that the other party must attend the dispute resolution method. Finally, the confidentiality that can be applied to methods of dispute settlement is contractual in nature, not interfering with the enforcement of ADR clauses.
Keywords: ADR; Civil Procedure; Conciliação (processo civil); Direito processual civil; Dispute Resolution; Enforceability; Multidoor; Solução de conflito; Transação; Tutela jurisdicional

Arbitrability in the context of Ghana's new arbitration law. - Mante, Joseph; Ndekugri, Issaka (International arbitration law review, 2012)
Examines the approach of Ghana's Alternative Dispute Resolution Act 2010 to the question of arbitrability. Reflects on the concept of arbitrability under international law, the relevant trends emerging from case law, and the approach adopted by the Ghanaian High Court in Attorney General v Balkan Energy LLC. Reviews the Act's arbitrability exemptions, their implications for international arbitration in Ghana, the potential jurisdictional challenges under the legislation and how its provisions could be amended to increase its conformity with international trends on arbitrability.
Keywords: Arbitrability; Arbitrage; Arbitragem; Arbitration; Comparative law; Ghana; International commercial arbitration; Jurisdiction

Reflections on finality in arbitration - Roodt, Christa (De Jure, 2012)
Ondersoek na die Finaliteit van 'n Arbitrasiebevel Hierdie artikel oorweeg die Telcordia- en Lufuno-sake vanuit die oogpunt van die finaliteit van 'n arbitrasiebevel. Die vraag wat te berde kom, is wanneer 'n arbitrasiebevel finaliteit bereik waar 'n saak voor meer as een forum (arbitrasie en staatlike howe), in meer as een jurisdiksie gevoer word. Die prosedurele meganismes wat Amerikaanse en Suid-Afrikaanse howe tydens die Telcordia-dispuut toegepas het asook hul onderskeie benaderings tot res iudicata, het 'n groot mate van ooreenstemming getoon. Dit is te verstane dat die afhandeling van 'n internasionale proses vertraag kan word deur bepaalde grondwetlike regte wat die spoed van die afhandeling van 'n saak kan beïnvloed. Nietemin, indien die reg op 'n billike verhoor op enige stadium in die verrigtinge gepleit mag word, word 'n geleentheid geskep vir die dispuut om vryelik te eskaleer gedurende die verhoor. Dit kan die hofproses oopstel vir misbruik en die afhandeling van die geskil vertraag. Die minderheidsbeslissing in Lufuno skenk 'n mate van oorweging aan die potensiële negatiewe implikasies hiervan. Die finaliteit van die geskilbeslegtingsproses kan na behore bestuur word aan die hand van 'n wyer interpretasie van res iudicata in internasionale dispute en 'n meer geredelike ondersoek hierna, op die hof se inisiatief. Die moontlikheid dat die Telcordia-dispuut verder bespoedig sou kon word, word ondersoek met verwysing na die New York Konvensie op die Erkenning en Afdwing van Arbitrasiebevele van 1958, en aan die hand van aanbevelings wat deur ander gerekende internasionale liggame uitgereik is.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration

Lex mercatoria in international arbitration theory and practice. Vol 1 - Elcin, Mert (European University Institute, 2012)
This dissertation suggests a new theory of lex mercatoria that takes into account the complex and spontaneous order of international commerce. Since the emphasis is put on the nature of this order, the concept of lex mercatoria is examined as an ex post governance mechanism resolving contractual disputes with a view to maintaining and restoring the order of international commerce, without focusing on the traditional distinction of the doctrine between national and non-national legal rules applicable to the substance of such disputes in explaining the concept. The aim is to reflect lex mercatoria’s subtle effect on the practice of international arbitration, and to provide an explanation of lex mercatoria as a solution to the problems of the institution of international arbitration in terms of uncertainty and unpredictability of awards, rather than representing it as a factor aggravating those problems. Lex mercatoria is defined as the law of adjudication of the disputes arising from international commercial contracts on the basis of a few substantive and procedural principles, under which the reasonable expectations of the parties to a particular contract become the single source of their contractual rights, obligations and risk allocations. The argument is that lex mercatoria can be applied to both the choice of law analyses and the substance of the disputes in international arbitration. In choice of law analyses, lex mercatoria addresses specific difficulties relating to the conflict of laws through a principled decision making, such as the applicable conflict rules, and the interpretation of the parties’ intentions as to the applicable substantive rules. In its substantive application, lex mercatoria deals with, either as lex contractus or as lex fori, the interpretation, supplementation and correction of the contract as well as the applicable national laws in accordance with the basic principles, on which the order of international commerce rests.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Commercial law; Conflict of laws; Foreign trade regulation; Law merchant

Lex mercatoria in international arbitration theory and practice. Vol 2 - Elcin, Mert (European University Institute, 2012)
This dissertation suggests a new theory of lex mercatoria that takes into account the complex and spontaneous order of international commerce. Since the emphasis is put on the nature of this order, the concept of lex mercatoria is examined as an ex post governance mechanism resolving contractual disputes with a view to maintaining and restoring the order of international commerce, without focusing on the traditional distinction of the doctrine between national and non-national legal rules applicable to the substance of such disputes in explaining the concept. The aim is to reflect lex mercatoria’s subtle effect on the practice of international arbitration, and to provide an explanation of lex mercatoria as a solution to the problems of the institution of international arbitration in terms of uncertainty and unpredictability of awards, rather than representing it as a factor aggravating those problems. Lex mercatoria is defined as the law of adjudication of the disputes arising from international commercial contracts on the basis of a few substantive and procedural principles, under which the reasonable expectations of the parties to a particular contract become the single source of their contractual rights, obligations and risk allocations. The argument is that lex mercatoria can be applied to both the choice of law analyses and the substance of the disputes in international arbitration. In choice of law analyses, lex mercatoria addresses specific difficulties relating to the conflict of laws through a principled decision making, such as the applicable conflict rules, and the interpretation of the parties’ intentions as to the applicable substantive rules. In its substantive application, lex mercatoria deals with, either as lex contractus or as lex fori, the interpretation, supplementation and correction of the contract as well as the applicable national laws in accordance with the basic principles, on which the order of international commerce rests.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Commercial law; Conflict of laws; Foreign trade regulation; Law merchant

Arbitrage transnational et droit international général (2012) - Jacob, Patrick; Latty, Franck (Annuaire Français de Droit International, 2012)

La priorité chronologique reconnue à l'arbitre en droit maritime français, particularisme ou universalisme ? Le principe dit de compétence-compétence - Yildiz, Irfan (Aix-Marseille Université, 2012)
L’abandon progressif du contrôle de l’opposabilité de la clause d’arbitrage au destinataire par la juridiction étatique au profit de l’arbitre sur le fondement de l’aspect négatif du principe de compétence-compétence a donné lieu à de nombreux critiques. Certains auteurs l’ont approuvé, valorisant une application rigide de l’effet négatif du principe, tandis que d’autres l’ont critiqué solidement. Ainsi, il est légitimement permis de s’interroger sur les excès de l’effet négatif du principe de compétence-compétence et le bien-fondé de l’abandon du contrôle de l’opposabilité à l’arbitre par les juges étatiques. Pour ce faire, nous allons, dans un premier temps, examiner le droit accordé à l’arbitre d’être juge de sa propre compétence de manière prioritaire, plus précisément le principe de compétence-compétence (Chapitre I). Ensuite, nous allons nous interroger sur l’extension de la clause d’arbitrage au destinataire au regard du principe de compétence-compétence, qui est considéré de remettre en cause ce principe (Chapitre II).
Keywords: Arbitre droit maritime; Compétence-compétence; Transport maritime

Duty of Confidentiality: Myth or Reality? - Yu, Hong-Lin (Civil Justice Quarterly, 2012)
Explores the extent to which there is a duty of confidentiality in relation to the information used in arbitration proceedings. Considers how the duty is regulated by arbitration rules in different countries and whether there is a sufficient consensus to develop an internationally accepted principle of duty of confidentiality. Discusses which jurisdictions have an implied duty of confidentiality in the parties' arbitration agreement. Looks at how confidential information is defined in different jurisdictions, who is bound by the duty of confidentiality and the exceptions to the duty.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Confidential information; Confidentiality; Confidentialité; Information confidentielle

L'arbitrage CCJA - Wambo, Jérémie (Revue de l'ERSUMA, 2011)
L’arbitrage est désormais une institution traditionnelle de la vie des affaires sur le plan national, mais aussi et surtout sur le plan international. C’est un « mode alternatif de règlement des litiges qui consiste à faire trancher un différend par de simples particuliers », qui peuvent être des « personnes choisies par les parties »115. On distingue généralement deux types d’arbitrage, l’arbitrage Ad Hoc, qui demeure le plus fréquent, et l’arbitrage Institutionnel. Mais notre discussion va beaucoup plus porter sur le deuxième type d’arbitrage à travers le Centre d’arbitrage de la Cour Commune de Justice et d’Arbitrage de l’OHADA. Les signataires du Traité de Port Louis (Traité OHADA) du 17 Octobre 1993 avaient, dès le préambule, exprimé leur désir de « promouvoir l’arbitrage comme instrument de règlement des différends contractuels ». C’est pourquoi l’article 1er dudit Traité qui définit ses objectifs précise qu’il est question entre autres d’encourager le « recours à l’arbitrage pour le règlement des différends contractuels ». Les articles 21 à 25 posent les bases de cet arbitrage. La concrétisation de ces intentions s’est manifestée par l’adoption à Ouagadougou par le Conseil des Ministres de l’OHADA le 11 Mars 1999, de l’Acte Uniforme relatif au Droit de l’Arbitrage, et du Règlement d’Arbitrage de la CCJA qui fixe les règles applicables à l’arbitrage CCJA. Plusieurs textes ont été pris par la suite qui ont permis d’organiser l’arbitrage CCJA (I) afin de rendre lisible le professionnel le déroulement de procédure arbitrale.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Procédure arbitrale; Règlement d'arbitrage

Culture of international arbitration and the evolution of contract law - Karton, Joshua David Heller (University of Cambridge, 2011)
Keywords: Arbitrage; Arbitragem; Arbitration; Contract law; International Arbitration

Mediação e judiciário: condições necessárias para a institucionalização dos meios autocompositivos de solução de conflitos - Gabbay, Daniela Monteiro (Universidade de São Paulo, 2011)
A questão central deste trabalho refere-se à institucionalização da mediação no âmbito do Judiciário e às condições necessárias para uma boa relação entre a mediação e o processo judicial. Esta questão foi analisada sob as perspectivas processual e institucional. A primeira recai sobre as bases do processo de mediação, em especial o devido processo legal mínimo, e a sua interação com o processo judicial, diferenciando a justiça do processo e a justiça do resultado. A segunda recai sobre o desenho dos programas de mediação que funcionam junto ao Judiciário e os papéis assumidos pelos diferentes atores que participam destes programas: juízes, mediadores, partes, advogados e funcionários dos Tribunais. Sob esta última perspectiva, foi realizada pesquisa empírica e comparada em programas de mediação que funcionam junto ao Judiciário no Brasil e nos EUA. The main issue of this work is the institutionalization of mediation within the Courthouse and the pre-conditions for having a good relationship between mediation and the Judiciary. This issue is analyzed from both procedural and institutional points of view. The procedural perspective falls on the mediation due process (minimal but meaningful due process standards) and on the differences between the procedural and substantial justices. The institutional perspective falls on the design of the Court-Connected Mediation Programs and on the roles of the players who participated in these programs: judges, mediators, plaintiff and defendant, attorneys, and Court workers. An empirical research was also done about the Court-Connected Mediation Programs in Brazil and in the United States.
Keywords: Arbitrage; Arbitragem; Arbitration; Court-connected mediation programs design; Empirical research; Institutionalization of mediation; Juizo arbitral; MARD; Mediación; Mediation; Mediação; Mediação e conciliação; Minimal due process; Médiation; Solução de conflito

Effectiveness and Remedies of the Arbitral Awards in OHADA’s System and in People’s Republic of China. - Samassekou, Mamoudou; Lianbin, Song (Journal of Politics and Law, 2011)
Today the arbitral justice has experienced an exceptional development. It is a universal phenomenon which requires the involvement of all economic and legal players of developed and developing countries.OHADA is a common business law and wish to secure legal security for regional and foreign economic agents by offering a vast economic space. The People’s Republic of China (PRC) is an emerging country which increases its economic outlets in a context of globalization. This natural interdependence will increase the scope of economic exchanges, which may generate some disputes in businesses. This article aims to compare two legal systems in the international commercial arbitration field: the legal system of OHADA and the PRC’s legal system; especially in the effectiveness and the remedies of the arbitrators’ decisions.

Le principe de compétence-compétence en droit de l'arbitrage - Boucaron-Nardetto, Magali (Université Nice Sophia Antipolis, 2011)
Dans son sens originaire, le principe compétence-compétence permet au tribunal arbitral, comme à tout juge, de statuer sur sa compétence. En droit français, il s’est transformé en règle de conflit entre justice publique et justice privée doublement originale : d’une part, il repose sur l’exercice coordonné du pouvoir de juger de la compétence ; d’autre part, il est pluraliste. Enclenché par l’apparence vraisemblable d’une convention d’arbitrage, le principe compétence-compétence consiste en un mécanisme composite se déployant dans le temps du procès arbitral et dans l’espace des deux ordres juridiques considérés. Ainsi, trois règles distinctes permettent à chacune des justices – justice française et justice arbitrale – de connaître de sa propre compétence de manière coordonnée. Tout d’abord, en amont et en parallèle de l’instance arbitrale, l’effet négatif de la compétence-compétence paralyse le pouvoir des juridictions étatiques de statuer sur leur compétence. Ensuite, le temps du procès arbitral, l’effet positif de la compétence-compétence des tribunaux arbitraux reconnaît à ces derniers le pouvoir de juger de leur compétence. Enfin, au stade post-arbitral, l’effet positif de la compétence-compétence des juridictions publiques permet à ces dernières de retrouver le pouvoir de statuer sur leur compétence lors des recours ouverts contre la sentence. Chacune des règles examinées connait limites ou écueils. Parfois, l’équilibre est rompu soit au profit des juridictions d’Etat, soit au profit des juridictions arbitrales. Force est de constater que le caractère pluraliste du principe compétence-compétence est tantôt réalité, tantôt mirage. In its original sense, the principle of competence-competence empowers the arbitral tribunal, as well as any judge, to decide on its own jurisdiction. Under French law, it has been transformed into a rule on conflict of jurisdiction between state court and arbitration tribunal doubly innovative. On one hand, it rests on the coordinated exercise of the power to rule on its jurisdiction; on the other hand, it is pluralist. Activated by the appearance of an arbitration agreement, the principle of competence-competence consists of a heterogeneous mechanism, using the time of arbitration proceedings and space of both legal orders. Thereby, three distinct rules allow each justice - French courts and arbitration - to rule on its own jurisdiction coordinately. First, during or prior the arbitration proceedings, the negative effect of the competence-competence paralyses the power of the state court to rule on its own jurisdiction. Secondly, during the arbitration proceedings, the positive effect of the competence-competence of the tribunal arbitral recognizes that arbitrators decide upon their own jurisdiction. Finally, at the post-arbitral stage, the positive effect of the competence-competence of state courts permits them to recover the power to rule on their own jurisdiction at the setting aside or enforcement stage of the arbitration. Each analyzed rule has its own limits. Sometimes, the balance is disrupted either in favour of state courts, or in favour of the arbitral tribunal. To conclude, it is clear that the pluralist character of the principle of competence-competence is in some cases a reality, in others a mirage.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Pluralisme juridique; Règlement de conflits

Dispute Resolution in International Electricity Trade - Han, Baoqing (Energy Procedia, 2011)
International electricity trade disputes can arise at three key levels: state to state; investor to state; private party to private party. Parties may be more open to submission of their disputes to international arbitration. However, they should make proper arbitration options according to the types of disputes. At the same time, considering the risks facing dispute resolution, it is imperative to specifically design effective tools to mitigate these risks.
Keywords: Dispute resolution; Disputes; International Arbitration; International electricity trade; Risk mitigation

L'annulation de la sentence arbitrale au Québec et dans l'espace OHADA : une approche comparée. - Kouassi, Fabrice Constant (Université de Sherbrooke, 2011)
Le processus de règlement des litiges par la voie de l’arbitrage a nourri des ambitions économiques énormes dans les sphères juridiques où ce mécanisme a été instauré. L’efficacité de ce processus qui signifie entre autre un processus ayant abouti à une application, voire une exécution effective des protagonistes est un gage de la réalisation de ces ambitions. Or, ce processus peut être compromis du fait de l’annulation de la sentence arbitrale par un juge dont l’intervention dans le processus peut soit le renforcer, soit l’annihiler fondamentalement. Cette situation explique dans une large mesure les raisons pour lesquelles la doctrine juridique se place en faveur d’une collaboration solide entre la justice publique et la justice privée de l’arbitrage. Comment cette question de l’annulation de la sentence arbitrale est abordée dans les sphères juridiques du Québec et de l’Ohada? Quels sont les effets juridiques issus de la comparaison de cette situation dans chacune de ces sphères? Telle se présente la substance de cette recherche dont la méthode comparative est alimentée par le paradigme de l’herméneutique juridique et son corollaire le pluralisme juridique. Les résultats issus du dialogue comparatif devraient participer à une amélioration des situations problématiques décelées dans les sphères concernées. The rule process of lawsuits based on arbitration has filled out huge economic ambitions related to judicial spheres where this mechanism has been established. The efficiency of this process, which among others, has led to an application, indeed a real execution of the protagonists, is somewhat a guarantee to the fulfilment of these ambitions. However, this process can be compromised because of the cancellation of the arbitral sentence by a judge whose intervention in the process can either reinforce it or destroy it. This situation mainly explains the reasons why the juridical doctrine is in favour of a solid collaboration. How do the juridical sphere of Quebec and Ohada tackle this issue of the cancellation of the arbitral sentence? What are the juridical effects stemmed from the comparism of this situation in both spheres? The way the substance of this research appears and whose comparative method is fed by the paradigm of the juridical hermeneutics and its juridical pluralism corollary. The results stemmed from the comparative dialog should participate in improving problematic situations detected in the applied spheres.
Keywords: Annulation; Arbitrage; Arbitragem; Arbitration; Litiges; Sentence arbitrale

Arbitration: One Size Does Not Fit All: Necessity of Developing Institutional Arbitration in Developing Countries - Namrata Shah, Niyati Gandhi (Journal of International Commercial Law and Technology, 2011)
Litigation in developing countries has many defects which has prompted a need for the development of alternative dispute resolution mechanisms. Arbitration, being one such substitutive mechanism as a type of private litigation is the most suitable for the same. This paper deals with the need to develop institutional arbitration to co-exist with ad hoc arbitration and scale it down to be available for dispute resolution in developing countries using an illustration of India. Certain recommendations to make institutional arbitration, which is considered to be appropriate for International commercial dispute resolution, suitable for domestic disputes in developing countries have been highlighted.
Keywords: Arbitrage; Arbitragem; Arbitration; Developing countries; Institutional arbitration

Les MARC en OHADA (Journal africain du droit des affaires, 2011)
GENERALITES SUR LES MARC La justice arbitrale La médiation commerciale : une alternative au système judiciaire L’utilité de l’expertise Interactions entre médiation et arbitrage LES MARC EN OHADA Approche culturelle des MARC en OHADA Regards franco-africains sur les étapes de la médiation commerciale La gestion d’une procédure d’arbitrage : vue d’un opérateur économique de l’espace OHADA Analyse comparée du droit de l’arbitrage OHADA et du droit international L’arbitrage de la Cour Commune de Justice et d’Arbitrage (CCJA) de l’OHADA Nouveau Règlement de médiation de la Cour d’Arbitrage de Côte d’Ivoire (CACI)
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Mediation; Médiation

L'arbitre international : étude de droit comparé - Partida, Sebastián (Université Paris 2, 2011)

A comparative study: Arbitration agreement in OHADA and People's Republic of China arbitration laws - Samassekou, Mamoudou; Song, Lianbin (Journal of Politics and Law, 2011)
This article aims to compare the arbitration agreement of the OHADA legal system to that of the People's Republic of China. In the Chinese legal system the parties to a contract are required to have an arbitration agreement written before the occurrence of any incident in the execution of their contract. The parties must specify in advance, in the said agreement, the chosen arbitration institution for potential disputes. In the OHADA legal system, the parties are free to decide before or during execution of the contract of an arbitration agreement. They may also decide whether in case of a dispute, they would want to refer to an institutional arbitration or an ad hoc arbitration. According to the chosen legal system the consequences are different.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration Agreement; China-OHADA

Contratación y arbitraje internacionales - Méndez Silva, Ricardo (Doctrina Jurídica, 2010)
https://archivos.juridicas.unam.mx/www/bjv/libros/6/2776/1.pdf
Keywords: Arbitrage international; Arbitragem; Arbitraje; Arbitraje Comercial International; Arbitration; International commercial arbitration

Uluslararası Ticari Tahkim ve geçici hukuki koruma tedbirleri - Balkar, Süheyla (Galatasaray Üniversitesi, 2010)
Yargılama sürecinin yaratabileceği olumsuzluklardan hak arayan kişileri korumaya ve onlara hukuki güven ortamı sağlamaya yarayan geçici hukuki koruma tedbirleri tüm hukuk sistemleri açısından yargılamanın etkinliğinin teminatıdır. Devlet yargısında olduğu gibi, özellikle ticari uyuşmazlıklar açısından büyük önem taşıyan tahkim yargılamasında da bu tür tedbirlerin varlığına ihtiyaç gün geçtikçe artmaktadır. Çalışmamızda, uluslararası ticari tahkime konu olan uyuşmazlıklarda geçici koruma tedbirlerine hükmedebilme yetkisi, bu yetkinin sınırları ve bu tür tedbir kararlarının icrası meseleleri gerek mahkemeler gerekse hakemler açısından incelenmiştir. Interim relief or provisional measures may be as important as an award on the merits of any arbitration case. If the subject matter of the arbitration is not preserved, a long and costly arbitration procedure may just end up in learning at the time of execution of the award, that there is no substance right to enforce anymore. Consequently, the topic of provisional measures, in the understanding that they maintain the status quo of the arbitration, becomes of great relevance to all who may be involved in the arbitration world. Nonetheless, the topic of provisional measures, the powers to enforce them and even, the degree of court cooperation/intervention in such matters, varies from one country to another. Unfortunately, provisional measures in arbitration face several problems related to the lack of actual enforceability of the arbitrators? resolutions as well as to the good will of the parties to arbitrate and to grant the other parties enough securities that the subject matter of the arbitration will be executable.
Keywords: Arbitration; Geçici hukuki korumalar; Hukuksal korunma; Incompatibility; Koruma tedbirleri; Legal protection; Protection measures; Tahkim; Temporary legal protection; Uyuşmazlık

Différends entre investisseurs et État : Prévention et modes de règlement autres que l’arbitrage - Conférence des Nations Unies sur le Commerce et le Développement (CNUCED) (Publications des Nations Unies, 2010)
Keywords: Différends; Etat; Investisseurs; Modes de règlement; Prevention

Chapitre II. Le consentement à l’arbitrage, manifestation d’une volonté contenue - Diallo, Ousmane (Le consentement des parties à l'arbitrage international, 2010)

Le consentement des parties à l’arbitrage international - Diallo, Ousmane (International, 2010)
Mode juridictionnel privé de règlement des litiges, l’arbitrage offre une alternative à la saisine du juge. Qu’il soit interne ou international, l’arbitrage repose généralement sur le consentement des parties. C’est donc à juste titre que celui-ci a été qualifié de pierre angulaire de l’arbitrage. Effectivement, c’est sur ce consentement que la justice privée s’est longtemps appuyée pour justifier sa légitimité, revendiquer son autonomie et conquérir un nouvel espace de liberté. Solidement porté par le consentement qui lui sert de fondement, l’arbitrage n’a cessé de se développer au point d’apparaître de nos jours comme le mode normal de règlement des litiges du commerce international. On le dit particulièrement adapté au règlement de telle ou telle catégorie de litiges, manière d’affirmer sa vocation à étendre son emprise. Parvenu à l’âge adulte, c’est donc tout naturellement que l’arbitrage cherche à s’affranchir du caractère exceptionnel que lui imprime sa subordination au consentement, lequel apparaît de plus en plus comme un îlot de résistance à son expansion, sinon à son efficacité. Première étude d’ensemble sur la question, le présent ouvrage a le grand mérite d’exploiter au mieux la richesse qu’offre une approche comparative, non seulement pour retracer le rôle important joué par le consentement dans l’évolution de l’arbitrage, mais aussi, et surtout, pour mettre à nu les multiples tentatives en vue de son émancipation de la tutelle des parties. Il en résulte une éclipse momentanée du consentement, qui ravive les contestations de la compétence arbitrale et dévoile à nouveau sa subordination au consentement, facteur de légitimation par excellence de l’arbitrage. C’est dire que le consentement ne fait pas que survivre à ces assauts, il réussit même à prospérer. Autant de questions aussi brûlantes qu’actuelles, sur lesquelles cet ouvrage offre une analyse détaillée et des solutions originales.
Keywords: Arbitrage international; Arbitration; Droit privé; International arbitration; Litige; Règlement des différends

L’ordre juridique arbitral : réalité, utilité et spécificité - Gaillard, Emmanuel (McGill Law Journal, 2010)
L’ordre juridique arbitral existe-t-il ? S’il est perçu par les arbitres, souvent de manière intuitive mais très réelle, c’est qu’il existe. L’ordre juridique arbitral ne doit pas cependant être exclusivement conçu comme une représentation mentale du rôle des arbitres et de la source de leur pouvoir de juger. Il existe en tant que système de droit.

Enforcement of Arbitral Awards in Sub-Sahara Africa - Onyema, Emilia (Arbitration International, 2010)
As the world celebrated the fiftieth anniversary of the New York Convention in 2008 it became necessary to examine the enforcement regimes for arbitration awards in Sub-Sahara Africa. This article examines the provisions for the recognition and enforcement, and requirements for the setting aside of both domestic and international arbitral awards under the arbitration laws of OHADA member states, Nigeria and Sudan, as representative of the legal regimes in Sub-Sahara African countries. The New York Convention applies to Convention awards in half of the countries of Sub-Sahara Africa. It is therefore relevant to examine the requirements for the enforcement of non-Convention awards in those states that are members of the New York Convention, and also in those states that are not members of the New York Convention. Different arbitration laws and regimes apply in the three representative jurisdictions chosen for this comparative analysis and these are also representative of the legal regimes in those countries with arbitration laws in the region. Though a generally supportive tendency towards the enforcement of arbitral awards can be gleaned from the examination of some arbitration-related judgments, this article again highlights the importance for the remaining countries in the region yet to sign up to and implement the New York Convention to consider adopting it, and for more arbitration hearings to be held within the region.
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Enforcement of Arbitral Awards; Sub-Sahara

Chapter 42, Dissenting Opinions by Party-Appointed Arbitrators in Investment Arbitration - van den Berg, Albert Jan (Looking to the future: essays in international law in honor of W. Michael Reisman, 2010)
Dissenting opinions appear to have become an accepted practice in international arbitration. Th e current debate concentrates on their procedure, form, and content. Alan Redfern noted that “[a]t present, a generally relaxed attitude towards dissenting opinions seems to be taken not only by the arbitral institutions, but also by the arbitrators themselves … .” In this contribution, I would like to explore the cautionary note with which Redfern concluded his seminal article, namely, that the “[t]ime has perhaps come to inquire whether the present leniency towards dissenting opinions … has gone too far.” I propose to do so with respect to investment arbitrations because ade available publicly, particularly party-appointed arbitrators’ dissenting opinions.
Keywords: Arbitrage; Arbitration; Arbitrator; Dissenting opinion; Investment arbitration; Opinion dissidente